Complexation with β-cyclodextrin derivatives enhanced the bioavailability of quercetin through improving solubility and inhibiting recrystallization - Qiao Chen; Hai-Xia Xu; Ji-Guang Chen; Lin Dai; Bao-Geng Fu; Qing-Feng Zhang (Journal of Food Engineering, 2027)

A review on the efficient hydrodeoxygenation of lignin-derived phenolic compounds over bimetallic catalysts - Guangming Liang; Xiaowen Bao; Yu Chen; Zhengtao Lin; Yao He; Riyang Shu (Fuel, 2027)

Whole genome sequencing analysis and functional characterization of Lacticaseibacillus rhamnosus HP-B1083 - Da-Hu Zhang; Zhen-Dong Tian; Bao-Zhi Ge; Qian-Meng Qi; Jia-Lin Lv; Hang Wu; Shao-Yang Hou; Shu-Hang Zhang (Brazilian Journal of Microbiology, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Integrated volatilomics, lipidomics, and precursor validation provide insights into the superior flavor of Gaoyou salted duck egg yolks - Jingyi Guo; Songyi Lin; Huan Liu; Yafei Zhang; Zhijie Bao (Food Research International, 2026)

Influence mechanism of tritium exposure on the growth and microcystin synthesis of Microcystis aeruginosa under rising temperature - Xue Gong; Xin-wen Zhang; Ling-shu Xu; Chuan-dong Wang; Bao Zhang; Qian Fu; Qi-lin Dai; Jin-long Lai (Environmental Pollution, 2026)

Discriminative predation stabilizes the fig-fig wasp mutualism in a patch-dynamic framework - Xiao-Fen Lin; Lin Wang; Jin-Bao Liao; Rui-Wu Wang (Ecological Modelling, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Analysis of the vibration characteristics of liquid droplets in oil induced by CPG electric field with data-driven assistance - Ye Peng; Yaozhong Hu; Haifeng Gong; Lin Yan; Bao Yu; Hong Yin; Ping Ouyang (Journal of Environmental Chemical Engineering, 2026)

Liupao tea alleviates high-fat diet-induced obesity by re-establishing metabolic homeostasis of short-chain fatty acids and chenodeoxycholic acid - Yuru Tan; Xuancheng Wang; Anlong Song; Song Xu; Xueting Lin; Bao Yang; Jichu Luo; Ying Tong; Mingsen Wen; Xuan Guan; Peiting Li; Zhe Luo; et al. (Food Research International, 2026)

Analysis of the deterioration rule and perception mechanism of egg yolk powder odor based on volatile omics, molecular docking and molecular dynamics simulation - Jiahui Song; Enhui Ma; Renrui Zheng; Zhuohang Huang; Jun Jiang; Zhijie Bao; Songyi Lin (Food Research International, 2026)

Retraction notice to “Investigating the causes of yolk mudding during storage of salted eggs: Water migration accelerates protein and lipid oxidation” [Food Chem. 481 (2025) 144112] - Jiyu Zhang; Songyi Lin; Sichen Lu; Xunze Yuan; Yue Tang; Zhijie Bao (Food Chemistry, 2026)

Multi-omics analysis provides mechanistic insights into tanninase-assisted flavor evolution in Phyllanthus emblica L. wine - Jie Chen; Xinyong Zhang; Ni Liu; Xujie Chen; Yue Wang; Qi Lin; Yuanyuan Bao (Food Chemistry, 2026)

Fabrication of algal oil oleogels with zein-alginate Conjugates: Ca2+-tuned foam templating - Yuge Bao; Qiming Wang; Zhenan Rao; Yangjie Zhou; Jichun Zhao; Lin Lei; Jian Ming (Food Hydrocolloids, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

The ss3a/be2b double mutant yields high resistant starch through cooperative regulation of starch fine structure in indica rice - Yining Ying; Jiayuan Chang; Zhongwei Zhang; Lin Zhang; Xuexue Wang; Chengqi Yan; Jinsong Bao (Carbohydrate Polymers, 2026)

CRISPR/Cas12a and CHA-based SERS platform for ultrasensitive nucleic acid detection - Huimin Wang; Chengxin Bao; Lin Liu; Feiwu Li; Yuxuan He; Xiangguo Liu; Yuejia Yin; Shuping Xu (Analytica Chimica Acta, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Indole biodegradation by Burkholderia contaminans DM32: Process characteristics and the IifR-mediated molecular mechanism - Ying-Si Wang; Jie Wang; Hong-Bing Tao; Hui-Zhong Liu; Bei-Bei Wang; Zhen-Lin Liao; Hong Qi; Qing-Shan Shi; Gang Zhou; Xiao-Bao Xie (International Biodeterioration & Biodegradation, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Wearable multifunctional conductive fabrics for integrated smart monitoring and protection of the human body - Miao Miao; Wendi Liu; Wuwei Bao; Rui Ma; Hao Yao; Zhenzhe Huang; Zixuan Lin; Ying Han; Wentao Shen; Yao Wang; Yifan Cui; Xinyang He (Chemical Engineering Journal, 2026)

Decoupling of mass-based and oxidative-potential-based source contributions to PM2.5 in Nanjing: Random forest combined with PMF analysis - Yan-Yu Chen; Fang Cao; Chang-Liu Wu; Xiao-Ying Yang; Yu-Ting Mei; Yuan Dai; Meng-Ying Bao; Wen-Huai Song; Yan-Lin Zhang (Atmospheric Environment, 2026)

Species Diversity, Parasitism Rates, Longevity, and Population Dynamics of the Parasitoid Complex Attacking Ophelimus bipolaris in China - Jin Hu; Yuan-Hao Li; Jing-Hui Su; Jin-Bo Sun; Guo-Bao Qin; Yan Qin; Lai-Feng Luo; Lin-Xia Feng; Kai-Jian Han; Zoya Yefremova; Jun Li; Xia-Lin Zheng (Neotropical Entomology, 2026)

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Quantifying pedestrian thermal comfort under extreme heat using 360° street view factors - Mingjie Zhang; Hai Yan; Renwu Wu; Huaizhen Zhu; Jiachen Liu; Wei Yang; Lin Zhu; Jiangnan Shi; Fan Yang; Zhiyi Bao (Sustainable Cities and Society, 2026)

Ferritin-mediated copper delivery induces dual cell death across diverse leukemia types - Huaiji Wang; Wenjing Wang; Wenqiang Sun; Feifan Liu; Caopei Zheng; Xiaoyun Lin; Yuhua Li; Weier Bao; Xiaoming Hu; Guobin Qi; Feng Li; Guanghui Ma; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Argo trajectory-derived current assimilation and its impact on the mid-layer circulation in the South China Sea - Jingyi Liu; Xiaohui Wang; Senliang Bao; Pinqiang Wang; Huizan Wang; Xiang Wang; Conghao Lin; Ciqiang Luo; Yuzhu An (Ocean Modelling, 2026)

Industrial waste salt pyrolysis toward zero liquid discharge: Enabling efficient organic removal and resource recovery - Zhi-Bo Li; Xiang-Lin Chang; Juan Xie; Rong Chen; Xiaochang C. Wang; Bao-Shan Xing (Journal of Water Process Engineering, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Spatial–Temporal Distribution Characteristics of Nitrogen in the Jingjiang Reach of the Yangtze River during 1992–2015 - Yihao Wu; Yuhong Zeng; Runpei Liu; Xiaoning Liu; Bao Qian; Li Lin (Water, Air, & Soil Pollution, 2026)

Maneuver-Aware Residual Multi-Scale LSTM for Short-Term Vessel Trajectory Prediction in Port-Approach Waters - Xinyue Lin; Xiaohan Zhang; Wendong Bao; Yawen Duan; Jiansen Zhao (Journal of Marine Science and Engineering, 2026)
Accurate short-term vessel trajectory prediction is important for traffic monitoring and collision-risk screening in port-approach waters, where vessels frequently turn, accelerate, decelerate, and merge into traffic lanes. This study develops a maneuver-aware residual multi-scale long short-term memory (LSTM) framework for Automatic Identification System (AIS)-based 10–30 min trajectory prediction. The method predicts residual displacement relative to the last observed position, constructs maneuver-aware features from local displacement, course variation, speed variation, turning rate, and acceleration-like terms, and compares fixed and maneuver-guided multi-scale fusion strategies. Experiments are conducted on public AIS data from San Francisco Bay and adjacent approach waters using Maritime Mobile Service Identity (MMSI)-level train/validation/test splits and three random seeds. The largest observed gains come from residual prediction and maneuver-aware features. In the three-seed main evaluation, the fixed multi-scale LSTM (Fixed-MS-LSTM) provides the strongest 10 min accuracy, while the maneuver-guided multi-scale residual LSTM (MGMS-RLSTM) achieves lower average displacement error (ADE) at 20 and 30 min and learns distinct temporal-scale preferences across straight, turning, and speed-changing samples. Encounter-oriented closest point of approach (CPA) and time to closest point of approach (TCPA) evaluation further shows that the residual multi-scale models support more accurate CPA/TCPA-based high-risk screening under the evaluated benchmark. These findings indicate that maneuver-guided fusion can be characterized as a horizon-dependent scale-selection mechanism that complements the fixed multi-scale counterpart.

Adaptive Multi-Scale Frequency-Domain Reconstruction for Multi-Source Gravity Data Fusion - Menghan Xi; Lin Wu; Zuoqin Shi; Qianqian Li; Shi Liu; Lifeng Bao (Journal of Marine Science and Engineering, 2026)
The gravity navigation reference map is a foundational element of gravity matching-aided navigation systems, as it directly determines positioning accuracy and overall navigation performance. To improve fused gravity anomalies and reduce reliance on manually selected parameters, this study proposes an adaptive multi-scale frequency-domain reconstruction (AMFR) algorithm. Specifically, the target ocean covered by multi-source satellite gravity data is divided into multiple scales, and distinct fusion parameters are assigned according to the characteristics of multi-source gravity data in different sea areas to enhance the accuracy of the fused gravity navigation reference map. Seven fusion schemes with different filtering diameters and weighting strategies are designed for comparative analysis. We evaluate the algorithm’s performance using measured gravity data with varying spatial distributions from the South China Sea and the Western Pacific Ocean, employing both RMS comparison and matching positioning experiments. Experimental results demonstrate that the RMS of the gravity navigation reference map constructed by the proposed AMFR algorithm is reduced by 30.4%, and the matching positioning accuracy is improved by 23.4%. The AMFR algorithm effectively enhances the precision of the gravity navigation reference map and improves the navigation performance of the gravity matching-aided navigation system.

Metagenomic screening of antimicrobial peptide candidates and isolation of two active peptides from bat gut bacteria - Zishun Zhao; Yanhui Zhao; Ying Sun; Yongli Bao; Jiang Feng; Tinglei Jiang; Aiqing Lin (World Journal of Microbiology and Biotechnology, 2026)

Agmatine induces mitophagy via the PTS-I2R pathway to increase autophagic flux and attenuate sepsis-induced intestinal epithelial cell apoptosis - He Jin; Shuangqin Yin; Yongming Li; Xiangwei Hou; Lin Qiao; Tianyin Kuang; Jing Zhou; Xue Yang; Wanting Zeng; Chao Fan; Li Luo; Lihui Wang; et al. (Inflammation Research, 2026)

Three bioactive dibenzocyclooctadiene lignans from the fruits of Kadsura coccinea - Wen-Ming Wu; Jian Liu; Chao Chen; Bao-Lin Wang; An Jin (Natural Product Research, 2026)

LEO satellite-enhanced GNSS-R joint position and velocity estimation algorithm for moving targets - Xuqiao Wang; Lan Du; Peiyuan Zhou; Zejun Liu; Zhongkai Zhang; Ken Deng; Lin Bao (International Journal of Remote Sensing, 2026)

Role of NADPH oxidase generated O2− in seed germination and cold stress response of Brassica napus - Wei-liang Qi; Guo-yan Bao; Mei-ying Sun; Wen-juan Ma; Xuan-ting Yang; Xiang-hong Gao; Miao-xin Zhou; Qi-lin Wang (Protoplasma, 2026)

Effects of volcanic altitudes on the rhizosphere microbial community composition and structure of Euphorbia maculata - Yaozhou Zhang; Han Lin; Qixiu Cheng; Haining Wang; Yiming Zhang; Yueming Bao; Rui Qin; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Data-model-driven recoil attenuation for networked riser-tensioner systems via dynamic event-triggered control - Shou-Xiang Yan; Zidong Ai; Bao-Lin Zhang (Ocean Engineering, 2026)

The domestication-associated WHP10 tandem cluster of amino acid transporter genes enhances whole-plant protein accumulation in maize - Wenhao Li; Youliang Li; Xiang Lin; Ruilin Chen; Wenjing Li; Chong You; Di Chen; Lulu Gao; Xiaoling Li; Shiqi Luo; Yunlong Li; Yuhua Long; et al. (Molecular Plant, 2026)

Urban heat exposure patterns and domain-specific executive function in adolescents - Lixin Hu; Wenwen Bao; Zhengge Jin; Jun Hong; Wenxin Ge; Yawen Tan; Liqing Yao; Wanxin Wu; Jiaqi Chen; Xiuzhi Yang; Zhuowen Wu; Sichun Lin; et al. (Environmental Research, 2026)

Ultrastable Pt clusters confined on CeO2 nano-islands for efficient low-temperature propane dehydrogenation over carbon nanotube - Jian Tao; Shu-Lin Liu; Zi-Dan Li; Wan-Yi Wang; Chuan-Feng Huang; Bao-Lian Su; Zhao Wang (Chemical Engineering Journal, 2026)

Onsite catalytic hydrogen co-combustion heating enables ultra-energy-efficient methane elimination - Long Cao; Jing-Cai Zhang; Bao-Lin Hou; Wei-Zhen Li (Chemical Engineering Journal, 2026)

Injectable icaritin-loaded Pickering emulsion gel for overcoming immunotherapy resistance in malignant ascites - Huijuan Wei; Jing Wang; Lin Zhong; Jia Zhang; Xuqi Sun; Xuanwen Bao; Haibo Zhang; Dong Chen; Jianhao Liu; Xiaomeng Dai; Peng Zhao (Chemical Engineering Journal, 2026)

Linking Mo/Fe ion conversion to green treatment of sulfonylurea pesticides in farmland drainage: Role of directed electron transfer and self-produced hydrogen peroxide - Bingkun Liu; Weijun Tian; Bingjie Huo; Xinbo Wang; Xinran Yu; Wei Bao; Ke Yang; Minghan Li; Yushan Wei; Yinming Ji; Daoqing Lin (Chemical Engineering Journal, 2026)

Alginate-based composite hydrogel derived from Azotobacter vinelandii Av1: Preparation, properties, and wound-healing efficacy - Peng Yang; Rongqiang Chen; Siyuan Peng; Lin Zhu; Yifei Chang; Zhi Bao; Xiaodan Fu; Mengshi Xiao; Min Yang; Haijin Mou (Carbohydrate Polymers, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Lactate acts as a metabolic brake on inflammation by repressing NLRP3 transcription via NF-κB inhibition - Hsin-An Lin; Hsin-Chung Lin; Chih-Yung Chiou; Hao-Hsuan Peng; Yu-Jen Chen; Bo-Ying Bao; Kuen-Jou Tsai; Chao-Feng Lin; Chieh-Tien Shih; Sheng-I. Hu; Kuo-Yang Huang; Lih-Chyang Chen (Inflammation Research, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Differential light spectrum regulation of oogenesis and spermatogenesis in Plectropomus leopardus - Hui Ding; Lin Li; Da Zheng; Mingjian Liu; Jinyang Xie; Binglin Li; Yuli Li; Zhenmin Bao; Bo Wang; Jingjie Hu (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mechanistic characterization of insecticidal Shiva toxin interactions with Drosophila melanogaster nicotinic acetylcholine receptors - Kyle D. Schneider; Joseph Tourtois; Daniel Bertrand; Kumiko Kambara; Daniel Hulbert; Alexandra Haase; Sophia R. Kanniainen; Brian DeVree; Robert M. Kennedy; Lin Bao (Pesticide Biochemistry and Physiology, 2026)

Adaptive dynamic programming-based integral sliding mode recoil control for deepwater drilling riser systems with parameter uncertainties - Yue-Ting Sun; Bo Yin; Bao-Lin Zhang (Ocean Engineering, 2026)

Disturbance observer-based memory-event-triggered recoil control for riser systems under deception attacks - Yan-Dong Zhao; Hai-Yang Yu; Bao-Lin Zhang; Zidong Ai (Ocean Engineering, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Managing street-tree health under rapid urbanization: Relative roles of street context and root-zone conditions in a subtropical city - Wenting Wang; Min Wu; Hai Yan; Ying Chen; Zichen Zhao; Lin Zhu; Jiangnan Shi; Renwu Wu; Fan Yang; Zhiyi Bao (Journal of Environmental Management, 2026)

Enhancing urban river self-purification through riverbed substrates configuration: A nature-based solution for nutrient removal and restoration planning - Yu Xin; Lin Liu; Shao-Hua Chen; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Sciences, 2026)

Sustainable stabilisation of collapsible loess with quicklime-recycled GGBS mixtures - Bao-Lin Dai; Chao Zhou; Qing-Yi Mu; Jian-Bing Peng (Geomechanics for Energy and the Environment, 2026)

Fluorescence spectroscopy coupled with machine learning for identification of recycled PET - Ze-Long Deng; Qing-Hua Yang; Qi-Zhi Su; Xue-Chao Song; Qin-Bao Lin (Food Packaging and Shelf Life, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Gelatin microspheres reinforced by o-nitrobenzyl–vinyl coupling for 3D cell culture and high-fidelity extrusion printing - Weichao Zhu; Chunling Ren; Qiaolin Chen; Yuchen Zhang; Libin Zhu; Liang Chen; Li Jiang; Tuan Liu; Qiuning Lin; Linyong Zhu; Bingkun Bao (Chemical Engineering Journal, 2026)

Efficient self-accelerated degradation of polyester enabled by encapsulated enzymes for closed-loop recycling - Ruiqi Bao; Ning Zheng; Zhenchao Zhou; Tariq Mehmood; Xinyi Shuai; Zejun Lin; Hong Chen (Chemical Engineering Journal, 2026)

Synergistically enhanced nanofiber aerogels by directional freeze-drying and multiple hydrogen bond cross-linking for high-performance piezoresistive sensor - Xiao Su; Yufeng Bao; Zhe Tang; Asim Shahzad; Yaowei Luo; Xinyu Zeng; Zhifei Liang; Yangqing Wu; Lin Shu; Renbo Zhu; LinGe Wang (Chemical Engineering Journal, 2026)

Efficient DNA Extraction Coupled with Fluorescence Loop-Mediated Isothermal Amplification (LAMP) for On-Site Early Warning Detection of Vibrio parahaemolyticus - Fengyi Liu; Qilin Geng; Xue Sun; Jie Lin; Xuan Zhu; Danyang Wang; Xiao-Hua Zhang; Jingjie Hu; Shi Wang; Lisui Bao; Jia Lv (Marine Biotechnology, 2026)

Sex differences in resting-state hypothalamic connectivity and its relationship with negative emotion and behavior measures in young adults - Guangfei Li; Yiran Shao; Lin Yang; Yanan Su; Mengmeng Wang; Zhao Zhang; Xiaoyi Sun; Bao Li; Xiaolin Wang; Yu Chen; Guangyu Bin; Chiang-Shan R. Li (Brain Structure and Function, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Facile and inherently safer synthesis of double-base propellants: Correlating microstructural homogeneity with combustion behavior - Chuanxiang Guo; Weihan Wan; Le Wang; Yitao Liu; Yuhang Bao; Yuqi Huang; Zucheng Wu; Xiangyang Lin (Process Safety and Environmental Protection, 2026)

Integrated internal model and feedforward-based fuzzy control for active recoil suppression of drilling risers - Yuan-Jie Jiang; Bao-Lin Zhang; Yun Zhang; Zidong Ai; Yan-Dong Zhao; Yanlong Cao (Ocean Engineering, 2026)

Adaptive backstepping sliding mode heading control for wave glider using neural network–based extended state observer - Qi-Jin Feng; Bao-Lin Zhang; Meng Cui; Peiyuan Yu; Qi Zhao; Zidong Ai; Xiujun Sun (Ocean Engineering, 2026)

Vertical stratification of soil moisture memory and its response to climatic driver factors in inner Mongolia (2001-2024) - Chaofan Zhou; Huili Gong; Beibei Chen; Xiaojuan Li; Lin Zhu; Mengxuan Bao; Jiajun Zhu (Journal of Arid Environments, 2026)

Evaluation of the effects of pulsed electric field and pasteurization on the quality of whole egg liquid: A comparative analysis of microbial safety and flavor characteristics - Liu Dong; Xinqing Lu; Zhijie Bao; Songyi Lin (Food Research International, 2026)

Proteomic-lipidomic based MALDI-TOF MS for rapid discrimination of Bacillus cereus and Bacillus thuringiensis and its emetic-producing strain in food - Xi Zeng; Yu Wang; Yun-pei Mai; Bao-zhu Jia; Hong Wang; Zhen-Lin Xu (Food Chemistry, 2026)

Diagnosing urban ecological vulnerability in multi-mountainous city from a 3D landscape perspective - Peijia Peng; Xun Lin; Yu Bao (Ecological Engineering, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Deep Learning-Based Monthly Runoff Simulation in Changing Environments: Enhancing Accuracy by Reducing Data Redundancy - Shenghong Liu; Ji Liu; Shaokang Yang; Zhenxin Bao; Shan-e-hyder Soomro; Wenjuan Chang; Qingxia Lin; Qirui Zhang; Gantao Yang; Ruilin Geng; Haiyu Wang; Longteng Dai (Water Resources Management, 2026)

Viscous drainage and dripping of eclogitized lower crust in the eastern Pamir imaged by geophysical data - Gang Wen; Yixian Xu; Bo Yang; Xiubin Lin; Xuewei Bao; Runyuan Zeng; Yi Zhang (Science China Earth Sciences, 2026)

Effect of Limosilactobacillus reuteri SBC5-3 Cell-free Supernatant on Growth Performance, Intestinal Inflammation, and Microbiota in Weaned Piglets Challenged With Enterotoxigenic Escherichia coli K88 - Le Xu; Guoying Bao; Shiyu Chen; Chen Liu; Xiannian Zi; Minjie Hu; Qinghua Liu; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Deletion of the SHORT Syndrome Gene Prkce Results in Brain Atrophy and Cognitive and Motor Behavior Deficits in Mice - Yu-Long Bao; Wei-Peng Duan; Yan Yang; Zhijie Lin; Ying Shen; Rui Zheng; Xin-Tai Wang (Neuroscience Bulletin, 2026)

Dynamic ecosystems of tumor drug resistance mechanisms: from molecular heterogeneity to systemic interventions - Qiaohong Bao; Hang Chen; Jiali Wu; Yahui Wang; Xinmei Chen; Zhizhe Lin; Youfa Xu; Jianming Chen (Apoptosis, 2026)

Integrated Transcriptomics and Machine Learning Reveal Lipid Metabolism Related Genes in Ischemic Stroke - Qiu-Lin Wang; Chang-Le Fang; Tian-Hao Bao; Rui-Ze Niu (Journal of Molecular Neuroscience, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Active time-delay recoil control for deepwater drilling riser systems: A Q-learning-based approach - Zidong Ai; Shou-Xiang Yan; Bao-Lin Zhang (Ocean Engineering, 2026)

Achieving “one stone, three birds”: A solid-waste steel-slag-derived system for synergistic antibiotic degradation and CO2 capture - Shiping Zhang; Xiaoyong Wu; Baolin Zhao; Gui Yang; Shenxu Bao; Xueying Chen; Ling Xia; Yao Wang; Juan Long; Yang Wu; Lin Wang; Binbin He (Journal of Cleaner Production, 2026)

Plant diversity shifts soil phosphorus and nitrogen limitations to carbon processes along latitudinal gradients: Role of nutrient stoichiometry - Belayneh Azene; Wenjie Bao; Chaoying Yang; Awoke Guadie; Yalemzewd Nigussie; Min Cao; Kun Xu; Yun Deng; Hua Huang; Guanghong Cao; Feng Liu; Shangwen Xia; et al. (Forest Ecology and Management, 2026)

Pulsed electric field technology as a strategy for achieving the synergistic effect of enhancing the safety and flavor quality of egg yolk liquid - Liu Dong; Enhui Ma; Xinqing Lu; Zhijie Bao; Songyi Lin (Food Chemistry, 2026)

Achieving 17.65% efficiency in organic solar cells by neutral linker engineering in dimerized small-molecule acceptors - Jianan Niu; Xue Zhou; Mingxin Sun; Fuzhen Bi; Guoqing Lin; Cheng Sun; Tan Wang; Mingliang Sun; Shuguang Wen; Xichang Bao (Chemical Engineering Journal, 2026)

Cation-anion synergistic interactions in ion-regulated cholesteric liquid crystal Hydroxypropyl methylcellulose coatings for lithium metal batteries - Zhanpeng Du; Yun Huang; Fengliang Wang; Lei Zhang; Jing Tao; Jin Bao; Heguo Zeng; Jiajun He; Huihui Li; Chao Zou; Chunmei Feng; Bingshu Guo; et al. (Chemical Engineering Journal, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Analysis of urban design rainstorm patterns based on parameter estimation and model approaches - Jun Zhao; Lin Yang; Long Zhu; Cuishan Liu; Zhenxin Bao; Min Liu; Qiyan Huang; Sadashiv Chaturvedi; Yu Liu; Yuhan Zhao (Stochastic Environmental Research and Risk Assessment, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Unraveling iron and zinc efficiency in pepper: integration of root architecture, uptake kinetics, and transcriptional regulation - Cheng-Xiang Zhou; Wei Zhang; Bao-Gang Yu; Hao-Feng Yang; Yuan Wang; Kai Sun; Fu-Lin Zhao; Huai-Yu Yang; Prakash Lakshmanan; Xin-Ping Chen; Chun-Qin Zou (Plant and Soil, 2026)

Electromyographic features for quantitative assessment of lower limb spasticity after stroke: a feasibility study - Lin Wu; Benjian Zou; Jiawei Liu; Chao Wang; Samit Chakrabarty; Ping Zhou; Tianzhe Bao; Sheng Quan Xie (Medical & Biological Engineering & Computing, 2026)

A hybrid deep learning and empirical model for short-term spatio-temporal ZTD forecasting for China - Xiongwei Ma; Haoran Huang; Qi Zhang; Bao Zhang; Qingzhi Zhao; Xiaohu Lin; Yunzheng Huang; Yiyang Zhao; Yibin Yao (Journal of Geodesy, 2026)

NUFIP1-engineered exosomes modulate propofol-induced neurotoxicity in neonatal rats via the ERS apoptotic pathway - Pengyue Zhao; Yang Yan; Bin Lan; Xingpeng Yang; Yizhao Ma; Yichen Bao; Lin Qi; Xiaohui Du; Songyan Li; Wen Sun (Apoptosis, 2026)

Retraction Note: Tetraspanin 1 inhibits TNFα-induced apoptosis via NF-κB signaling pathway in alveolar epithelial cells - Lawei Yang; Yahong Wang; Zhanchun Pan; Shenglan Gao; Bao’an Zou; Ziying Lin; Dehui Feng; Changmei HuangFu; Gang Liu (Inflammation Research, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Seasonal variation regulates the efficacy of phytoremediation strategies on the rhizosphere resistome in urban river ecosystems - Yu Xin; Li-Hua Liu; Lin Liu; Shao-Hua Chen; Yu-Ming Zheng; Quan-Bao Zhao (Journal of Hazardous Materials, 2026)

Decarbonization in green building rating systems: A systematic review on embodied and operational carbon credits - Wai Lam Ng; Kyle Sebastian Mulya; Keng Yinn Wong; Huiyi Tan; Zhikang Bao; Lin Chen; Pow-Seng Yap; Peng Jiang; Kok Sin Woon (Journal of Environmental Management, 2026)

The response of microbial metacommunity to long-term exposure of nanoplastics and microcystin-LR in freshwater mesocosm - Chaonan Zhang; Feifan Bao; Min Zhang; Daohui Lin (Journal of Environmental Sciences, 2026)

Sex-specific associations between exposure to metal mixtures and mitochondrial DNA copy number: A repeated-measures study - Junxiu He; Xiaoting Ge; Sencai Lin; Yu Bao; Hong Cheng; Sihan Hu; Xiuming Feng; Qinghua Fan; Ying Yang; Xiaobo Yang (Journal of Environmental Sciences, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Effects of silver nanoparticles and nitrile fungicides on soil microbial community structure, metabolic functions, and resistance genes - Yiwang Wang; Ting Gao; Jiajia Liu; Shaoheng Bao; Fuli Wang; Ge Yao; Xiaoyan Lin; Shijie Jiang; Jinlong Lai; Penggang Han; Jiang Hui (Applied Soil Ecology, 2026)

Integrating biodiversity and key ecosystem services into the optimization of multi-scenario land use simulation in the Three-River-Source National Park region, China - Shengwang Bao; Fan Yang; Fanzhen Kong; Yongsheng Lin; Yingshuang Hu (Anthropocene, 2026)

Decoding microglial metabolic cell death and PANoptosis hub genes in subacute phase of traumatic brain injury: a multi-omics and experimental validation study - Zhe Wu; Bao-ya Yang; Jin-qing Lai; Shi-hong Lin; Long Lin; Jian-long Chen; Jia-xiang Pan; Yao-xin Ruan; Xiang-rong Chen (Apoptosis, 2026)

Effects of temperature change pattern on the hatching of zooplankton resting eggs and community structure - Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Han Zhu; Yi-Long Xi (Hydrobiologia, 2026)

PRDX6 as a Ferroptosis-Related Hub Gene in the Entorhinal Cortex of Alzheimer’s Disease: A Multidimensional Bioinformatics and Experimental Validation Study - Xiaolin Li; Ziteng Man; Tiantian Cheng; Juan Song; Yanan Bao; Yu Lin; Hongyan Yang (Journal of Molecular Neuroscience, 2026)

The role of ribosomal protein RPL35A in heme regulation and hematopoiesis in the blood clam Anadara granosa - Mengshi Zhang; Yushan Liao; Zhihua Lin; Xin He; Yongbo Bao (Aquaculture, 2026)

Decontamination of volatile compounds from post-consumer recycled HDPE via supercritical CO2: Unravelling the critical role of co-solvent molecular structure - Ming-Yue Zhang; Qi-Zhi Su; Can Xu; Tian-Long Zhang; Huai-Ning Zhong; Qin-Bao Lin; Dan Li; Ben Dong (Waste Management, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Adjuvant-metal-ion-chelating PTEN mRNA with cell-membrane-coating augments the immune sensitivity for precise cancer immunotherapy - Mengyu Guo; Jin-Cheng Guo; Haodong Yao; Fene Gao; Lina Zhao; Lu Cai; Xuan Fan; Lin Bao; Xin Li; Xiaoyu Zhang; Mingdi Hu; Jie Mei; et al. (Science Bulletin, 2026)

Characteristics of particulate organic phosphorus and its release mechanisms for algal growth in sub-deep reservoirs - Jia Yu; Yan Zeng; Jingan Chen; Jingfu Wang; Hongyun Bao; Lin Shi; Hongchen Wu (Journal of Hydrology, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Human settlement doubled global oceanic island erosion and fire regimes during the early colonization stage - Fan Zhang; Huawei Wang; Chuan-Chou Shen; Jian Lin; Kai Zhou; Yongshun Chen; Kunshan Bao; Xinxin Li (Global and Planetary Change, 2026)

Egg yolk lecithin alleviates fatigue in flood-stressed mice by modulating hypothalamic microglial activation and the hepatic AKT/GSK3β pathway to attenuate neuroinflammation and metabolic dysregulation - Zhihong Lu; Songyi Lin; Zulayati Abula; Dongmei Li; Xuedi Zhang; Zhijie Bao (Food Research International, 2026)

A constitutive model for the mechanical behaviour of saturated frozen soils considering the dual effects of confining pressure - Bao-Lin Dai; Chao Zhou; Jean-Michel Pereira; Anh Minh Tang (Computers and Geotechnics, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Combustion acceleration in Al/CuO nanothermite films via gap-induced particle-advection mechanism - Xiaoxia Ma; Changcheng Bao; Lin Shi; Junzhe Xu; Wei Liu; Jimin Han; Li Yang (Chemical Engineering Journal, 2026)

Quorum quenching driven enzymatic activity and metabolic pathway modulation in anaerobic reactor for enhanced methane production - Zijing An; Yibin Bao; Yuwei Yang; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Hailu Fu; Hongjun Lin; Faqian Sun (Bioresource Technology, 2026)

Sewage sludge valorization into iron-carbon composites for environmental remediation: A critical review on synthesis, synergy, and sustainability - Haijie Ben; Yue Zhang; Huiming Zeng; Yulin Wang; Feng Lin; Zhikang Bao; Jian Zhang; Bingzhi Li; Jingxi Zhu; Meng Li; Yong Zeng; Chuan Liang; et al. (Bioresource Technology, 2026)

Air temperature differences and view factor influences between sidewalks and roadways in urban streets: A case study in Hangzhou, China - Zichen Zhao; Hai Yan; Huaizhen Zhu; Xinge Nan; Renwu Wu; Wenting Wang; Wei Yang; Lin Zhu; Jiangnan Shi; Fan Yang; Zhiyi Bao (Building and Environment, 2026)

Identification of virgin and recycled polypropylene based on FTIR spectroscopy combined with machine learning - Zi-Wen Dong; Xue-Chao Song; Qin-Bao Lin (Food Additives & Contaminants: Part A, 2026)

Implications of phase information from GPS and GRACE(FO) for identifying GPS stations influenced by poroelastic deformation - Fei Lin; Yu Sun; Natthachet Tangdamrongsub; Shuo Zheng; Bao Zhang (Journal of Geodesy, 2026)

Short-term and long-term effects of outdoor artificial light at night on reproductive hormones among infertile women from a preconception cohort study - Wenbin Fang; Cun Huang; Ying Tang; Mengdie Li; Yaning Sun; Yanlan Tang; Yinyin Chen; Yawen Cao; Jiqi Fang; Kunjing He; Jing Shen; Zhiyuan Huang; et al. (International Journal of Biometeorology, 2026)

Neuroprotective effect of sinomenine on parkinson’s disease through NLRP3/Caspase-1/GSDMD pathway-mediated pyroptosis inhibition - Xi Bao; JingCai Xu; Jia Zhou; Lin Huang; HaiChang Li; Yun Huang (Metabolic Brain Disease, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Mechanistic impacts of extra-long tunnel construction on eco-environmentally vulnerable zones: Coupled system dynamics and LSTM-Transformer modelling - Yan Yin; Weixing Bao; Hanqing Lu; Zhiming Huang; Xuhui Lin (Tunnelling and Underground Space Technology, 2026)

Assessment of provincial PV recycling potential: Integrating product lifetime distribution and scrap capacity - Bao-Jun Tang; Wen Shi; Ru Li; Xi-Lin Cao (Sustainable Production and Consumption, 2026)

Characterization of the mechanism of action of a re-engineered spider toxin acting on insect voltage-gated sodium channels - Felipe Andreazza; Wilson Valbon; Joseph Tourtois; Cadence Flohrschutz; Lucy Bell; Kyle Schneider; Lin Bao; Ke Dong (Pesticide Biochemistry and Physiology, 2026)

Neural network-based adaptive sliding mode fuzzy control for riser system with mass-related parametric perturbation - Yue-Ting Sun; Bao-Lin Zhang; Bo Yin (Ocean Engineering, 2026)

Sedimentary dynamics in the subaqueous delta of the abandoned estuary: Effects of strong wave activity and riverine re-supply - Chaoran Lin; Longhai Zhu; Yaping Wang; Rui Bao; Rijun Hu; Lingpeng Meng (Marine Geology, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Mechanisms driving anammox bacteria enrichment in constructed wetlands for self-purification of high-nitrogen polluted wastewater: Environmental gradients and microbial interactions - Lin Liu; Jie Li; Yu Xin; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Sciences, 2026)

Stream position matters in a least-disturbed catchment? Multifaceted biodiversity indices and community assembly of macroinvertebrates along watercourse - Huawei Bao; Zongwei Lin; Guohao Liu; Yixia Wang; Yaochun Wang; Jiuli Shi; Lishani Wijewardene; Naicheng Wu (Journal for Nature Conservation, 2026)

Corrigendum to “Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides” [Food Chem. 496(Part 2) (2025) 146787] - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Moisture-driven cracking triggers gully sidewall collapse: identifying critical thresholds in frozen Mollisols - Bao Liu; Yanru Wen; Litao Lin; Seyed Hamidreza Sadeghi; Tong Zhou; Xinhua Peng (CATENA, 2026)

Spatial variation of rainfall for landslide early warning: an examination from Majiajing watershed in Yunnan, China - Jing-Kun Bao; Kun Wang; Chuan-Bing Zhu; Ze Li; Ze-Min Xu; Yun-Fei Zhang; Lin Tian; Yang Yang; Jun-Yao Luo; Tai-Qiang Yang (Natural Hazards, 2026)

Soil bacteria predominantly drive ecosystem multifunctionality within disturbed meadows on the Tibetan Plateau - Long Huang; Dandan Wei; Weikai Bao; Bin Hu; Honghui Lin; Fanglan Li (Applied Soil Ecology, 2026)

Aptamer conformation sensing in nanopore for on-site quantitative detection of cadmium ions at nanomolar concentrations - Shujun He; Ronghui Liu; Xinxin Bao; Jiayuan Pang; Xi Zhang; Yue Liu; Wenfu Lin; Jiadun Liu; Tianxin Li; Yao Li; Yi Li; Xinrong Guo (Analytica Chimica Acta, 2026)

Assessing the impact of urban form on river-cooling dynamics: An empirical study in Hangzhou, China - Xinge Nan; Huaizhen Zhu; Ye Shu; Hai Yan; Ariane Middel; Wei Lin; Aoxiang Ning; Zhiyi Bao (Urban Climate, 2025)

Joint effects of predatory protists and predatory bacteria on driving the evolution of bacterial antibiotic resistance - Thi Bao-Anh Nguyen; Kenneth Dumack; Michael Bonkowski; Qing-Lin Chen; Tim Urich; Verena Groß; Ji-Zheng He; Hang-Wei Hu (Soil Biology and Biochemistry, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

LSD1 modulates ovarian reserve establishment by modifying FOXO3 and mitophagy-related genes - Shaogang Qin; Zijian Zhu; Tianhua Zhu; Yi Lin; Meina He; Ting Zhao; Meng Gao; Yibing Bao; Lin Lin; Jingwen Zhang; Longping Liu; Jianbin Wang; et al. (Science Bulletin, 2025)

Fuzzy disturbance observer-based sampled-data fuzzy recoil control with memory for deepwater drilling riser systems - Yan-Dong Zhao; Hai-Yang Yu; Zidong Ai; Yanlong Cao; Bao-Lin Zhang (Ocean Engineering, 2025)

Unraveling the mechanistic interplay of carbon cycle and nitrogen transport within deep reservoirs: A perspective of δ13CDIC analysis - Yufei Bao; Yuchun Wang; Qian Zhang; Xiaobo Liu; Peng Hu; Meng Sun; Xiaodong Qu; Jie Wen; Shanze Li; Bing Lin; Jialong Huang (Journal of Hydrology, 2025)

Linking nature-based hydrodynamic redesign to ecological feedback in urban channelized rivers: A 3D modeling-metagenomic integration framework - Yu Xin; Lin Liu; Xin Ye; Shao-Hua Chen; Yu-Ming Zheng; Quan-Bao Zhao (Journal of Hydrology, 2025)

Surrogate model of flooding loss to alleviate computational burden in reservoirs operation - Yifan Bao; Pan Liu; Fanqi Lin; Xu Cheng; Yuzhu Li; Xiaojing Zhang (Journal of Hydrology, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Enhancing heavy metal immobilization in cropping systems via modified clay minerals: A machine learning- assisted meta-analysis - Wenwen Zhang; Pengjie Zhao; Tianda Pu; Wanjia Bao; Hantong Qie; Xiao Tan; Meng Ren; Aijun Lin (Journal of Environmental Chemical Engineering, 2025)

The inhibitory mechanisms of plasma-activated water on biofilm formation of Pseudomonas fluorescens by disrupting quorum sensing - Yi-Ming Zhao; Lin Zhang; Yulong Bao; Yiting Guo; Haile Ma; Ronghai He; Paula Bourke; Da-Wen Sun (Food Research International, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

A systematic analysis of the sensory qualities of Asparagus cochinchinensis (lour.) Merr. From the four major production areas in China: Sensory characteristics, key flavor substances, and molecular mechanisms of flavor formation - Jingping Zhong; Shuyu Deng; Mengqi Li; Honglin Yin; Xinming Chen; Zhiyan Deng; Xiaoming Bao; Qingchu Tan; Junzhi Lin; Dingkun Zhang; Gang Shen; Li Han; et al. (Food Chemistry, 2025)

Dietary prebiotics combined with iron supplementation: A two-pronged approach to reduce rice cadmium bioavailability - Rong-Yue Xue; Yao-Sheng Zhang; Jin-Feng Xi; Lei Zhou; Xin-Ying Lin; Tian-Wen Ye; Yu-Hang Bao; Dongmei Zhou; Hong-Bo Li (Food and Chemical Toxicology, 2025)

Enhancing urban thermal resilience in multi-mountainous cities through optimized 3D block morphology: a machine learning framework - Xun Lin; Zhitai Wang; Yu Bao; Xintong Chen (Energy and Buildings, 2025)

Multifunctional carbon dots@PVA films with excellent antibacterial, antioxidant and full-band UV resistance properties for fruit preservation - Bao-Juan Wang; Xin-Lin Jia; Hao-Wen Sun; Zhao-Fan Wu; Xiao-Xiao Luo; Yuan-Qing Mao; Huan-Ming Xiong (Chemical Engineering Journal, 2025)

Multi-side-port nanotube array based on pillar[5]arene-Ag(I) self-assembly for efficient and recyclable separation of trace pyridine - Hao-Ran Yang; Jintao Tian; Xing Han; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Nanoconfined enzymatic cascade strategy for highly efficient synthesis of D-allulose - Kan Zhan; Anni Bao; Suhai Zhang; Liang Chen; Yichen Wan; Keke Hou; Jian Hao; Lin Chaoping; Zhiyong Sun; Renchao Zheng; Yuguo Zheng (Chemical Engineering Journal, 2025)

Machine learning coupling microbial succession to decipher gas stripping-reinforced sulfate reduction for hydrogen sulfide removal - Ting-Ting Zhang; Ei Myat Mon Oo; Bi-Long Chen; Lin Liu; Quan-Bao Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Bioresource Technology, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

A relative-independent haplotype derivation method applied for noninvasive prenatal testing for chromosomal rearrangements in a pregnant carrier - Mengyang Du; Xi Yang; Ruixiu Zhang; Na Yu; Liying Peng; Jiawen Lin; Xue Yan; Yiming Wu; Shihua Bao (Molecular Genetics and Genomics, 2025)

Nano-sized heterogeneous photocatalyst Fe3O4@V/TiO2-catalyzed synthesis and antimycobacterial evaluation of 2-substituted benzimidazoles - Lijian Bao; Xiaodong Chen; Yanli Li; Guangyuan Zhu; Jingjun Wang; Mingyue Chen; Xingyu Bian; Qiang Gu; Yumin Zhang; Feng Lin (Molecular Diversity, 2025)

A comprehensive study on coastline mapping and sustainable management of coastal resources in China: Connotation, methodologies, and practical applications - Weiwei Dong; Guilan Lin; Yongling Zheng; Huiquan Lu; Chengqiang Wu; Jingjing Bao (Journal of Coastal Conservation, 2025)

The mechanism of p38 MAPK, NF-κB, and IL-6 in T-2 toxin and/or selenium deficiency induced spleen injury - Xiang Xiao; Rongqi Xiang; Jiaxin Liu; Ziwei Guo; Haobiao Liu; Xue lin; Miaoye Bao; Viscardi Angelo; Jing Han (Immunologic Research, 2025)

Functional Analysis of the mstn1 Gene and Its Transcriptional Regulation by Mef2 Factors in Yellowfin Seabream, Acanthopagrus latus (Hottuyn, 1782) - Hong-Xi He; Ke-Cheng Zhu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Lin Xian; Teng-Fei Zhu; Dian-Chang Zhang; Min Yang (Fish Physiology and Biochemistry, 2025)

Activation of the cGAS-STING pathway in monocytes exacerbates pulmonary fibrosis induced by paraquat poisoning - Yangyang Sun; Zheming Yuan; Weidong Li; Xueyang Lin; Chen Yang; Yufeng Yang; Hui Miao; Shengran Wang; Ziqi Cui; Zhenghao Bao; Simin Lang; Weiqiang Sun; et al. (Toxicology and Applied Pharmacology, 2025)

Biocontrol potential and antifungal mechanism of a novel Bacillus velezensis NH-13–5 against Botrytis cinerea causing postharvest gray mold in table grapes - Lin Xiao; Jin-Tian Wang; Dong-Fang Cao; Hong Li; Hong-Yu Fang; Tian-Li Qu; Bao-Hua Zhang; Shuai-Shuai Li; Feng-Yu Du (Postharvest Biology and Technology, 2025)

Two-stage energy efficiency optimization of ship speed and trim considering varying sea conditions and optimization frequency - Xinyue Zhang; Ping Yang; Diju Gao; Chunteng Bao; Lin Ma (Ocean Engineering, 2025)

Investigation of dietary supplementation with Tricholoma matsutake on immunoregulation: The underlying direct mechanism - Renzhi Lv; Yifei Wang; Qunyan Fan; Zhijie Bao; Songyi Lin (Food Bioscience, 2025)

GC-IMS and chemometrics identify critical flavor control points in egg yolk powder processing - Jiahui Song; Yaru Li; Fujun Guo; Songyi Lin; Zhijie Bao (Food Control, 2025)

Characterization of CD8+ T Cells in large yellow croaker Larimichthys crocea and their dynamics in response to Cryptocaryon irritans infection - Guolong lai; Xinran Li; Sichang Liu; Luyang Zhao; Mengtian Xie; Li Huang; Wenxuan Zhang; Wenbing Bao; Yan Lin; Xinhua Chen; Yang Ding (Fish & Shellfish Immunology, 2025)

Humid heat’s nonlinear impact on school-age children’ sleep health: Evidence from Guangdong, China - Yuan Gao; Li-Zi Lin; Wen-Wen Bao; Wan-Ting He; Yun-Ting Zhang; Guang-Hui Dong; Shenjing He (Environmental Research, 2025)

Novel fused-bimacrocycles supply stepwise and orthogonal assembly, versatile way to construct multi-functional materials - Ting-Ting Huang; Xin-Yu Dai; Juan Liu; Tai-Bao Wei; Hong Yao; Bingbing Shi; Jin-Fa Chen; Qi Lin (Chemical Engineering Journal, 2025)

Preparation of antibacterial CO2-based polycarbonate hydrogels with dual cross-linkages for co-loading of antibiotics and hypoglycemic agents and their applications on diabetic wound dressings - Zheng-Ian Lin; Tzu-Hsien Tsai; Guan-Lin Liu; Chih-Yuan Hsu; Siang-Ming Tsai; Yi-Ping Fang; Wing-Cheung Law; Han-Lin Tsai; Jia-Ying Tsai; Hsuan-Ying Chen; Bao-Tsan Ko; Pei-Wen Cheng; et al. (Chemical Engineering Journal, 2025)

Heparin-loaded silk fibroin microparticles/bacterial nanocellulose (Hep@SFMPs/BNC) conduits for application as small-caliber artificial blood vessels - Geli Li; Luhan Bao; Lin Chen; Xingping Zhou; Feng F. Hong (Carbohydrate Polymers, 2025)

Genotypic diversity and genome-wide association study of phosphorus content, amylose content, pasting, and textural properties of potato starch - Daraz Ahmad; Lin Zhang; Yan Gao; Yaqi Hu; Bowen Deng; Chuan Tong; Jinsong Bao (Carbohydrate Polymers, 2025)

Do healthier trees cool better? Assessing the impact of street tree health on urban thermal regulation and pedestrian comfort - Wenting Wang; Min Wu; Hai Yan; Yijuan Sang; Renwu Wu; Wei Yang; Zichen Zhao; Xinge Nan; Lin Zhu; Zhiyi Bao (Building and Environment, 2025)

CO2 dispersion modelling and disaster evaluation at Changbaishan volcano, NE China - Lin Wang; Feixiang Wei; Baoxiao Bao; Wenya Xi (International Journal of Earth Sciences, 2025)

A dansyl-quinolinium-based ratiometric fluorescent probe for detecting HSO3-/SO32- in living cells - Feng-Ting Liu; Xian-Fang Liu; Zhi Jin; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2025)

Estimating the Mediterranean sea-level trends from 1993 to 2022 showing the consistency of X-TRACK-L2P coastal altimetry with tide gauge data and trend impacts on Egypt's northern coast - Mohamed M. Youssef; Qianqian Li; Ahmed Zaki; Lin Wu; Lifeng Bao (Frontiers in Marine Science, 2025)
In recent decades, sea level has risen markedly along Mediterranean coastlines, highlighting the growing impacts on vulnerable coastal regions. This study analyzed sea-level variability using tide gauge (TG) records from 45 stations, coastal altimetry data (X-TRACK-L2P and X-TRACK/ALES), and virtual altimetry station (VAS) data. Based on TG records from 1993 to 2022, the results reveal positive linear trends, with 11 stations recording rates well above the global mean. The highest rate, 5.281 mm/year, was observed at TARANTO (Station ID: 2095). Strong consistency was also found between TG and X-TRACK-L2P coastal data, with X-TRACK-L2P trends ranging from −3 to 6 mm/year. In addition, sea-level rise in the Adriatic, Aegean, and Levantine sub-basins exceeded the current global mean. The agreement between TG and X-TRACK/ALES data was more limited, observed at only two sites located about 7 km and 20 km apart from the first valid point on the altimetry track, respectively. Furthermore, the findings highlight the diverse impacts of sea-level rise on Egypt's northern coast, where densely populated areas, productive agricultural lands, and cultural heritage sites are particularly at risk. In conclusion, all types of data used indicate positive linear trends in the Mediterranean Sea. In addition, several sites have rates of sea-level trend that exceed the global mean, underscoring the urgent need for proactive adaptation measures.

Megastigmane glycosides from the leaves of Nicotiana tabacum and their neuroprotective activities - Jun-zhang Wu; Jun-ping Gu; Bao-min Lin; Duo-bin Mao; Hong Tao (Natural Product Research, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

Multi-level Priors-Guided Diffusion-based Remote Sensing Image Super-Resolution - Lijing Lu; Zhou Huang; Yi Bao; Lin Wan; Zhihang Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Deciphering the mechanism underlying allergenicity reduction in egg white powder by pulsed electric field treatment - Luyue Huang; Shiyi Zhao; Xinqing Lu; Zhijie Bao; Songyi Lin (Food Bioscience, 2025)

Phenotypic and functional characterization of CD4-2+ T cells in large yellow croaker Larimichthys crocea - Xinran Li; Guolong Lai; Yan Lin; Sichang Liu; Wenbing Bao; Wenxuan Zhang; Li Huang; Guangming Shao; Shihao Chen; Yang Ding; Xinhua Chen (Fish & Shellfish Immunology, 2025)

Efficient recovery of lithium from the reverse osmosis concentrate of shale gas wastewater treatment: Adsorption performance and mechanism of Al-doped manganese-based adsorbent particles prepared via hydrophilic modification - Xin Li; Xifan Li; Quanxun Liang; Guijing Chen; Wenjie Wang; Jin Bao; Jiawang Qin; Shun Tang; Xiao Lin; Alberto Tiraferri; Baicang Liu (Desalination, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Development of a multifunctional and biocompatible hydrogel for flexible implantable sensors - Kaiqi Zhang; Huibiao You; Yuxi Liu; Fulei Lin; Yanan Li; Lina Jia; Jinxiao Bao; Xin Ge; Gaofei Pan; Huitao Yu; Ruiguang Xing (Chemical Engineering Journal, 2025)

Machine learning-assisted dual-mode hydrogel sensor for the detection of nitrite - Si-Qi Yang; Bao-Zhu Jia; Jie Liu; Fan-Xuan Gong; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Anthropogenic land-use driven changes in soil stoichiometry reduce microbial carbon use efficiency - Xinle Tong; Lichao Fan; Mingda Wang; Jingjing Guo; Lei Bao; Lingzhi Hui; Yichao Chen; Zhengrong Li; Shuai Qian; Xiaodong Xu; Lin Ma; Xiangtian Meng; et al. (Agriculture, Ecosystems & Environment, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

A new approach to inferring the threshold range for quality control of ocean T/S profiles based on probability distribution of historical data - Lin Conghao; Wang Huizan; Bao Senliang; Liu Zenghong; Yan Hengqian; An Yuzhu (Acta Oceanologica Sinica, 2025)

YOLO-LDFI: A Lightweight Deformable Feature-Integrated Detector for SAR Ship Detection - Wendong Bao; Shuoying Chen; Jiansen Zhao; Xinyue Lin (Journal of Marine Science and Engineering, 2025)
A lightweight enhanced detection model named YOLO-LDFI is proposed in this study for ship target detection in SAR images, aiming to improve detection accuracy and deployment efficiency under complex maritime environments. Based on YOLOv11n, the model incorporates four architectural improvements in a progressive manner: linear deformable convolution (LDConv), deformable context-aware attention mechanism (DCAM), frequency-adaptive dilated convolution detection head (FAHead), and Inner-EIoU. Experiments conducted on the public SAR ship detection dataset HRSID demonstrate that the proposed model achieves an AP50 of 90.7% and an F1 score of 87.0%, with only 2.63 M parameters and a computational complexity of 6.7 GFLOPs. Ablation experiments validate the contribution of each component to improved feature alignment, reduced background interference, and more accurate target localization. Overall, the results indicate that the proposed model offers a reasonable trade-off between detection performance and computational efficiency in SAR ship detection tasks.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Occurrence, removal and ecological risk assessment of antibiotics in rural domestic wastewater treatment systems in the Beijing-Tianjin-Hebei region - Hongliang Wang; Sai Zhang; Ziyu Lin; Feifei Xiao; Bao Xiang; Ao Li (Journal of Hazardous Materials, 2025)

Sustainable aviation fuel and next-generation aircraft: Low-carbon pathway for China's civil aviation industry - Rui Yan; Bao-Jun Tang; Yu-Jie Hu; Chang-Jing Ji; Kun-Ben Lin; Meng Shen (Journal of Environmental Management, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

Rationally designed and facilely constructed CoFe2O4@SiO2 yolk@shell heterostructure spherical jars as interlayer achieve high-performance Li S batteries via “3 + 1” modal anchoring & catalyzing coupled with microreactor - Yingying Bao; Bin Yue; Lin Li; Shan Jiang; Hong Shao; Yunrui Xie; Qianli Ma; Wensheng Yu; Jinxian Wang; Xiangting Dong (Chemical Engineering Journal, 2025)

The Adhesion Characteristics of Fouling Organism on Two Kinds of Mesh Coat - Lei Li; Jinmeng Bao; Dagui Liao; Yanan Wei; Cong Yan; Xiaoxu Fan; Shen Lin; Dan Liu; Wei Tian; Yanming Sui; Mei Jiang (Thalassas: An International Journal of Marine Sciences, 2025)

Global distribution pattern in characteristics of gross primary productivity response to soil water availability - Shanning Bao; Nuno Carvalhais; Jian Xu; Jing M. Chen; Yang Lei; Gegen Tana; Changgui Lin; Jiancheng Shi (Agricultural and Forest Meteorology, 2025)

Transcriptomic and Metabolomic Analyses Provide Insights into Cryptocaryon irritans Resistance in Golden Pompano (Trachinotus ovatus) - Bo Liu; Bao-Suo Liu; Jing-Wen Yang; Hua-Yang Guo; Nan Zhang; Teng-Fei Zhu; Lin Xian; Ke-Cheng Zhu; Dian-Chang Zhang (Fishes, 2025)
Golden pompano (Trachinotus ovatus) is an economically important fish species along China’s southern coast. However, infections by Cryptocaryon irritans severely constrain the healthy and sustainable development of the aquaculture industry. To investigate the genetic basis of resistance to this parasite in golden pompano, this study employed transcriptomic and metabolomic analyses to compare differences between susceptible (ES) and resistant (RS) groups following C. irritans challenge. Transcriptome analysis identified 2031 differentially expressed genes (DEGs) between EST and RST groups, comprising 1004 up-regulated and 1027 down-regulated genes. Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment revealed that these DEGs were primarily enriched in lipid metabolism and amino acid metabolism pathways. Untargeted metabolomics detected 461 significantly differentially abundant metabolites (295 up-regulated, 166 down-regulated), confirming pronounced metabolic differences between ES and RS groups, particularly in lipid and amino acid metabolism. Further, KEGG enrichment highlighted steroid hormone biosynthesis, α-linolenic acid metabolism, and arachidonic acid metabolism as the most significantly altered pathways upon infection. This integrated transcriptomic and metabolomic study reveals substantial differences in gene expression and metabolite profiles between susceptible and resistant golden pompano in response to C. irritans. These changes predominantly involve lipid metabolism and amino acid metabolism, suggesting that these processes are critical in determining host resistance/susceptibility.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Unraveling the mysterious jujube-like aroma in Pu-erh tea: Decoding the material basis for distinctive aroma formation - Guohe Chen; Wanling Xiao; Zhichao Lin; Mengzhen Xia; Yajie Xue; Jing Zhang; Sudu Bao; Junye Zhu; He Xie; Jianan Huang; Zhonghua Liu; Chao Wang (Food Research International, 2025)

Prussian blue anchored Fe(Ⅲ)-Tannic acid composite-mediated colorimetric and photothermal dual-mode immunosensor for the detection of tetrodotoxin - Sayed Haidar Abbas Raza; Bao-Zhu Jia; Jing-Min Li; Qin-Chun Yin; Wu-Yi Zhou; Sameer D. Pant; Hongtao Lei; Zhen-Lin Xu; Lin Luo (Food Control, 2025)

Interface molecular reconstruction with scarcity active factor for long-life aqueous zinc batteries at thermal environment - Xin Chen; Yin Yang; Runzhi Liang; Junjie Zheng; Jia Yao; Jingying Li; Yi Gan; Xin Liu; Xiaodong Liang; Ze Wang; Qin Liu; Lin Lv; et al. (Chemical Engineering Journal, 2025)

Spatial confinement-enabled full-color emission from carbon dots via controlled sp2 domain assembly in spray pyrolysis - Lin Lan; Zhenfeng Gan; Yuan Ma; Rui Bao; Xin Kong; Liang Liu; Jianhong Yi (Chemical Engineering Journal, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Effects of Physical Exercise on High-Fat Diet–Induced Hypothalamic Inflammation: Systematic Review - Yu Xue Sun; Jia Bao Guo; Bing Lin Chen (Molecular Neurobiology, 2025)

Associations of Metal Mixtures with Lipid Profiles: Exploring the Mediating Role of Testosterone in a Cross-Sectional Study - Sencai Lin; Ying Yang; Junxiu He; Sihan Hu; Yu Bao; Xiaoting Ge; Xiaobo Yang (Biological Trace Element Research, 2025)

RETRACTED: Investigating the causes of yolk mudding during storage of salted eggs: Water migration accelerates protein and lipid oxidation - Jiyu Zhang; Songyi Lin; Sichen Lu; Xunze Yuan; Yue Tang; Zhijie Bao (Food Chemistry, 2025)

Dynamic changes of volatile compounds during the processing of egg white powder based on GC-IMS investigation - Aini Sun; Yaru Li; Fujun Guo; Songyi Lin; Zhijie Bao (Food Chemistry, 2025)

GC-IMS combined with multivariate statistical analysis: An efficient strategy for characterizing flavor components and assessing storage stability of egg yolk powder - Jiahui Song; Shuyun Chen; Songyi Lin; Fujun Guo; Zhijie Bao (Food Chemistry, 2025)

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

Exploring food-derived bioactive peptides: Efficacy, mechanisms, and clinical implications in ferroptosis regulation - Chenzhe Gao; Lin Zhang; Jiahui Ma; Haiyan Zhang; Yue Pang; Chenyu Xue; Dehai Li; Xiaoyu Zhao; Munkh-Amgalan Gantumur; Mizhou Hui; Weichen Hong; Yihong Bao; et al. (Trends in Food Science & Technology, 2025)

Potential viral influence on sulfur metabolism in acid sulfate soils - Li Bi; Shuai Du; Rob Fitzpatrick; Qing-Lin Chen; Thi Bao-Anh Nguyen; Zi-Yang He; Ji-Zheng He; Hang-Wei Hu (Soil Biology and Biochemistry, 2025)

Characterisation of greenhouse gas emissions from temporary wastewater treatment plants under different operation modes - Yan Yin; Weixing Bao; Bowen Che; Hanqing Lu; Xuhui Lin (Process Safety and Environmental Protection, 2025)

Disturbance observer-based composite recoil controller design for deepwater drilling riser systems after emergency disconnection - Hai-Yang Yu; Yan-Dong Zhao; Bao-Lin Zhang; Yanbin Wang; Yan-Long Cao (Ocean Engineering, 2025)

Investigation of the efficacy of fish scale collagen peptide on wound healing through various administration routes - Siqi Shen; Songyi Lin; Deyou Gao; Jianlan Hu; Zhijie Bao (Food Bioscience, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

A machine learning network for FY-3A MERSI NIR PWV retrieval under all-weather conditions - Yunzheng Huang; Bao Zhang; Xiongwei Ma; Wanqiang Yao; Qi Zhang; Yibin Yao; Xiaohu Lin; Qingzhi Zhao; Chaoqian Xu (Atmospheric Research, 2025)

Integrative analysis based on CRISPR screen identifies apilimod as a potential therapeutic agent for cisplatin-induced acute kidney injury treatment - Yunpeng Chu; Muyun Wei; Zhongyu Cao; Luan Chen; Jie Tan; Wei Bao; Fan Yang; Yingtian Zhang; Yunxiao Lin; Yutong Zhang; Shiyi Li; Cai Lv; et al. (Science China Life Sciences, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Topping-induced transcriptome changes reveal PaSPL-mediated regulation of plant architecture in Platanus acerifolia - Yanping Zhang; Yali Guan; Yongkang Lu; Lin Wang; Yuqing Chen; Manzhu Bao (Plant Molecular Biology, 2025)

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

Dolomites in a carbonate-evaporite system: the fifth member of the Middle Ordovician Majiagou Formation, Eastern Ordos Basin, China - Siyi Fu; Chenggong Zhang; Hao Liu; Liubin Wei; Hongping Bao; Xingchao Ye; Zhongtang Su; Hongde Chen; Liangbiao Lin (Frontiers in Marine Science, 2025)
Introduction The carbonate-evaporite system contains substantial hydrocarbon resources and serves as an excellent subject for studying dolomitization problem. In the Ordos Basin, the fifth member of the Ordovician Majiagou Formation have extensive carbonate-evaporite deposits. Methods This study utilizes extensive drilling data, thin section microscopic examination, scanning electron microscopy, and a variety of geochemical analyses to investigate the origins of evaporites and the genesis of dolomites within this formation. Results Our findings indicate that the fifth member of the Majiagou Formation primarily contains two types of evaporites (halite and anhydrite) and five types of dolomites: micritic (Dol-1), fine-crystalline fabric-obliterative dolomite (Dol-2), fabric-retentive dolomite (Dol-3), microbial mats-associated dolomite (Dol-4), and medium–coarse crystalline dolomite (Dol-5). The evaporites, originating from seawater (sulfur isotope compositions ranging from 23.0 to 27.9 ‰), exhibit a planar distribution controlled by paleotopography and evaporation intensity, with distinct deposition centers for gypsum and halite. The eastern part of the study area is dominated by halite deposits, while both gypsum and halite are developed in the central region, and the western part is primarily characterized by gypsum deposition. LA-ICP-MS data indicate varying concentrations of MgCO3 (34.4-44.3 wt%) and CaCO3 (45.4-58.9 wt%), as well as trace elements including Na, Al, Si, K, Cu, Ba, Mn, and Fe. REE patterns and δCe/δEu anomalies provide insights into dolomitization mechanisms. Discussion The formation of dolomites occurred in distinct stages. The first stage, from the penecontemporaneous to shallow burial periods, the formation of Dol-1, Dol-2, and Dol-3 through seepage-reflux dolomitization and evaporative pumping. Dol-4 also formed during this stage, closely associated with microbial dolomitization and influenced by tidal transport. The second stage, during deep burial, resulted in Dol-5, which can be further categorized into Dol-5-1, formed by continued dolomitization from pore fluids, and Dol-5-2, formed through hydrothermal processes. The intensity of dolomitization is closely linked to the distribution of evaporites. Carbonates underlying gypsum strata exhibit a higher degree of dolomitization compared to those beneath halite strata. This is due to gypsum absorbing Ca 2+ and releasing high-salinity brine during its transformation to anhydrite, thereby increasing the Mg 2+ /Ca 2+ ratio in formation fluids. Consequently, the hydrocarbon resource potential of carbonate strata beneath gypsum layers is likely higher than that of those beneath halite layers.

Comprehensive analysis of microplastics at typical outlets around Hainan Island: From spatial distribution to flux estimation and correlation analysis - Shiyu Xie; Yuanyuan Su; Dan Qi; Fei Liu; Liu Gao; Ruiqi Bao; Xing Cheng; Xubing Lin; Tingting Zhang; Licheng Peng (Water Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Reinforcement learning-based backstepping sliding mode heading control for unmanned sailboats - Chen-Ming Li; Bao-Lin Zhang; Yan-Long Cao; Bo Yin (Ocean Engineering, 2025)

Sampled-data fuzzy modeling and control for offshore structures subject to parametric perturbations and wave loads - Zhihui Cai; Bao-Lin Zhang; Qing-Long Han; Xian-Ming Zhang; Jigang Zhang; Ouguan Xu (Ocean Engineering, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Henry; et al. (Molecular Plant, 2025)

RAPID LEAF FALLING 1 facilitates chemical defoliation and mechanical harvesting in cotton - Bing Zhang; Dandan Yue; Bei Han; Danfan Bao; Xiao Zhang; Xuyang Hao; Xin Lin; Keith Lindsey; Longfu Zhu; Shuangxia Jin; Maojun Wang; Haijiang Xu; et al. (Molecular Plant, 2025)

Metabolic profiling and evaluation of antioxidant and anti-inflammatory properties of Apis cerana cerana Honey from Sansha City, Hainan Province, China - Jiao Wu; Xiang-Tan Xu; Cheng Xing; Xin-Bao Hao; Xing-Yue Fang; Zhi-Hao Xie; Shan Zhao; Jing-Lin Gao; Lu Xu; Shi-Jie Wang (Food Chemistry, 2025)

Enhancement of Oryzanol application by constructing modified β-CD inclusion complex and polycaprolactone-chitosan electrospun fiber membranes: Perspectives on wound dressings and grape preservation - Wen Li; Jintao He; Qijue Chen; Feng Bao; Yinqiang Huo; Jing Deng; Qinlu Lin; Feijun Luo (Food Chemistry, 2025)

Formaldehyde oxidation reaction enhanced by interface engineering of Cu/Cu2O/Co(OH)2 composite electrocatalyst for bipolar hydrogen production - Zi Qiang Ma; Chang Bao Han; Wen Kang Zhao; De Cai Fang; Yi Lin Zhao; Chang Xin Liu; Xinxin Wang; Ling Sun; Xue Mei Song (Chemical Engineering Journal, 2025)

Reduced mixed Ni-Co-Al metal oxide catalysts with rich oxygen vacancy derived from layered double hydrotalcite for selective hydrogenation of furfuryl alcohol to 1,5-Pentanediol - Nan Xi; Qiwang Li; Yi Chen; Ruixi Bao; Qinglian Wang; Yixiong Lin; Jun Yue; Rong Wang; Chen Yang; Wang Yin; Ting Qiu (Chemical Engineering Journal, 2025)

Gibberellin induces rapid regeneration of juveniles from the Sargassum fusiforme holdfasts - Lin Luo; Dongya Bao; Congquan Gao; Xingda Sheng; Peng Jin; Xu Gao; Zengling Ma; Binbin Chen; Mingjiang Wu (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Using end-member model algorithm to infer sedimentary processes from mangrove sediment grain-size in Guangdong, South China - Zhanyi Lin; Qiuchi Wan; Fan Zhang; Jing Zhong; Zhongle Zhou; Kunshan Bao (Regional Studies in Marine Science, 2025)

Recoil control of nonlinear drilling riser systems via integral sliding mode schemes - Bao-Lin Zhang; Shou-Xiang Yan; Xian-Ming Zhang; Yanlong Cao; Xiuquan Liu (Ocean Engineering, 2025)

T-2 toxin induces cardiac fibrosis by causing metabolic disorders and up-regulating Sirt3/FoxO3α/MnSOD signaling pathway-mediated oxidative stress - Lichun Qiao; Xue Lin; Haobiao Liu; Rongqi Xiang; Jingming Zhan; Feidan Deng; Miaoye Bao; Huifang He; Xinyue Wen; Huan Deng; Xining Wang; Yujie He; et al. (Journal of Environmental Sciences, 2025)

Identification of Dendrobium officinale species and authentication of commercial products by DNA barcoding and high-resolution melting analysis - Zhilong He; Zhao Yang; Cui Dong; Shanshan Yan; Jing Lin; Hexigeduleng Bao; Fan Tang; Leilei Zhang; Cheng Zhu; Yan Hu; Yanfei Ding (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

A data-driven model for assessing the direct coal liquefaction performance and influencing factors - Lin-Sheng Li; Hao-Wei Li; Gai-Xia Shi; Xing-Bao Wang; Yimeng Zhu; Wen-Ying Li (Fuel, 2025)

Small intestine-residing probiotics suppress neurotoxic bile acid production via extracellular vesicle-mediated inhibition of Clostridium scindens - Wei-Leng Chin; Bao-Hong Lee; Qiao-Yu Hsu; Chih-Yao Hou; Ming-Chyi Pai; Chi-Wei Lin; Wei-Hsuan Hsu (Food Research International, 2025)

Preferred crystal plane growth orientation induced by low-energy ions for highly reversible zinc anodes - Guanzhong Wang; Xiyan Bao; Xiaofang Wang; Xize Chen; Wei Lai; Di Wu; Chen Zhang; Lin Gao; Minglei Cao; Xingxing Li; Qin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

The effect of interfering ions on the degradation of organic pollutants by two types of activated persulfates over Fe-based catalysts in water: A meta-analysis - Pengjie Zhao; Hantong Qie; Xuedan Cui; Wenwen Zhang; Tianda Pu; Wanjia Bao; Xiaolu Li; Aijun Lin; Meng Ren (Chemical Engineering Journal, 2025)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Di-Wei Ma; Khalid Hassan Mohamed; Jian-Lin Hu; Chang-Qin Yin; Yu-Bin Wei; Xiao-Pan Chai; Qing-Bao Zhang; Lan-Chun Zhang; Jia Liu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Screening of Regulatory mRNAs and miRNAs that Suppress Staphylococcus aureus Proliferation via Macrophage Ferroptosis - Lili Wang; Jiajia Bao; Danyang Yang; Sijia Gao; Xintong He; Dan He; Lin Liu; Yulian Xu; Qinya Yang; Sifei He; Lei Xu; Anlong Li (Current Microbiology, 2025)

Association of Blood Metals and Metal Mixtures with the Myocardial Enzyme Profile: An Occupational Population-Based Study in China - Xiaoting Ge; Junxiu He; Yuan Zheng; Qiuyue Wang; Hong Cheng; Yu Bao; Sencai Lin; Xiaobo Yang (Biological Trace Element Research, 2025)

Gut microbiome composition likely affects the growth of Trachinotus ovatus by influencing the host's metabolism - Chen-Xu Wu; Bao-Suo Liu; Hua-Yang Guo; Teng-Fei Zhu; Lin Xian; Nan Zhang; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture International, 2025)

The bio-decolorization of methyl orange by S.putrefaciens CN32 and responding mechanism to salinity stress based on transcriptomic analysis - Bai-Hang Zhao; Bing-Lin Zhang; Bao-Yu Zhang; Rui-Xuan Liu; Xu-Ming Liu (Water Research, 2025)

Experimental study on the effect of different sealing ratios on the behavior of continuous spill fires in sloped tunnels - Weibing Jiao; Changkun Chen; Wuhao Du; Zida Lin; Yipeng Bao; Shishan Liu (Tunnelling and Underground Space Technology, 2025)

Long-term variation of O3 in the Yangtze River Delta and its influencing factors from a regional perspective - Qiuyue Bao; Weili Lin; Junli Jin; Xiaobin Xu; Gang Zhao; Xiaoyi Zhang; Qianli Ma (Urban Climate, 2025)

Strychni Semen and two alkaloidal components cause apoptosis in HK-2 cells through TRADD-MAPK/NF-κB pathway - Wenyi Tian; Yuling Li; Fengzhi Liu; Hui Liu; Chen Li; Lin Bao; Xiaodong Liang (Toxicon, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Experimental and theoretical study on the in-situ thermal tensile strength and gasification kinetics of iron coke: Dual-activation mechanism of iron-catalyzed gasification - Jie Wang; Wei Wang; Xuheng Chen; Junfang Bao; Ruilin Lin; Runsheng Xu (Fuel, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Integration of UV-vis spectroscopy and machine learning for identification of recycled polyethylene terephthalate - Yan-Ling Xie; Qi-Zhi Su; Qin-Bao Lin; Huai-Ning Zhong; Dan Li; Ben Dong (Food Packaging and Shelf Life, 2025)

Experimental investigation on swelling and gas breakthrough properties of GMZ bentonite considering alkaline solution effects - Lin-Yong Cui; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Bao Chen; Yu-Jun Cui (Engineering Geology, 2025)

Dimerized small-molecule acceptors with electron withdrawing linker for efficient organic solar cells - Jianan Niu; Mingxin Sun; Fuzhen Bi; Guoqing Lin; Shuguang Wen; Cheng Sun; Mingliang Sun; Xichang Bao (Chemical Engineering Journal, 2025)

Study on the performance of electric double-layer capacitors based on lignocellulose gel polymer electrolytes with different pH values for Zn2+-lignocellulose coordination mechanism - Yanzhou Wang; Yun Huang; Xu Wang; Jin Bao; Chao Zou; Xichang Wang; Yunhe Zhang; Changjian Zhang; Zhongwei Zhao; Xing Li; Mingshan Wang; Yuanhua Lin; et al. (Chemical Engineering Journal, 2025)

Role of Exercise on Neuropathic Pain in Preclinical Models: Perspectives for Neuroglia - Chen-Chen Zhu; Yi-Li Zheng; Chan Gong; Bing-Lin Chen; Jia-Bao Guo (Molecular Neurobiology, 2025)

A new Eötvös correction algorithm for marine shipborne gravity survey with irregular nonlinear track - Shi Liu; Lin Wu; Menghan Xi; Guocheng Mao; Lifeng Bao; Yong Wang (Acta Geophysica, 2025)

Preliminary Investigation of the Spatial-Temporal Characteristics and Vertical Dynamics of Internal Solitary Waves in the South China Sea from SWOT Data - Zhikuan Pan; Zhenhe Zhai; Qi Li; Qianqian Li; Lin Wu; Lifeng Bao (Journal of Marine Science and Engineering, 2025)
Internal waves are crucial for understanding oceanographic parameters such as spatiotemporal distribution and energy transfer. They significantly impact ocean circulation, marine ecosystems, and offshore operations. However, studying internal waves is challenging due to their dynamic nature and the need for effective observation methods. This study investigated nonlinear internal solitary waves (ISWs) in the South China Sea using SSHa data from the SWOT satellite mission (Cycles 2 to 20). The distribution patterns and seasonal variations in ISWs were analyzed, revealing that ISWs are more frequently observed in summer while being rarely detected in winter. By combining SSHa observations with a Mode-1 vertical structure model, the isopycnal displacement, velocity fields, and energy characteristics of ISWs were reconstructed. The results show a maximum isopycnal displacement of 160 m at 400 m depth and peak kinetic energy near the surface (~2000 J/m3) and potential energy at a depth of around 300 m (~9000 J/m3). These findings highlight the vertical variability of ISWs and demonstrate the capability of SWOT data in capturing their fine-scale evolution, providing new opportunities for oceanic research and enhancing our understanding of internal waves’ impact on marine environments and ocean circulation.

Identification of growth-related genes based on BSA in Pacific white shrimp Litopenaeus vannamei - Zhenning Bao; Yang Yu; Pengfei Lin; Fuhua Li (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Herry; et al. (Molecular Plant, 2025)

Comprehensive interpretation of hillslope subsurface flow – An analytical approach to hillslopes with complex geometry - Bao-Ming Jin; Xin Yang; Kwan Tun Lee; Pin-Chun Huang; Peng Lin; Lanlan Gao; Lo-Ya Chen (Journal of Hydrology, 2025)

Advancements in the development of porous nanomaterials for CO2 capture of deep decarbonization: Pore structure and chemical group optimization - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Lin Guo; Youming Zhu; Jinfeng Mei; Jian Rong; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Effect of gibberellic acid treatment and cold stratification on breaking combined (physiological + mechanical) dormancy and germination in Sassafras tzumu (Hemsl.) Hemsl seeds - Yu Wu; Zhi Yun Deng; Ming Zhu Wang; Lin Yue Liu; Yong Bao Shen (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Unveiling the regulatory mechanism of pulsed electric field modified instant soy milk powder: Exploring allergenicity, conformation, and epitopes - Jie Ding; Yaru Li; Limin Zhong; Xinqing Lu; Zhijie Bao; Songyi Lin (Food Chemistry, 2025)

Improving the bactericidal activity of carvacrol against Bacillus cereus by the formation of sodium casein-stabilized nanoemulsion and its application in milk preservation - Jun Li; Fu-Yu Liu; Bao-Lin He; Rui Cui; Hong Wu (Food Hydrocolloids, 2025)

Advancing zero-carbon community in China: policy analysis, implementation challenges, and strategic recommendations - Lin Zhou; Shun Li; Zhengxuan Liu; Yuekuan Zhou; Bao-Jie He; Zhenya Zhang; Hanbing Wang; Guoqiang Zhang (Energy and Buildings, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Cadmium translocation combined with metabolomics analysis revealed potential mechanisms of MT@MSN-CS and GSH@MSN-CS in reducing cadmium accumulation in rice (Oryza sativa L.) grains - Wen-Ze Fang; Jun-Qiao Chen; Jing-Dong Mao; Bao-Feng Zhang; Li-Ping Lou; Qi Lin (Environmental Science and Pollution Research, 2025)

Taxifolin regulates SLC31A1-mediated cuproptosis and tumor progression in hepatocellular carcinoma - Jike Li; Yuelian Wang; Lei Bao; Guo Chen; Qing Ye; Chengshi He; Lin Liu; Mei Luo (Human Cell, 2025)

Deciphering Trachinotus ovatus resistance to Streptococcus agalactiae:GWAS identification of key SNPs and candidate genes - Yi-Yao Sun; Jie Gao; Bao-Suo Liu; Nan Zhang; Hua-Yang Guo; Ke-Cheng Zhu; Lin Xian; Dian-Chang Zhang (Aquaculture, 2025)

PPARβ/δ agonist GW0742 mitigates acute liver damage induced by acetaminophen overdose in mice - Lin Wang; Jing-Hui Chen; Yan-Jing Zhang; Ming-Bao Zhang; Tao Zeng (Toxicology and Applied Pharmacology, 2025)

Coupling phylogenetic relatedness and distribution patterns provides insights into sandburs invasion risk assessment - Ming Yang; Yuhan Qi; Xiaoqing Xian; Nianwan Yang; Lin Xue; Chi Zhang; Han Bao; Wanxue Liu (Science of The Total Environment, 2025)

Efficient removal of levofloxacin by FeCo2O4@C-REC activated peroxymonosulfate: Performance and mechanism - Bai-Hang Zhao; Bao-Yu Zhang; Bing-Lin Zhang; Jing Zhang; Chun Wang; Ye Li (Journal of Water Process Engineering, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Nanozyme-mediated ratiometric fluorescence hydrogel for on-site detection of sulfite in food - Si-Qi Yang; Bao-Zhu Jia; Jie Liu; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Screening and molecular interaction machine investigation of fish scale collagen novel auxiliary memory-improving peptides - Siqi Shen; Jie Ding; Shuyu Zhang; Deyou Gao; Zhijie Bao; Songyi Lin (Food Bioscience, 2025)

Improved viability of probiotics by co-encapsulation of wheat germ oil under storage and gastrointestinal conditions: Effects of drying methods and wall composition - Bao-Lin He; Rui Cui; Teng-Gen Hu; Hong Wu (Food Hydrocolloids, 2025)

Identification and quantification of volatile organic compounds in Chinese recycled HDPE: Consequences for its applicability - Ming-Yue Zhang; Qi-Zhi Su; Qin-Bao Lin; Huai-Ning Zhong; Sheng Chen; Dan Li; Ben-Dong; Min-Qing Xu; Wei-Li Li (Food Packaging and Shelf Life, 2025)

An assessment of the psychologically restorative effects of the environmental characteristics of university common spaces - Hongyan Wen; Hanzheng Lin; Xiao Liu; Weihong Guo; Jiawei Yao; Bao-Jie He (Environmental Impact Assessment Review, 2025)

Confined ionic association and its effect on Li+/Mg2+ permselective transport through the HKUST-1 nanopore - Jianduo Zhang; Fucheng Dai; Jianbo Li; Dawei He; Xuan Lin; Xiaobin Jiang; Junjiang Bao; Xiaopeng Zhang; Gaohong He; Ning Zhang (Desalination, 2025)

Chronic polyaluminum chloride perturbation shaped community assembly patterns: An overlooked mechanism of nitrogen removal inhibition - Nan-ping Wu; Qian Zhang; Hong-yu Wang; Yun-jie Zhang; Meng Li; Bin Ji; Yufei Bao; Bing Lin; Yu-wei Ding; Qi He; Jia-jing Chen (Chemical Engineering Journal, 2025)

Multi-omics analyses reveal mechanism for high resistant starch formation in an indica rice SSIIIa mutant - Yining Ying; Bowen Deng; Lin Zhang; Yaqi Hu; Lei Liu; Jinsong Bao; Feifei Xu (Carbohydrate Polymers, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

SNPs in the Galectin-8 gene of Acanthopagrus latus have been found to be associated with resistance trait to Streptococcus iniae - Jin-Min Pan; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Teng-Fei Zhu; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture International, 2025)

Characterization of the Galectin-3 gene and its association with Streptococcus iniae resistance traits in Acanthopagrus latus (Houttuyn, 1782) - Jin-Min Pan; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Teng-Fei Zhu; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture, 2024)

Genomic prediction of growth traits in autotetraploid Pacific oyster (Crassostrea gigas) using whole-genome resequencing - Weijun Wang; Xiaokai Bao; Tao Lin; Yuting Meng; Zan Li; Guohua Sun; Yanwei Feng; Xiaohui Xu; Jianmin Yang; Yangfan Wang (Aquaculture, 2024)

A high selective separation method for high-purity polysaccharides from dandelions by density-oriented deep eutectic solvent ultrasonic-assisted system - Han Zhang; Yu Lin; Yanan Bao; Wen-Jing Li; Bo Hong; Min Zhao (Sustainable Chemistry and Pharmacy, 2024)

An effective way to monitor the population of juvenile horseshoe crabs in the Beibu Gulf of China - Mujiao Xie; Yuyuan Bao; Xiaoyong Xie; Wuying Lin; Xiaohai Chen; Xinyi Zhao; Xiaobo Xiao (Regional Studies in Marine Science, 2024)

SILAR-assisted synthesis of Cu2O modified TiO2 nanotube arrays: Study on efficient photocatalytic dye degradation and hydrogen evolution - Junwei Hou; Lin Gan; Nan Bao; Chengye Zhang; Kailu Liu; Qingyao Wang (Journal of Water Process Engineering, 2024)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Room-temperature synthesis of carbon polymer dots from biomass for advanced sensing and fluorescent applications - Lin Lan; Rui Bao; Xin Kong; Liang Liu; Jinsong Wang; Jianhong Yi (Journal of Environmental Chemical Engineering, 2024)

Facile preparation of photothermal and superhydrophobic melamine sponge for oil/water separation and anti-icing - Mingkun Wang; Zhihong Zhou; Lei Qiao; Bao Lin; Zhiwei He (Journal of Environmental Chemical Engineering, 2024)

The revelation of characteristic volatile compounds in egg powder and analysis of their adsorption rules based on HS-GC-IMS technology - Liu Dong; Fujun Guo; Yuan Gao; Zhijie Bao; Songyi Lin (Food Chemistry, 2024)

Mechanism of targeted uric acid reduction by soybean protein peptide SHECN in hyperuricemia mice and improvement of liver injury - Yifei Dong; Dongmei Li; Zhijie Bao; Yiru Chen; Songyi Lin (Food Bioscience, 2024)

The interaction of Lactiplantibacillus plantarum and Latilatilactobacillus sakei regulated the formation of characteristic quality attributes of low-salt fermented tilapia - Ke Zhang; Si-Jia Lin; Xin-Yi Qi; Bao-Cai Xu; Lei Qin; Xu-Hui Huang (Food Bioscience, 2024)

Screening and safety assessment of migrating substances released from biodegradable packaging materials into milk - Chuang-Chuang Zhao; Qin-Bao Lin; Cang-Hao Xie; Yi-Qi Liu; Huai-Ning Zhong; Wei-Yue Gu; David Julian McClements; Da Ma (Food Control, 2024)

Aluminate-activated nano-SiO2 for enhancing water vapor barrier properties in polymers films: A safe and effective strategy - Chuang-Chuang Zhao; Qin-Bao Lin; Yan-Fen Chen; Huai-Ning Zhong; David Julian McClements; Da Ma (Food Packaging and Shelf Life, 2024)

Corrigendum to “Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor” [Environ. Res. 231 (2023) 116061] - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2024)

Ratiometric fluorescence and photothermal dual-mode immunosensor based on MnO2 nanosheets for the detection of isocarbophos - Jie Liu; Hao Deng; Bao-Zhu Jia; Ze-Shan Lin; Yu Wang; Hong Wang; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2024)

High-valent iron–oxo species in heterogeneous catalysis: Formation, mechanism, and reactivity for the degradation of various emerging organic contaminants - Yin Li; Jiahui Hu; Yutian Bao; Yanan Xiao; Lin Lin; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

Transcriptome profiling of longissimus dorsi during different prenatal stages to identify genes involved in intramuscular fat deposition in lean and obese pig breeds - Jun Feng Chen; Jing Wang; Jin Chai; Wei Jin; Qiao Ling Ren; Qiang Ma; Qing Xia Lu; Jia Jie Sun; De Lin Mo; Jia Qing Zhang; Bao Song Xing (Molecular Biology Reports, 2024)
Background There was significant difference in muscle development between fat-type and lean-type pig breeds. Methods and results In current study, transcriptome analysis and bioinformatics analysis were used to compare the difference in longissimus dorsi (LD) muscle at three time-points (38 days post coitus (dpc), 58 dpc, and 78 dpc ) between Huainan (HN) and Large white (LW) pig breeds. A total of 24500 transcripts were obtained in 18 samples, and 2319, 2799, and 3713 differently expressed genes (DEGs) were identified between these two breeds at 38 dpc, 58 dpc, and 78 dpc, respectively. And the number and foldchange of DEGs were increased, the alternative splice also increased. The cluster analysis of DEGs indicated the embryonic development progress of LD muscle between these two breeds was different. There were 539 shared DEGs between HN and LW at three stages, and the top-shared DEGs were associated with muscle development and lipid deposition, such as KLF4, NR4A1, HSP70, ZBTB16 and so on. Conclusions The results showed DEGs between Huainan (HN) and Large white (LW) pig breeds, and contributed to the understanding the muscle development difference between HN and LW, and provided basic materials for improvement of meat quality.

EMP1 correlated with cancer progression and immune characteristics in pan-cancer and ovarian cancer - Jun Zhang; Jing Yang; Xing Li; Lin Mao; Yan Zhang; Yi Liu; Yindi Bao (Molecular Genetics and Genomics, 2024)

Effects of Dietary 5-Aminolevulinic Acid on Growth, Nutrient Composition, and Intestinal Microflora in Juvenile Shrimp, Litopenaeus vannamei - Yiming Li; Yucong Ye; Yashi Zhu; Zongli Yao; Kai Zhou; Yuxing Wei; Lin Zhang; Ning Bao; Yunlong Zhao; Qifang Lai (Marine Biotechnology, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Characterization of the transmembrane C-type lectin reveals a novel phagocytic receptor for hemocytes of Tegillarca granosa - Dan Su; Jie Lin; Yang Zhang; Zexin Yang; Yefeng Lin; Yingbin Xu; Shanjie Zha; Yongbo Bao; Hongxing Liu (Aquaculture, 2024)

Chronic dietary exposure to glyphosate-induced connexin 43 autophagic degradation contributes to blood-testis barrier disruption in roosters - Qing Liang; Bao-You Liu; Tian-Lin Zhang; Hai-Jing Zhang; Yu-Long Ren; Hai-Peng Wang; Hao Wang; Lin Wang (Science of The Total Environment, 2024)

Synergistic management of nitrogen contamination in overflow wastewater and algal proliferation in lake receiving wastewater based on electrochemical oxidation process - Ya-Ning Wang; Ding Li; Lin Liu; Jia-Fang Xie; Zhi-Tang Lyu; Quan-Bao Zhao; Yu-Ming Zheng (Process Safety and Environmental Protection, 2024)

Finite time adaptive recoil controller design for deepwater drilling riser systems - Yun Zhang; Bao-Lin Zhang; Qing-Long Han; Yan Ji; Yanbin Wang; Bin Zhang (Ocean Engineering, 2024)

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

Comparison and identification of aroma components in 21 kinds of frankincense with variety and region based on the odor intensity characteristic spectrum constructed by HS–SPME–GC–MS combined with E-nose - Xinming Chen; Dandan Yang; Lin Huang; Mengqi Li; Jihai Gao; Can Liu; Xiaoming Bao; Zhizhi Huang; Jinhui Yang; Haozhou Huang; Dingkun Zhang; Runchun Xu (Food Research International, 2024)

Development of fermented Atemoya (Annona cherimola × Annona squamosa)-Amazake increased intestinal next-generation probiotics - Yeu-Ching Shi; She-Ching Wu; Yi-Ching Lin; Yu-Juan Zheng; Cheng-Hao Huang; Bao-Hong Lee (Food Chemistry, 2024)

Insufficient FUNDC1-dependent mitophagy due to early environmental cadmium exposure triggers mitochondrial redox imbalance to aggravate diet-induced lipotoxicity - Cai-Yu Lian; Hui-Jia Li; Wei-Hao Xia; Yue Li; Xue-Lei Zhou; Du-Bao Yang; Xue-Mei Wan; Lin Wang (Environmental Pollution, 2024)

Enhanced seismic performance: A novel cable brace with bending energy dissipation for semi-rigid steel frames - Wei Bao; Zhaoxin Lin; Fengming Ren; Guifeng Zhao; Jiaopeng Fang; Zhanhua Liang (Engineering Structures, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Smart nanoscale lamellated supramolecular assemblies overcome biofilm barriers and enhance foliar affinity for efficient control of bacterial diseases - Lizhu Xiang; Xiaohui Wang; Jinghan Yang; Rui Wang; Lin Chen; Xiaoping Bao; Xianfu Mu; Peiyi Wang (Chemical Engineering Journal, 2024)

Variations in soil quality indicators under different cultivation ages and slope positions of arable land in the Mollisol region of China - Bao Liu; Yanru Wen; Litao Lin; Xue Wen; Ruilu Gao; Bin Zhang; Ting-Yong Li; Shuihong Yao (CATENA, 2024)

A Cohesive Model-Based Nonlinear Discontinuous Deformation Analysis for Tensile Fracture in Geotechnical Materials - Shi-Lin Gong; Cheng-Bao Hu; Dao-Sheng Ling; Jia-Ying Liu; Zhong-Ling Zong; Guang-Qi Chen; Miao-Miao Sun (Rock Mechanics and Rock Engineering, 2024)

Correction to: A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Ubiquity and ecological risks of conjugated steroids cannot be overlooked: First evidence from estuarine sediments - Fei Tian; Shan Liu; Ru Xu; Nian-Nian Wu; Shuang-Shuang Liu; Yuan-Yue Cheng; Qian Xiong; Zhen-Zhao Tang; Lin-Bao Zhang; Zhe Zhang; Hai-Gang Chen (Marine Pollution Bulletin, 2024)

Experimental study on the burning characteristics and smoke temperature distribution of continuous spill fires in sloped tunnels - Weibing Jiao; Changkun Chen; Zida Lin; Yipeng Bao; Lang Shi (Tunnelling and Underground Space Technology, 2024)

Applications of electrospun nanofibers in food safety and quality analysis: A review - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Lin Luo; Zhen-Lin Xu (Trends in Food Science & Technology, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

A novel neuroprotective peptide against cognitive disorder in mice by regulating hippocampal oxidative stress and synaptic plasticity - Zhiqiang Lu; Yuan Gao; Zhijie Bao; Songyi Lin (Food Bioscience, 2024)

Molecular characterization of histone gene in golden pompano (Trachinotus ovatus) and antimicrobial activity of its derived peptides - Yu Liang; Jin-Min Pan; Ke-Cheng Zhu; Lin Xian; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Teng-Fei Zhu; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Design, synthesis, X-ray crystal structure, and antimicrobial evaluation of novel quinazolinone derivatives containing the 1,2,4-triazole Schiff base moiety and an isopropanol linker - Lan Yang; Muhan Ding; Jun Shi; Na Luo; Yuli Wang; Dongyun Lin; Xiaoping Bao (Molecular Diversity, 2024)

A clinical-radiomics nomogram based on spectral CT multi-parameter images for preoperative prediction of lymph node metastasis in colorectal cancer - Qian Li; Rui Hong; Ping Zhang; Liting Hou; Hailun Bao; Lin Bai; Jian Zhao (Clinical & Experimental Metastasis, 2024)

Verification of Seasonal Prediction by the Upgraded China Multi-Model Ensemble Prediction System (CMMEv2.0) - Jie Wu; Hong-Li Ren; Jianghua Wan; Jingpeng Liu; Jinqing Zuo; Changzheng Liu; Ying Liu; Yu Nie; Chongbo Zhao; Li Guo; Bo Lu; Lijuan Chen; et al. (Journal of Meteorological Research, 2024)

Tick saliva interference with LTβR signaling facilitates the transmission of Lyme disease spirochetes - Lin Jin; Bao-Gui Jiang; Yizhu Yin; Jingya Guo; Jia-Fu Jiang; Xiaopeng Qi; Gary Crispell; Shahid Karim; Wu-Chun Cao; Ren Lai (Toxicon, 2024)

Distribution of soil tardigrades as revealed by molecular identification across a large-scale area of Australia - Zi-Yang He; Hang-Wei Hu; Bao-Anh Thi Nguyen; Qing-Lin Chen; Anthony Weatherley; Michael Nash; Li Bi; Keren Wu; Ji-Zheng He (Soil Biology and Biochemistry, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

A machine learning scheme for estimating fine-resolution grassland aboveground biomass over China with Sentinel-1/2 satellite images - Huaqiang Li; Fei Li; Jingfeng Xiao; Jiquan Chen; Kejian Lin; Gang Bao; Aijun Liu; Guo Wei (Remote Sensing of Environment, 2024)

Research and application of comprehensive detection methods for geological structural planes in drill and blast tunnels - Peng Yang Qiao; Zao Bao Liu; Yong Ping Li; Chao Lin; Guo Ying Yan (Journal of Applied Geophysics, 2024)

De novo synthesis of a novel hapten and development of a monoclonal antibody–based immunoassay for the detection of dichlorvos and trichlorfon - Bao-Zhu Jia; Feng-Yan Chen; Xing-Xing Yang; Surat Hongsibsong; Xing-Xing Wang; Zhen-Lin Xu; Lin Luo (Food Chemistry, 2024)

Identification and health risk assessment of volatile and semi-volatile migrants along with chemical elements in food contact water-borne coating paper - Qing-Hua Yang; Qin-Bao Lin; Xin-Yu Hua; Jia Liao; Shi-Qiang Lu; Ling-Yan Yan; Hong-Sheng Ma (Food Packaging and Shelf Life, 2024)

A bounding surface model for anisotropic and structured soils under saturated and unsaturated conditions - Bao-Lin Dai; Chao Zhou; Anh Minh Tang; Lina-María Guayacán-Carrillo (Computers and Geotechnics, 2024)

Self-conductive organic quaternary ammonium lithium salt-based ultra-concentrated electrolyte for safe lithium metal batteries - Yijing Liu; Sibo Qiao; Jinrui Hu; Fen Guo; Lixia Bao; Weichao Lin; Xiao Xu; Pengpeng Liu; Weibo Kong; Yuehan Jia; Jiliang Wang (Chemical Engineering Journal, 2024)

Carbon dots with tunable excitation-independent fluorescence and organelle-specific targeting via core graphitization and surface groups engineering - Ming-Yuan Sun; Bao-Hua Tian; Xin-Xin Li; Yu Li; Yu Lei; Xi-Lin Guo; Qiang Miao; Hao Li; Hai-Xia Liang (Chemical Engineering Journal, 2024)

Spodumene nanosheets@ZrO2-SiO2 heterostructure nanofibers modified separator for long-cycle lithium-sulfur batteries - Lin Li; Bin Yue; Yingying Bao; Shan Jiang; Hong Shao; Qianli Ma; Wensheng Yu; Jinxian Wang; Xiangting Dong (Chemical Engineering Journal, 2024)

Hierarchical supramolecules composed of starch-based nanocluster aggregates with light-responsive mechanical strain for remotely rapid and precise actuation - Fu-Xiang Wei; Xu Yuan; Feng-Qiong Jiang; Zhen Wang; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Carbohydrate Polymers, 2024)

Influence of arbuscular mycorrhizal fungi on root foraging and competitive ability depends on soil phosphorus distribution: evidence from two pairs of invasive and native plants - Na-Na Yao; Ao Liu; Xiao-Jing Wang; Hao-Hui Deng; Sheng-Qi Fan; Hai-Jie Zhang; Hui-Xuan Liao; Shao-Lin Peng; Bao-Ming Chen (Applied Soil Ecology, 2024)

Dietary Supplementation with Nano-Curcumin Improves the Meat Quality and Nutrition Value of Largemouth Bass (Micropterus salmoides) Fed with a High-Carbohydrate Diet - Yamin Wang; Jing Chen; Kaipeng Zhang; Xiaoxue Bao; Shan Xie; Zhenye Lin; Xiaotong Chen; Yingying Yu (Fishes, 2024)
This study investigated the effects of curcumin nanoparticles on the flesh quality of largemouth bass on a high-carbohydrate diet. A total of 180 fish (11.01 ± 0.02 g) were fed three semi-purified diets: the Control group (LC) were supplemented with standard carbohydrate (10%), the experimental group (HC) were supplemented with 15% carbohydrate, and the experimental group were supplemented with 0.2% nano-curcumin added to 15% carbohydrate (HCN) for 6 weeks. Results showed that a* value, taurine, valine, isoleucine, histidine, cystine, fatty acids (C17:0 and C20:2n6), MDA (malondialdehyde) content, and SOD (Superoxide dismutase) activity were significantly elevated (p

Investigating Polystyrene Nano-Plastic Effects on Largemouth Bass (Micropterus salmoides) Focusing on mRNA Expression: Endoplasmic Reticulum Stress and Lipid Metabolism Dynamics - Kaipeng Zhang; Jing Chen; Yamin Wang; Mingshi Chen; Xiaoxue Bao; Xiaotong Chen; Shan Xie; Zhenye Lin; Yingying Yu (Fishes, 2024)
Nano-plastics (NPs) have emerged as a pervasive global contaminant, posing significant threats to carnivorous fish, in recent years. The accumulation of polystyrene nano-plastics (PS-NPs) can cause endoplasmic reticulum (ER) stress. However, the concurrent impacts of PS-NPs on lipid metabolism and ER stress in largemouth bass have not been sufficiently investigated. To study this gap, we established a largemouth bass model exposed to PS-NPs in a culture environment. The exposure experiment focused on 100 μg/L PS-NPs (100 nm). Transcriptomics analysis revealed a significant enrichment of differentially expressed genes involved in a lipid metabolism pathway and ER process. The levels of biochemical parameters associated with lipid metabolism, including high-density lipoprotein cholesterol, total cholesterol, triglyceride, and low-density lipoprotein cholesterol, demonstrated that exposure to PS-NPs for nineteen days had an impact on lipid metabolism. Additionally, the expression levels of genes associated with fatty acid biosynthesis and ER stress exhibited a significant increase following exposure to PS-NPs for nineteen days, whereas these changes were not significant after a seven-day exposure period. The ER stress induced by PS-NPs exhibited a positive correlation with lipid metabolism disorder and the magnitude of damage caused by prolonged exposure to PS-NPs in largemouth bass. The present study provides novel insights into the health threats encountered by largemouth bass when exposed to NPs.

Multidimensional Evaluation of Altimetry Marine Gravity Models with Shipborne Gravity Data from a New Platform Marine Gravimeter - Bo Wang; Lin Wu; Pengfei Wu; Qianqian Li; Lifeng Bao; Yong Wang (Journal of Marine Science and Engineering, 2024)
With the development of satellite altimetry technology and the application of new altimetry satellites, the accuracy and resolution of altimeter-derived gravity field models have improved over the last decades. Nowadays, they are close enough to shipborne gravimetry. In this paper, multi-source shipborne gravity data in the South China Sea were taken to evaluate the accuracies of two high-precision altimeter-derived marine gravity field models (SS V30.1, DTU17). In these shipborne gravity data, there are dozens of routes’ ship gravimetry data, obtained from the National Geophysical Data Center (NGDC); data were tracked from a marine survey with a commercial marine gravimeter (type KSS31M), and data were tracked from a marine gravimetry campaign that was conducted with a newly developed platform gravimeter (type JMG) in the South China Sea in September 2020. After various data filtering, processing, and calibrations, the shipborne gravity data were validated with crossover points analysis. Then, the processed shipborne data were employed to evaluate the accuracy of the altimeter-derived marine gravity field models. During this procedure, the quality of JMG shipborne gravity data was compared with the results of KSS31M and NGDC data. Analysis and evaluation results show that the crossover points verification accuracies of KSS31M and JMG are 0.70 mGal and 1.61 mGal, which are much better than the accuracy of NGDC, which is larger than 8.0 mGal. In the area where the bathymetry changes slowly, the root mean square error values between altimetry gravity models and KSS31M data are respectively 3.28 mGal and 4.54 mGal, and those of the JMG data are respectively 2.94 mGal and 2.60 mGal. According to the above results, we can conclude that the JMG has the same 1–2 mGal accuracy level as KSS31M and can meet the measurement requirements of marine gravity.

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Investigation of coupled response on cylindrical eccentricity induced vibration and flow induced vibration - Yanxu Bao; Xiaoyu Zhang; Yongshui Lin; Jiangyan Shao; Wei Chen; Chang-Kyu Rheem; Xiaobin Li (Ocean Engineering, 2024)

On the transferability of residence time distributions in two 10-km long river sections with similar hydromorphic units - Jie Bao; Xuehang Song; Yunxiang Chen; Yilin Fang; Xinming Lin; Zhangshuan Hou; Zhuoran Duan; Huiying Ren; William Perkins; Xiaoliang He; Timothy Scheibe (Journal of Hydrology, 2024)

New simple method for calculating large-strain consolidation settlement of layered soft soils with horizontal drains and vacuum preloading with comparison to test data - Ze-jian Chen; Peng-lin Li; An Li; Jian-hua Yin; Ding-bao Song (Geotextiles and Geomembranes, 2024)

Large magnesium isotopic fractionation in lunar agglutinatic glasses caused by impact-induced chemical diffusion - Le Zhang; Cheng-Yuan Wang; Hai-Yang Xian; Jintuan Wang; Yan-Qiang Zhang; Zhian Bao; Mang Lin; Yi-Gang Xu (Geochimica et Cosmochimica Acta, 2024)

Effects of dietary 5-aminolevulinic acid on growth performance and nonspecific immunity of Litopenaeus vannamei, as determined by transcriptomic analysis - Yucong Ye; Siwen Li; Xinglin Du; Lin Zhang; Ning Bao; Yiming Li; Yunlong Zhao (Fish & Shellfish Immunology, 2024)

Surface charge accumulation of functionalized carbonized polymer dots selectively induces lysosomal membrane permeabilization of breast cancer cells - Yu Lei; Bao-Hua Tian; Xin-Xin Li; Ming-Yuan Sun; Xi-Lin Guo; Yi-Da Wang; Hui-Qing Zhou; Ri-Sheng Ma; Hai-Xia Liang (Chemical Engineering Journal, 2024)

The effects of nanoplastics and microcystin-LR coexposure on Aristichthys nobilis at the early developmental stages - Chaonan Zhang; Fei Wang; Feifan Bao; Junjie Zhu; Jiang Xu; Daohui Lin (Aquatic Toxicology, 2024)

Genomic structures of insulin-like growth factor from golden pompano (Trachinotus ovatus) and their expression responses to the feed types - Bo Liu; Yin-Yin Liang; Hua-Yang Guo; Bao-Suo Liu; Jing-Wen Yang; Nan Zhang; Lin Xian; Ke-Cheng Zhu; Dian-Chang Zhang (Fish Physiology and Biochemistry, 2024)

A rho-type GTPase activating protein affects the growth and development of Cordyceps cicadae - Xueqian Li; Yu Zou; Neeraj Shrivastava; Jiandong Bao; Fu-Cheng Lin; Hongkai Wang (Archives of Microbiology, 2024)

Wind and Wave-Induced Vibration Reduction Control for Floating Offshore Wind Turbine Using Delayed Signals - Shouxiang Yan; Yilong Wang; Fengbin Pang; Wei Zhang; Bao-Lin Zhang (Journal of Marine Science and Engineering, 2024)
Active vibration control is a critical issue of the wind turbine in the field of marine energy. First, based on a three-degree-of-freedom wind turbine, a state space model subject to wind and wave loads is obtained. Then, a delayed state feedback control scheme is illustrated to reduce the vibration of platform pitch angle and tower top foreaft displacement, where the control channel includes time-delay state signals. The designed controller’s existence conditions are investigated. The simulation results show that the delayed feedback H∞ controller can significantly suppress wind- and wave-induced vibration of the wind turbine. Furthermore, it presents potential advantages over the delay-free feedback H∞ controller and the classic linear quadratic regulator in two aspects: vibration control performance and control cost.

A global meta-analysis reveals the positive effect of invasive alien plants on soil heterotrophic respiration - Sheng-Qi Fan; Shao-Lin Peng; Bao-Ming Chen (Soil Biology and Biochemistry, 2024)

Co-hydrothermal carbonization of municipal sludge and agricultural waste to reduce plant growth inhibition by aqueous phase products: Molecular level analysis of organic matter - Guangchun Shan; Weiguang Li; Jie Liu; Shanshan Bao; Zhenling Li; Shuncai Wang; Lin Zhu; Beidou Xi; Wenbing Tan (Science of The Total Environment, 2024)

Safety assessment of polypropylene self-heating food container: The release of microplastics and volatile organic compounds - Can Xu; Jia-ling Hu; Ben Dong; Qin-bao Lin; Si-liang Wu; Jie Chen; Jing Wang; Dan Li; Huai-ning Zhong (Food Packaging and Shelf Life, 2024)

An untargeted metabolomics study of cardiac pathology damage in rats caused by low selenium diet alone or in combination with T-2 toxin - Xue Lin; Lichun Qiao; Haobiao Liu; Miaoye Bao; Huan Deng; Lianxu Jia; Xinyue Wen; Feidan Deng; Ping Wan; Yizhen Lyu; Jing Han (Food and Chemical Toxicology, 2024)

Three thousand years of Hg pollution recorded in mangrove wetland sediments from South China - Minqi Chen; Bigyan Neupane; Xuan Zhan; Ting Liu; Zhanyi Lin; Changjun Gao; Claudio Zaccone; Kunshan Bao (Environmental Research, 2024)

Effects of fertilization applications on soil aggregate organic carbon content and assessment of their influencing factors: A meta-analysis - Xi Yang; Yiwen Bao; Bowen Li; Ruixue Wang; Chao Sun; Donghao Ma; Lin Chen; Hongtao Zou; Jiabao Zhang (CATENA, 2024)

Savanna Nightjars (Caprimulgus affinis stictomus) adjust calling height to gain amplitude advantage in urban environments - Shih-Hsiung Liang; Chia-Hung Jen; Lin-Lee Lee; Chao-Chieh Chen; Bao-Sen Shieh (Journal of Ornithology, 2024)

Gelselegine-gelsedine type bisindoles as well as the units from Gelsemium elegans with promoting proliferation of oral mucosa fibroblast cells - Jing Lin; Jing Wu; Mei-Fen Bao; Sumet Kongkiatpaiboon; Xiang-Hai Cai (Phytochemistry, 2024)

Dynamic analysis of lift-off operation of offshore wind turbine jacket foundation from the transportation barge - Mingsheng Chen; Guibo Yuan; Bin Li; Chun Bao Li; Mingjun Ouyang; Lin Li; Wei Shi; Zhaolong Han; Wei Zhang; Ziwen Chen (Ocean Engineering, 2024)

Effect of aqueous phase from hydrothermal carbonization of sewage sludge on heavy metals and heavy metal resistance genes during chicken manure composting - Guangchun Shan; Xiaoshu Wei; Weiguang Li; Jie Liu; Shanshan Bao; Shuncai Wang; Lin Zhu; Beidou Xi; Wenbing Tan (Journal of Hazardous Materials, 2024)

BmNPV p35 regulates apoptosis in Bombyx mori via a novel target of interaction with the BmVDAC2-BmRACK1 complex - Lin-Bao Zhu; Han-Dan Zhu; Zhi-Hao Huang; Hui-Hua Cao; Sadaf Ayaz; Jia-Yue Yang; Xi-Ya Chen; Ying Zhang; Shi-Huo Liu; Jia-Ping Xu (Insect Biochemistry and Molecular Biology, 2024)

Axisymmetric finite strain consolidation model for soft soil consolidation with vertical drains under combined loading considering creep and non-Darcy flow - Peng-Lin Li; Zhen-Yu Yin; Ding-Bao Song; Jian-Hua Yin; Yu Pan (Geotextiles and Geomembranes, 2024)

Extending the freshness of tilapia surimi with pulsed electric field modified pea protein isolate-EGCG complex - Zhong Han; Ze-Ling Chen; Xin-Dong Xu; Songyi Lin; Yan Wang; Lang-Hong Wang; De-Bao Niu; Xin-An Zeng; Meng-Wai Woo; Ruo-Yong Wang (Food Hydrocolloids, 2024)

Co-enzymatic hydrolysis enhanced thermal stability of mayonnaise - Guangshun Jiang; Songyi Lin; Junzhang Li; Kun Liu; Fujun Guo; Zhijie Bao (Food Bioscience, 2024)

Advances in dual-functional packaging: Visual monitoring of food freshness using plant essential oils and pH-sensitive natural pigments - Qiong Peng; Feng Bao; Min Tang; Feifei Zhong; Wen Li; Jing Deng; Qinlu Lin; Mingli Yan; Zavuga Zuberi (Food Control, 2024)

Preparation of an injectable and photocurable carboxymethyl cellulose/hydroxyapatite composite and its application in cranial regeneration - He Qiu; Jing Wang; Hong Hu; Lu Song; Zhanhong Liu; Yang Xu; Shuo Liu; Xiangdong Zhu; Hang Wang; Chongyun Bao; Hai Lin (Carbohydrate Polymers, 2024)

Shelterbelt effects on soil redistribution on an arable slope by wind and water - Yanru Wen; Bao Liu; Litao Lin; Mengmeng Hu; Xue Wen; Ting-Yong Li; Jiandong Rong; Shuihong Yao (CATENA, 2024)

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Gold nanocluster-based ratiometric fluorescence immunoassay for broad-spectrum screening of five eugenols - Lin Luo; Zhen-Xi He; Bao-Zhu Jia; Rui-Yao Kang; Wen-Feng Zhang; Ri-Ming Huang; Zhen-Lin Xu (Analytica Chimica Acta, 2024)

Toward intelligent food packaging of biosensor and film substrate for monitoring foodborne microorganisms: A review of recent advancements - Feng Bao; Zhao Liang; Jing Deng; Qinlu Lin; Wen Li; Qiong Peng; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Insights into growth stages and genotypes in airborne Pb accumulation in Oryza sativa L. grains: Utilizing isotope fingerprinting alongside a model study - Qi Lin; Ming-Jin Zhuang; Wei Dai; Jing Fang; Bao-Feng Zhang; Jing-Dong Mao; Li-Ping Lou (Chemosphere, 2024)

Landscape of plasmids encoding β-lactamases in disinfection residual Enterobacteriaceae from wastewater treatment plants - Zejun Lin; Zhenchao Zhou; Xinyi Shuai; Guangshu Zeng; Ruiqi Bao; Hong Chen (Water Research, 2024)

Natural or balanced? The physiological and psychological benefits of window views with different proportions of sky, green space, and buildings - Tianyi Yao; Wei Lin; Zhiyi Bao; Chengcheng Zeng (Sustainable Cities and Society, 2024)

Extended state-based finite-time fuzzy optimal recoil control for nonlinear drilling riser systems after emergency disconnection - Bao-Lin Zhang; Ying-Tai Guo; Qing-Long Han; Yan Ji; Yanbin Wang; Xian-Ming Zhang; Zhihui Cai (Ocean Engineering, 2024)

Discrete recoil control system modelling and optimal recoil damping of deepwater drilling riser systems - Bao-Lin Zhang; Yue-Ting Sun; Yan-Dong Zhao; Qing-Long Han; Xian-Ming Zhang; Zhihui Cai (Ocean Engineering, 2024)

Association of blood cadmium levels and all-cause mortality among adults with rheumatoid arthritis: The NHANES cohort study - Haobiao Liu; Mian Liu; Lichun Qiao; Zhihao Yang; Yujie He; Miaoye Bao; Xue Lin; Jing Han (Journal of Trace Elements in Medicine and Biology, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

A highly sensitive ratiometric fluorescent probe for detecting HSO3−/SO32− and viscosity change based on FRET/TICT mechanism - Feng-Ting Liu; Shu-Mei Zhai; Dong-Fang Gao; Shu-Hao Yang; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2024)

Carbon doping enhances the fluoride removal performance of aluminum-based adsorbents - Lin Tong; Ying Miao; Shushu Li; Ning Bao; Qingwen Zhou; Yuhuan Yang; Changqing Ye (Environmental Science and Pollution Research, 2024)

High arsenic pollution of the eutrophic Lake Taihu and its relationship with iron, manganese, and dissolved organic matter: High-resolution synchronous analysis - Wenming Yan; Xiangyu He; Musong Chen; Bao Qian; Minjuan Li; Yulin Yan; Chen Lin; Zhigang Mao (Journal of Hazardous Materials, 2024)

Electrochemical oxidation degradation of xanthate and its mechanism: Effects of carbon chain length and electrolyte type - Huanjun Bao; Meirong Wu; Xiangsong Meng; Shangyong Lin; Jianhua Kang; Wei Sun (Journal of Cleaner Production, 2024)

The Pacific-North American teleconnection in the Cenozoic - Zhibo Li; Yongyun Hu; Jian Zhang; Xiang Li; Jiaqi Guo; Jiawenjing Lan; Qifan Lin; Shuai Yuan; Mengyu Wei; Zihan Yin; Qiang Wei; Xiujuan Bao; et al. (Global and Planetary Change, 2024)

Impact of ethanol extract of propolis on heat-induced egg white protein gels: Formation and properties - Man Zhang; Lin Mei; Yating Wu; Guoguo Jin; Di Bao (Food Hydrocolloids, 2024)

Effects of polypropylene microplastics on carbon dioxide dynamics in intertidal mangrove sediments - Xubing Lin; Shuying Lin; Licheng Peng; Miao Chen; Xing Cheng; Shiyu Xie; Ruiqi Bao; Yuanyuan Su; Tariq Mehmood (Environmental Pollution, 2024)

KOH-activated biochar and chitosan composites for efficient adsorption of industrial dye pollutants - Xu Su; Xuanming Wang; Ziyi Ge; Zhengrong Bao; Li Lin; Yixuan Chen; Wanning Dai; Yuanyuan Sun; Hechong Yuan; Wen Yang; Jun Meng; Hailong Wang; et al. (Chemical Engineering Journal, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

PCSK9 regulates myocardial ischemia–reperfusion injury through parkin/pink1-mediated autophagy pathway - Guangwei Huang; Hailong Bao; Peng Zhan; Xiyang Lu; Zonggang Duan; Xinlin Xiong; Muzhi Lin; Bing Wang; Hongxin An; Luanda Xiahou; Haiyan Zhou; Zhenhua Luo; et al. (Molecular & Cellular Toxicology, 2024)

Automated identification of protein expression intensity and classification of protein cellular locations in mouse brain regions from immunofluorescence images - Lin-Xia Bao; Zhuo-Ming Luo; Xi-Liang Zhu; Ying-Ying Xu (Medical & Biological Engineering & Computing, 2024)

Imbalance of T follicular helper cell subsets trigger the differentiation of pathogenic B cells in idiopathic membranous nephropathy - Bishun Deng; Huijie Huang; Li Deng; Ziling Zhao; Miao Liu; Haibiao Lin; Xiaowan Wang; Ruimin Tian; Xiaoxin Tu; Anping Peng; Enyu Liang; Kun Bao; et al. (Inflammation Research, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Rational tuning of binding properties of pillar [5] arene-based sensing material by synergistic effect and its application for fluorescent turn-on detection of isoniazid and controlled reversible morphology - Jian-Peng Hu; Qi Zhao; Qi Lin; Hong Yao; You-Ming Zhang; Tai-Bao Wei (Analytica Chimica Acta, 2024)

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Cryopreservation of Goldlined seabream Rhabdosargus sarba (Forsskål, 1775) sperm: CASA observation and enzyme activity evaluation - Jin-Min Pan; Ke-Cheng Zhu; Jun Liu; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Jin-Hui Sun; Dian-Chang Zhang (Aquaculture, 2024)

Toxic effects of nanoplastics and microcystin-LR coexposure on the liver-gut axis of Hypophthalmichthys molitrix - Chaonan Zhang; Feifan Bao; Fei Wang; Zhihao Xue; Daohui Lin (Science of The Total Environment, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

Pt-Zn clusters encapsulated in hierarchical MFI zeolite for efficient propane dehydrogenation - Jinyang Lu; Zhikang Xu; Yuanyuan Yue; Xiaojun Bao; Minggui Lin; Haibo Zhu (Chemical Engineering Journal, 2024)

Development of PEG-mediated genetic transformation and gene editing system of Bryum argenteum as an abiotic stress tolerance model plant - Fengjun Leng; Guiwei Zhou; Ruoyuan Shi; Chengyang Liu; Yirui Lin; Xinqiang Yu; Yanhua Zhang; Xiangxi He; Zhu Liu; Mingming Sun; Fang Bao; Yong Hu; et al. (Plant Cell Reports, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

Study on seismic behavior and collapse risk of super high-rise braced mega frame-core tube structural system - Wenchen Shan; Xuhong Zhou; Xuchuan Lin; Lianjin Bao; Y. Frank Chen (Soil Dynamics and Earthquake Engineering, 2024)

Bacterial interference competition and environmental filtering reduce the fungal taxonomic and functional contribution to plant residue decomposition in anoxic paddy soils - Yuanyuan Bao; Jan Dolfing; Xin Li; Ruirui Chen; Xiaodan Cui; Zhongpei Li; Xiangui Lin; Youzhi Feng (Soil and Tillage Research, 2024)

Synthesis and antifungal activity of 2,4-dihydroxy-5-methylphenyl ethanone derivatives against phytopathogenic fungi in vitro - Lin Jia; Cui-Ping Zhang; Yi Zhu; Chun-Yan Zhao; Zeng-Hui Han; Dong-Bao Hu; Wei Shi (Phytochemistry Letters, 2024)

Surface sediment erosion characteristics and influencing factors in the subaqueous delta of the abandoned Yellow River Estuary - Chaoran Lin; Rui Bao; Longhai Zhu; Rijun Hu; Jinlong Ji; Shilei Yu (Marine Geology, 2024)

Efficient wastewater disinfection using a novel microwave discharge electrodeless ultraviolet system with ozone at an ultra-low dose - Jue-Lin Xiang; Jun-Jie Wang; Zhi-Jing Wu; Bao-Jun Xu; Hai-Sheng Du; Ying Chen; Min Liu; Min-Yong Lee; Wen-Long Wang; Ye Du (Journal of Hazardous Materials, 2024)

NO production of granulocytes associated with antibacterial immune response in Tegillarca granosa - Hongxing Liu; Sixuan Ding; Yingbin Xu; Jie Lin; Kaiqi Jiang; Shanjie Zha; Yongbo Bao (Fish & Shellfish Immunology, 2024)

Genome-wide identification of heat shock protein gene family and their responses to pathogen challenge in Trachinotus ovatus - Yi-Yao Sun; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Ke-Cheng Zhu; Lin Xian; Peng-Hai Zhao; Hui-Yuan Yang; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

An implicit stabilized material point method for modelling coupled hydromechanical problems in two-phase geomaterials - Qin-yang Sang; Yong-lin Xiong; Rong-yue Zheng; Xiao-hua Bao; Guan-lin Ye; Sheng Zhang (Computers and Geotechnics, 2024)

Benzotrithiophene-based covalent organic frameworks as efficient catalysts for artificial photosynthesis of H2O2 in pure water - Mingjie Liu; Peipei He; Hantao Gong; Zhenghua Zhao; Yueming Li; Kai Zhou; Yuemin Lin; Jing Li; Zongbi Bao; Qiwei Yang; Yiwen Yang; Qilong Ren; et al. (Chemical Engineering Journal, 2024)

Mechanochemical synthesis of Ni/MgO dual functional materials at room temperature for CO2 capture and methanation - Zhan-Kuo Guo; Su Gao; Shu-Xiang Xiang; Jin-Peng Wang; Guo-Cui Mao; Hui-Lin Jiang; Bao-Xia Dong; Yun-Lei Teng (Chemical Engineering Journal, 2024)

BioTreasury: a community-based repository enabling indexing and rating of bioinformatics tools - Qi Zhao; Xin Zhou; Jingxing Wu; Jieyi Cai; Xiaoqiong Bao; Lin Tang; Chaoye Wang; Chunlei Liu; Yukai Wang; Yuyan Teng; Mohan Zheng; Weiping Mu; et al. (Science China Life Sciences, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

A ratiometric fluorescent probe based on the FRET platform for the detection of sulfur dioxide derivatives and viscosity - Feng-Ting Liu; Peng-Fei Jiang; Yan-Pu Wang; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Influences of hydrodynamics on microbial community assembly and organic carbon composition of resuspended sediments in shallow marginal seas - Yangli Che; Chaoran Lin; Shen Li; Jiao Liu; Longhai Zhu; Shilei Yu; Nan Wang; Haoshuai Li; Mutai Bao; Yang Zhou; Tonghao Si; Rui Bao (Water Research, 2024)

Identification of large yellow croakers (Larimichthys crocea) scavenger receptor genes: Involvement in immune response to Pseudomonas plecoglossicida infection and hypoxia-exposure experiments - Xuanyang Sun; Ning Bao; Chen Rui; Yadong Xue; Qian Fang; Tianyu Zheng; Ziyang Lin; Xiumei Liu; Xubo Wang (Fish & Shellfish Immunology, 2024)

Yield loss of inferior crop species and its physiological mechanism in a semiarid cereal-legume intercropping system - Wei Wang; Jian-Hua Zhao; Meng-Ying Li; Wei Zhang; Muhammad Maqsood Ur Rehman; Bao-Zhong Wang; Fazal Ullah; Zheng-Guo Cheng; Li Zhu; Jin-Lin Zhang; Hong-Yan Tao; Wen-Ying Wang; et al. (European Journal of Agronomy, 2024)

Cyclic tests and shear resistance design of stiffened corrugated steel plate shear walls - Chen-Bao Wen; Hao-Jun Sun; Ya-Zhou Liu; Yan-Guo Hou; Jia-Qi Zuo; Yan-Lin Guo (Engineering Structures, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Sub-Himalayan Mesozoic-Cenozoic tectonic-stratigraphic properties and deformation features in the western limb of Hazara Kashmir syntaxis, Pakistan - Irshad Hussain; Zuo-Chen Li; Misbah Fida; Jabir Hussain; Wakeel Hussain; Xian-Zhi Pei; Ya-Jie Yang; Meng Wang; Rui-Bao Li; Lei Pei; Hao Lin (Arabian Journal of Geosciences, 2024)

Response of distributions and emissions of summer biogenic sulfur in the Pacific Arctic to enhanced Pacific Water inflow - Cheng‐Xuan Li; Bao‐Dong Wang; Kan Chen; Gui‐Peng Yang; Jian‐Fang Chen; Li‐Na Lin; Zi‐Cheng Wang (Limnology and Oceanography, 2024)
The inflow of warm and nutrient‐rich Pacific Water (PW) through the Bering Strait into the Arctic Ocean is likely to have far‐reaching consequences for the ecosystem and biogenic sulfur cycle in the Earth's sensitive subarctic–arctic region of the Pacific sector, even impacting climate change under global warming scenarios. We performed a detailed biogeochemical study of summer biogenic sulfur cycling from cold (2012) to warm (2014) years in the Bering Strait and the Chukchi Sea, so as to highlight the importance of enhanced Pacific inflow in driving dimethylsulfide (DMS) variability. In the Bering Strait, the enhanced Pacific inflow led to the vertical expansion of the eastern high‐DMS regions due to the vertical extension of Alaska Coastal Water, and the horizontal expansion of the western surface high‐DMS regions due to the westward intrusion of Bering Shelf Water. The enhanced extension of PW potentially stimulated seawater warming, the northward retreat of the ice edge, and the enlargement of sea ice‐free areas in the Chukchi Sea. The northern ice melting zone at 71°N with a bloom of phytoplankton was an area of locally high dimethylsulfoniopropionate concentrations and slow DMS consumption in 2012. A hotspot for dimethylated sulfur compound concentrations and DMS sea–air flux occurred in the convergence region near 67.7°N during 2014, due to enhanced mixing caused by increased Bering Sea Water. Owing to the increased advection of PW during 2012–2014, surface DMS and its emission to the atmosphere increased sharply by threefold in the Chukchi Sea.

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

A multi-objective energy efficiency optimization method of ship under different sea conditions - Lin Ma; Ping Yang; Diju Gao; Chunteng Bao (Ocean Engineering, 2023)

Risk assessment of terrestrial protected areas to extreme wind hazards: A case study in Queensland, Australia - Jinda Qi; Bao-Jie He; Yue Cao; Jiaying Dong; Ervine Shengwei Lin (Landscape and Urban Planning, 2023)

Chitosan composite films based on tea seed oil nano-microcapsules: Antibacterial, antioxidant and physicochemical properties - Qiuya Ji; Zhou Jin; Wanlu Ding; Yating Wu; Chunjie Liu; Kang Yu; Nannan Zhang; Guoguo Jin; Peiran Lu; Di Bao; Lin Mei (Food Packaging and Shelf Life, 2023)

Covalent codeposition modification of reverse osmosis membranes with Noria and zwitterionic copolymers for antifouling in reclaimed water production - Xinyu Zhang; Zhenglun Lin; Daoji Wu; Ming Xie; Jingtao Xu; Xian Bao; Xiaoxiang Cheng; Ying Wang; Feiyong Chen (Desalination, 2023)

Macrogenomic analysis of the effects of aqueous-phase from hydrothermal carbonation of sewage sludge on nitrogen metabolism pathways and associated bacterial communities during composting - Guangchun Shan; Weiguang Li; Jie Liu; Wenbing Tan; Shanshan Bao; Shuncai Wang; Lin Zhu; Xinhao Hu; Beidou Xi (Bioresource Technology, 2023)

SIRT3-dependent mitochondrial redox homeostasis mitigates CHK1 inhibition combined with gemcitabine treatment induced cardiotoxicity in hiPSC-CMs and mice - Jia-Wen Chen; Tian-Kai Shan; Tian-Wen Wei; Qi-Qi Jiang; Chong Du; Ling-Feng Gu; Tong-Tong Yang; Liu-Hua Zhou; Si-Bo Wang; Yu-Lin Bao; Hao Wang; Yong Ji; et al. (Archives of Toxicology, 2023)

Impacts of climate change on herpetofauna diversity in the Qinghai‐Tibetan Plateau - Alex Plimo Karuno; Xue Mi; Youhua Chen; Da‐Hu Zou; Wei Gao; Bao‐Lin Zhang; Wei Xu; Jie‐Qiong Jin; Wen‐Jing Shen; Song Huang; Wei‐Wei Zhou; Jing Che (Conservation Biology, 2023)
Although numerous studies on the impacts of climate change on biodiversity have been published, only a handful are focused on the intraspecific level or consider population‐level models (separate models per population). We endeavored to fill this knowledge gap relative to the Qinghai‐Tibetan plateau (QTP) by combining species distribution modeling (SDMs) with population genetics (i.e., population‐level models) and phylogenetic methods (i.e., phylogenetic tree reconstruction and phylogenetic diversity analyses). We applied our models to 11 endemic and widely distributed herpetofauna species inhabiting high elevations in the QTP. We aimed to determine the influence of environmental heterogeneity on species’ responses to climate change, the magnitude of climate‐change impacts on intraspecific diversity, and the relationship between species range loss and intraspecific diversity losses under 2 shared socioeconomic pathways (SSP245 and SSP585) and 3 future periods (2050s, 2070s, and 2090s). The effects of global climatic change were more pronounced at the intraspecific level (22% of haplotypes lost and 36% of populations lost) than the morphospecies level in the SSP585 climate change scenario. Maintenance of genetic diversity was in general determined by a combination of factors including range changes, species genetic structure, and the part of the range predicted to be lost. This is owing to the fact that the loss and survival of populations were observed in species irrespective of the predicted range changes (contraction or expansion). In the southeast (mountainous regions), climate change had less of an effect on range size (>100% in 3 species) than in central and northern QTP plateau regions (range size

Analysis of volatile organic compounds and potential odour compounds in food contact paperboard using headspace two-dimensional GC-QTOF-MS - Dan Li; Ying Zeng; Zhi-Kang Ye; Han-Ke Li; Yu-Zhe Li; Ben Dong; Qi-Zhi Su; Qin-Bao Lin; Jing Xiao; Huai-Ning Zhong (Food Additives & Contaminants: Part A, 2023)

Preparation and characterization of ZSM-5 molecular sieve using coal gangue as a raw material via solvent-free method: Adsorption performance tests for heavy metal ions and methylene blue - Jida Gao; Qianji Lin; Tingzhi Yang; Yong chao Bao; Juan Liu (Chemosphere, 2023)

Evaluating city road dust emission characteristics with a dynamic method: A case study in Luoyang, China - Jiawei Chen; Hanyang Man; Wenying Cai; Laichang Lin; Xiaoduo Chen; Xiaohan Shao; Yumeng Bao; Bo Zhu; Lizhong Xu (Science of The Total Environment, 2023)

Phenolic glycosides and indole alkaloids isolated from the roots and rhizomes of Clematis chinensis and their anti-inflammatory activity - Hai-Bing Jiang; Si-Yuan Shao; Ya-Zi Wei; Ming-Bao Lin; Shuai Li (Phytochemistry, 2023)

Adaptive learning-based recoil control for deepwater drilling riser systems - Yun Zhang; Bao-Lin Zhang; Qing-Long Han; Xian-Ming Zhang; Ximei Liu; Bin Zhang (Ocean Engineering, 2023)

Non-spherical collapse of a cavitation bubble induced by a rigid filament - Jinghan Pan; Chengxu Tu; Taohou Chen; Xufeng Xia; Pengfei Du; Fubing Bao; Jianzhong Lin (Ocean Engineering, 2023)

Genome architecture and tetrasomic inheritance of autotetraploid potato - Zhigui Bao; Canhui Li; Guangcun Li; Pei Wang; Zhen Peng; Lin Cheng; Hongbo Li; Zhiyang Zhang; Yuying Li; Wu Huang; Mingwang Ye; Daofeng Dong; et al. (Molecular Plant, 2023)

Controllable formation of polydopamine on carbon dots for ultrasensitive detection of alkaline phosphatase and ratiometric fluorescence immunoassay of benzocaine - Shi-Qi Lin; Bao-Zhu Jia; Wei Luo; Hong Wang; Hong-Tao Lei; Wen-Feng Zhang; Zhen-Lin Xu; Lin Luo (Food Chemistry, 2023)

Identification and characterisation of microplastics released from plastic-coated paper cups using micro-Raman spectroscopy - Tianlong Zhang; Jia-Ling Hu; Yipin Duan; Sheng Chen; Dan Li; Ben Dong; Ming-Zhen Mo; Jing Wang; Jian-Guo Zheng; Huai-Ning Zhong; Qin-Bao Lin (Food Control, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Prenatal and postnatal exposure to heavy metals in PM2.5 and autism spectrum disorder - Hao-Hsuan Lin; Chau-Ren Jung; Chuan-Yao Lin; Ya-Chu Chang; Chia-Yun Hsieh; Pei-Chuan Hsu; Bao-Ru Chuang; Bing-Fang Hwang (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

Stretchable textile with ultra-high electromagnetic interference shielding performance based on porous wrinkled conductive network - Tai-Bao Yang; Ji-You Zong; Hao Lin; Ding-Xiang Yan; Jun Lei; Zhong-Ming Li (Chemical Engineering Journal, 2023)

Bifidobacterium spp. as functional foods: A review of current status, challenges, and strategies - Bao-Lin He; Yong Xiong; Teng-Gen Hu; Min-Hua Zong; Hong Wu (Critical Reviews in Food Science and Nutrition, 2023)

Cryopreservation of black seabream (Acanthopagrus schlegelii) sperm - Jin-Min Pan; Ke-Cheng Zhu; Jun Liu; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Jin-Hui Sun; Dian-Chang Zhang (Theriogenology, 2023)

Manipulating critical memory periods to treat psychiatry disorders - Jiahui Deng; Xiao Lin; Yongbo Zheng; Sizhen Su; Xiaoxing Liu; Kai Yuan; Le Shi; Yanping Bao; Lin Lu (Science Bulletin, 2023)

Effect of additional periodic motion on gas-liquid two-phase secondary flow behavior in inclined pipes - Yangyang Bao; Tingxia Ma; Yao Zhang; Lin Wang (Ocean Engineering, 2023)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

Phenotypic screening of novel probiotics with potential anti-neuroinflammation activity based on cell and zebrafish models - Bao-Lin He; Teng-Gen Hu; Hong Wu (Food Bioscience, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

Causal relationships between chronotype and risk of multiple cancers by using longitudinal data and Mendelian randomization analysis - Shanshan Tian; Longtao Huangfu; Sizhi Ai; Junwei Zheng; Le Shi; Wei Yan; Ximei Zhu; Qianwen Wang; Jiahui Deng; Yanping Bao; Suhua Chang; Lin Lu (Science China Life Sciences, 2023)

Genome-wide DNA methylation landscape of four Chinese populations and epigenetic variation linked to Tibetan high-altitude adaptation - Zeshan Lin; Yan Lu; Guoliang Yu; Huajing Teng; Bao Wang; Yajun Yang; Qinglan Li; Zhongsheng Sun; Shuhua Xu; Wen Wang; Peng Tian (Science China Life Sciences, 2023)

Fixation of CO2 by soil fungi: contribution to organic carbon pool and destination of fixed carbon products - Fang Li; Zhong-Jun Jia; Lin Chen; Yan-Lai Han; Yuan-Feng Cai; Brajesh K. Singh; Jia-Bao Zhang (Biology and Fertility of Soils, 2023)

Evidence for the Late Pliocene Aridification in the Eastern Tarim Basin, Northwest China - Hua Zhang; Feng-Lin Lü; Cheng-Lin Liu; Peng-Cheng Jiao; Hui-Jing Yin; Hui Yan; Bao-Cheng Ma; Liang-Liang Zhao; Hong-Chao Liu (Journal of Earth Science, 2023)

Improvement of CYGNSS soil moisture retrieval model considering water and surface temperature - Shuangcheng Zhang; Qinyu Guo; Qi Liu; Zhongmin Ma; Ning Liu; Shengwei Hu; Lin Bao; Xin Zhou; Hebin Zhao; Lifu Wang; Tianhe Wan (Advances in Space Research, 2023)

CAS FGOALS-f3-L Model Datasets for CMIP6 DCPP Experiment - Shuai Hu; Bo Wu; Yiming Wang; Tianjun Zhou; Yongqiang Yu; Bian He; Pengfei Lin; Qing Bao; Hailong Liu; Kangjun Chen; Shuwen Zhao (Advances in Atmospheric Sciences, 2023)
The outputs of the Chinese Academy of Sciences (CAS) Flexible Global Ocean-Atmosphere-Land System (FGOALS-f3-L) model for the decadal climate prediction project (DCPP) of the Coupled Model Intercomparison Project Phase 6 (CMIP6) are described in this paper. The FGOALS-f3-L was initialized through the upgraded, weakly coupled data assimilation scheme, referred to as EnOI-IAU, which assimilates observational anomalies of sea surface temperature (SST) and upper-level (0–1000-m) ocean temperature and salinity profiles into the coupled model. Then, nine ensemble members of 10-year hindcast/forecast experiments were conducted for each initial year over the period of 1960–2021, based on initial conditions produced by three initialization experiments. The hindcast and forecast experiments follow the experiment designs of the Component-A and Component-B of the DCPP, respectively. The decadal prediction output datasets contain a total of 44 monthly mean atmospheric and oceanic variables. The preliminary evaluation indicates that the hindcast experiments show significant predictive skill for the interannual variations of SST in the north Pacific and multi-year variations of SST in the subtropical Pacific and the southern Indian Ocean.

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

Superior performance of a membrane bioreactor through innovative in-situ aeration and structural optimization using computational fluid dynamics - Liguo Shen; Qihang Wu; Qunfeng Ye; Hongjun Lin; Jianzhen Zhang; Cheng Chen; Rong Yue; Jiaheng Teng; Huachang Hong; Bao-Qiang Liao (Water Research, 2023)

Deep removal of fluoride from tungsten smelting wastewater by combined chemical coagulation-electrocoagulation treatment: From laboratory test to pilot test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Meirong Wu; Lei Yang; Huanjun Bao; Jianhua Kang; Haisheng Han; Chenyang Zhang; Wei Sun (Journal of Cleaner Production, 2023)

Investigating the stretchability of doped poly(3-hexylthiophene)-block-poly(butyl acrylate) conjugated block copolymer thermoelectric thin films - Qing-Bao Zheng; Yan-Cheng Lin; Yen-Ting Lin; Yun Chang; Wei-Ni Wu; Jhih-Min Lin; Shih-Huang Tung; Wen-Chang Chen; Cheng-Liang Liu (Chemical Engineering Journal, 2023)

Periodate activation by atomically dispersed Mn on carbon nanotubes for the production of iodate radicals and rapid degradation of sulfadiazine - Jiahui Hu; Yubin Zou; Yin Li; Zehui Yu; Yutian Bao; Lin Lin; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Involvement of IGF1 in endoplasmic reticulum stress contributes to cataract formation through regulating Nrf2/NF-κB signaling - Ruiping Peng; Hongmei Lin; Haocheng Zhu; Yi Zhang; Tiancheng Bao; Weili Li; Juan Deng (Functional & Integrative Genomics, 2023)

Research on carbon footprint measurement and emissions reduction optimization of the beer supply chain in China - Jing Chen; Han Bao; Lin-Ke Pei (Environmental Science and Pollution Research, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Authentication of recycled and virgin polyethylene terephthalate based on UPLC-Q-TOF-MS using non-volatile organic compounds and chemometrics - Tian-Ying Hao; Qin-Bao Lin; Xue-Feng Wu; Si-Liang Wu; Huai-Ning Zhong; Ben Dong; Zhi-Feng Chen; Zhi-Kang Ye; Zhi-Wei Wang; Xiaowen Xu (Food Additives & Contaminants: Part A, 2023)

Bridging the gap between artificial intelligence and mental health - Tangsheng Lu; Xiaoxing Liu; Jie Sun; Yanping Bao; Björn W. Schuller; Ying Han; Lin Lu (Science Bulletin, 2023)

Numerical study of transient flow characteristics of gas-liquid two-phase flow in inclined upward tube under periodic vibration - Lin Wang; Yao Zhang; Yangyang Bao; Tingxia Ma (Ocean Engineering, 2023)

Removal of chemical oxygen demand and ammonia nitrogen from high salinity tungsten smelting wastewater by one-step electrochemical oxidation: From bench-scale test, pilot-scale test, to industrial test - Xiangsong Meng; Ping Zeng; Shangyong Lin; Huanjun Bao; Meirong Wu; Lei Yang; Gaogui Jing; Haisheng Han; Chenyang Zhang; Xiaoyun Jiang; Songlin Wang; Wei Ding; et al. (Journal of Environmental Management, 2023)

Improvement of hydrolysis efficiency and interfacial properties of zein using nanoemulsions prepared by a low energy emulsification method - Jia-Ling He; Bo-Hao Liu; Han-Lin Zhang; Di Xu; Bao-Ming Shi; Ying-Hua Zhang (Food Bioscience, 2023)

Response of sulfur-metabolizing biofilm to external sulfide in element sulfur-based denitrification packed-bed reactor - Hong-Xu Bao; Han-Lin Wang; Shu-Tong Wang; Yi-Lu Sun; Xue-Ning Zhang; Hao-Yi Cheng; Zhi-Min Qian; Ai-Jie Wang (Environmental Research, 2023)

Effect of the aqueous phase from the hydrothermal carbonization of sewage sludge as a moisture regulator on nitrogen retention and humification during chicken manure composting - Guangchun Shan; Weiguang Li; Wenbing Tan; Shanshan Bao; Jie Liu; Shuncai Wang; Lin Zhu; Li Chen; Beidou Xi (Chemical Engineering Journal, 2023)

Peat records of atmospheric environmental changes in China: A brief review and recommendations for future research perspectives - Kunshan Bao; Ting Liu; Minqi Chen; Zhanyi Lin; Jing Zhong; Bigyan Neupane (CATENA, 2023)

Heterogeneous aggregation between microplastics and microalgae: May provide new insights for microplastics removal - Yuanyuan Su; Liu Gao; Licheng Peng; Xiaoping Diao; Shengyou Lin; Ruiqi Bao; Tariq Mehmood (Aquatic Toxicology, 2023)

Enhanced vitamin K2 production by engineered Bacillus subtilis during leakage fermentation - Meng-jie Zhou; Jing Wu; Liu-xiu Hu; Wen-song Hu; Jun-bao Huang; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Zheng-lian Xue; Yan Liu (World Journal of Microbiology and Biotechnology, 2023)

Seamless Prediction in China: A Review - Hong-Li Ren; Qing Bao; Chenguang Zhou; Jie Wu; Li Gao; Lin Wang; Jieru Ma; Yao Tang; Yangke Liu; Yujun Wang; Zuosen Zhao (Advances in Atmospheric Sciences, 2023)

Tracing surface seawater mixing and nutrient transport by 222Rn on the northern coast of Beibu Gulf, China - Hao Wang; Qiangqiang Zhong; Fule Zhang; Suiyuan Chen; Hongyan Bao; Jing Lin; Dekun Huang; Tao Yu (Acta Oceanologica Sinica, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Priming effects of nZVI on carbon sequestration and iron uptake are positively mediated by AM fungus in semiarid agricultural soils - Yu-Miao Yang; Minha Naseer; Ying Zhu; Bao-Zhong Wang; Song Wang; Yue Ma; Xiao-Lin Zhang; Xu-Zhe Zhao; Wen-Ying Wang; Shuang-Guo Zhu; Hong-Yan Tao; You-Cai Xiong (Science of The Total Environment, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

In situ construction of MnIn2S4/Ti3C2TxMXene Schottky junction composites for efficient photoreduction and recovery of U(VI) - Yingjun Wang; Longyu Qiu; Shuangyou Bao; Fenyang Tian; Lin He; Weiwei Yang; Yequn Liu; Yongsheng Yu (Chemical Engineering Journal, 2023)

Improved Bathymetry in the South China Sea from Multisource Gravity Field Elements Using Fully Connected Neural Network - Qianqian Li; Zhenhe Zhai; Qi Li; Lin Wu; Lifeng Bao; Heping Sun (Journal of Marine Science and Engineering, 2023)
Traditional bathymetry inversion methods that rely on an altimetry-derived gravity anomaly (GA) and/or a vertical gravity gradient anomaly (VGG) have been widely used for bathymetry prediction in the South China Sea. However, few studies attempt new methods to combine multisource gravity data to improve the accuracy of the bathymetry. In this study, we introduce a fully connected deep neural network (FC-DNN) to merge GA, VGG, and the deflection of vertical (DOV) to predict the bathymetry in the South China Sea. Single beam sounding depths were used as sample data for neural network training. Independent shipboard depths and GEBCO2023, topo_25.1, and ETOPO2022 models were applied as validation data. The assessment results showed that the FC-DNN model reached a high precision level with an STD of 49.20 m. More than 70% of the differences between the FC-DNN bathymetric model and other depth models were less than 100 m. Furthermore, the spectral analysis results showed that the FC-DNN bathymetry model has stronger energy in medium and short wavelengths than other models, which indicates that additional gravity field element DOVs can recover richer topographic signals in those particular bands.

Hemocyte proliferation is associated with blood color shade variation in the blood clam, Tegillarca granosa - Zexin Yang; Xin He; Hongyu Jin; Dan Su; Zhihua Lin; Hongxing Liu; Yongbo Bao (Aquaculture, 2023)

The therapeutic look up: Stress reduction and attention restoration vary according to the sky-leaf-trunk (SLT) ratio in canopy landscapes - Wei Lin; Chengcheng Zeng; Zhiyi Bao; Hexian Jin (Landscape and Urban Planning, 2023)

Evaluating the aqueous phase obtained from hydrothermal carbonization of municipal sludge as possible liquid fertilizer for plant growth: An analysis of heavy metals and their molecular composition - Guangchun Shan; Weiguang Li; Shanshan Bao; Jie Liu; Lin Zhu; Wenbing Tan (Journal of Cleaner Production, 2023)

Cues of intraguild predators (Harmonia axyridis) and different temperatures alter foraging and oviposition strategies of the parasitoid Aphidius gifuensis - Xing-Lin Yu; Yi Feng; Tong-Xian Liu; Bao-Li Qiu (Journal of Asia-Pacific Entomology, 2023)

An injectable antibacterial hydrogel to regulate ocular immune for endophthalmitis treatment - Zunzhen Ming; Lin Han; Huanhuan Zhu; Meiyu Bao; Qiangyuan Fan; Shaobo Xue; Kesheng Wang; Yue Zhang; Meiling Lu; Chongshun Xu; Qi Wu; Tingting Li; et al. (Chemical Engineering Journal, 2023)

Geostatistical inversion method based on seismic waveform similarity - Xue-Bin Ni; Jia-Jia Zhang; Kang Chen; Guang-Zhi Zhang; Bao-Li Wang; Zhuo-Fan Liu; Ying Lin (Applied Geophysics, 2023)

A historical overview of water quality in the coastal seas of China - Ming Xin; Xia Sun; Lin-Ping Xie; Bao-Dong Wang (Frontiers in Marine Science, 2023)
Using historical data, long-term variations in pollutant sources and water quality in China’s coastal waters over the last three decades are reviewed. The results show that the total area of non-clean water, which reflects state of total water quality, increased rapidly before 2000, but then underwent two stages of decline, with a modest decline by one-quarter between 2001 and 2015, followed by a sharp decline of more than half of that in 2015 since then. Consequently, water quality at present is better than it was at the beginning of the 1990s. The total area of polluted water fluctuated without any trend from the end of the 1990s until 2015, but has declined sharply by nearly two-thirds since 2015, indicating that the water quality in China’s coastal seas has improved substantially. Geographically, the Bohai Sea was the first to see a turning point in water quality, followed by the Yellow Sea and East China Sea, while the South China Sea was the last. The main pollutants that govern the water quality grade and area are dissolved inorganic nitrogen and phosphate as well as petroleum hydrocarbons. As a response to variations in water quality, changes in both the frequency and total area affected by harmful algal blooms were similar to those of water quality over the last three decades, albeit with a slight lag. Analysis showed that variations in water quality were closely related to the land- and sea-sourced pollutant inputs. The combination of shift in the mode of economic growth from high-speed growth to high-quality development and the enforcement of the new, strictest ever Environmental Protection Law resulted in a significant decline of pollutant emissions, inducing a turning point in the water quality in the coastal seas of China in the mid-2010s.

Trade-off between microbial ecophysiological features regulated by soil fertility governs plant residue decomposition - Yuanyuan Bao; Jan Dolfing; Ruirui Chen; Zhongpei Li; Xiangui Lin; Youzhi Feng (Soil and Tillage Research, 2023)

X-ray diffraction and the symmetry of ultrathin crystalline materials between two-dimensional and three-dimensional crystals - Hengrui Ma; Qiaorong Jiang; Zi-Ang Nan; Gen Li; Yanyan Jia; Ruoxin Ning; Jia-Bao Ji; Zhenming Cao; Linzhe Lü; Huiqi Li; Sheng Dai; Haixin Lin; et al. (Science Bulletin, 2023)

Assessment of future eco-hydrological regime and uncertainty under climate changes over an alpine region - Lin Wang; Jianyun Zhang; Zhangkang Shu; Zhenxin Bao; Junliang Jin; Cuishan Liu; Ruimin He; Yanli Liu; Guoqing Wang (Journal of Hydrology, 2023)

Starch structural reasons for the effects of SSIIIa deficiency on the textural and digestive properties of cooked rice - Zhongwei Zhang; Yining Ying; Lin Zhang; Gaoxing Dai; Guofu Deng; Jinsong Bao; Feifei Xu (Journal of Cereal Science, 2023)

Improving flavor of summer Keemun black tea by solid-state fermentation using Cordyceps militaris revealed by LC/MS-based metabolomics and GC/MS analysis - Yuan-Yuan Zhang; Peng Zhang; Miao-Miao Le; Yan Qi; Zi Yang; Feng-Lin Hu; Tie-Jun Ling; Guan-Hu Bao (Food Chemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Salinibacterium sedimenticola sp. nov., Isolated from Tidal Flat Sediment - Chun-Yan Lu; Lei Dong; Shuai Li; Wen-Hui Lian; Zhi-Liang Lin; Zhuo-Huan Zheng; Lei Gao; Bao-Zhu Fang; Wen-Jun Li (Current Microbiology, 2023)

Vibration for enhancement of electrochemical analysis of biomolecules in a droplet on the rough surface of a disposable working electrode - Ya-Hong Wang; Xiang-Yun Lin; Ye Cheng; Hua Wang; Wu Liu; Xiang-Kai Zhuge; Xiao-Lei Huo; Ning Bao (Analytica Chimica Acta, 2023)

A cross-sectional study of the association between heavy metals and pan-cancers associated with sex hormones in NHANES 1999–2018 - Hai-ming Cao; Ya-zhu Yang; Bao-yi Huang; Yunzhe Zhang; Yu Wu; Zi Wan; Lin Ma (Environmental Science and Pollution Research, 2023)

Physiological response and photosynthetic recovery to an extreme drought: Evidence from plants in a dry-hot valley savanna of Southwest China - Da Yang; Yang-Si-Ding Wang; Qin Wang; Yan Ke; Yun-Bing Zhang; Shi-Bao Zhang; Yong-Jiang Zhang; Nate G. McDowell; Jiao-Lin Zhang (Science of The Total Environment, 2023)

Removal of residual benzohydroxamic acid-lead complex from mineral processing wastewater by metal ion combined with gangue minerals - Xiangsong Meng; Min Jiang; Shangyong Lin; Zhiyong Gao; Haisheng Han; Mengjie Tian; Chenyang Zhang; Ruohua Liu; Meirong Wu; Huanjun Bao; Wei Sun (Journal of Cleaner Production, 2023)

High-efficiency removal of Cs (I) by vermiculite/zinc hexacyanoferrate (II) composite from aqueous solutions - Tianya Dai; Jinpeng Feng; Jiann-Yang Hwang; Yangyang Bao; Chenhui Gao; Zeping Wang; Wei Mo; Xiujuan Su; Hongfei Lin (Journal of Environmental Chemical Engineering, 2023)

Effects of persulfate-assisted hydrothermal treatment of municipal sludge on aqueous phase characteristics and phytotoxicity - Guangchun Shan; Weiguang Li; Yujie Zhou; Shanshan Bao; Lin Zhu; Wenbing Tan (Journal of Environmental Sciences, 2023)

Oxidative modification of malondialdehyde influences the structure and emulsification properties of egg yolk high-density lipoprotein - Yang Tian; Songyi Lin; Pengfei Jiang; Guangshun Jiang; Zhijie Bao (Food Bioscience, 2023)

Polystyrene microplastics induce endoplasmic reticulum stress, apoptosis and inflammation by disrupting the gut microbiota in carp intestines - Fuhan Wang; Qirui Zhang; Jie Cui; Bowen Bao; Xian Deng; Lin Liu; Meng-yao Guo (Environmental Pollution, 2023)

Vascular cells responses to controlled surface structure and properties of bacterial nanocellulose artificial blood vessel after mercerization - Gaoquan Hu; Luhan Bao; Geli Li; Lin Chen; Feng F. Hong (Carbohydrate Polymers, 2023)

Can Eurasia Experience a Cold Winter under a Third-Year La Niña in 2022/23? - Fei Zheng; Bo Wu; Lin Wang; Jingbei Peng; Yao Yao; Haifeng Zong; Qing Bao; Jiehua Ma; Shuai Hu; Haolan Ren; Tingwei Cao; Renping Lin; et al. (Advances in Atmospheric Sciences, 2023)

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

The changes of chemical molecular components in soil organic matter are associated with fungus Mortierella capitata K. - Fang Li; Lin Chen; Zhan-Hui Zhao; Yue Li; Hai-You Yu; Yi Wang; Jia-Bao Zhang; Yan-Lai Han (Soil and Tillage Research, 2023)

Effect of biomass retention time on performance and fouling of a stirred membrane photobioreactor - Bao-Trong Dang; Xuan-Thanh Bui; Thanh-Tin Nguyen; Huu Hao Ngo; Long D. Nghiem; Ky-Phuong-Ha Huynh; Thi-Kim-Quyen Vo; Thi-Dieu-Hien Vo; Chitsan Lin; Shiao-Shing Chen (Science of The Total Environment, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

China Brain Project: from bench to bedside - Xiaoxing Liu; Teng Gao; Tangsheng Lu; Yanping Bao; Gunter Schumann; Lin Lu (Science Bulletin, 2023)

Recoil suppression of deepwater drilling riser systems via static output feedback control with memory - Bao-Lin Zhang; Zhihui Cai; Wei Zhang; Feng-Bin Pang; Qing-Long Han; Xian-Ming Zhang (Ocean Engineering, 2023)

OSA-linear dextrin enhances the compactness of pea protein isolate nanoparticles: Increase of high internal phase emulsions stability - Xiao-Long Li; Wen-Jie Liu; Bao-Cai Xu; Bao Zhang; Wu Wang; Dong-Lin Su (Food Chemistry, 2023)

Non-targeted screening for contaminants derived from food contact water-borne coatings and risk assessment based on (Q)SAR matrix - Qing-Hua Yang; Qin-Bao Lin; Jia Liao; Hong-Sheng Ma; Xiao-Fen Wei; Yue Wang; Xiaowen Xu (Food Packaging and Shelf Life, 2023)

Influence of plants on anammox process in constructed Wetland: Irrelevance, inhibition or enhancement - Jie Li; Lin Liu; Yu-Ming Zheng; Lin Ma; Quan-Bao Zhao; Xuan Wang; Chao-Xiang Liu (Chemical Engineering Journal, 2023)

An internally damped inertial platform for marine gravimetry and a test case in the South China Sea - Pengfei Wu; Lin Wu; Lifeng Bao; Long Wang; Bo Wang; Danling Tang (Journal of Oceanology and Limnology, 2023)

A marine gravimeter based on electromagnetic damping and its tests in the South China Sea - Pengfei Wu; Lin Wu; Lifeng Bao; Long Wang; Bo Wang; Danling Tang (Journal of Oceanology and Limnology, 2023)

Stem cell-derived exosomes for chronic wound repair - Peng Mi; Jia-Lin Liu; Bao-Ping Qi; Ben-Mei Wei; Cheng-Zhi Xu; Lian Zhu (Cell and Tissue Research, 2023)

Estimating the true spatial resolution of satellite altimeter-derived gravity field models with shipborne data in the South China Sea - Bo Wang; Lin Wu; Qian-qian Li; Li-feng Bao; Yong Wang (Applied Geophysics, 2023)

Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Shi-Mei Liang; Xing Zhai; Cheng-Xuan Li; Ming Xin; Ping Sun; Xuan-Li Liu; Lin Liu; Bao-Dong Wang (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.

A critical thermal transition driving spring phenology of Northern Hemisphere conifers - Jian‐Guo Huang; Yaling Zhang; Minhuang Wang; Xiaohan Yu; Annie Deslauriers; Patrick Fonti; Eryuan Liang; Harri Mäkinen; Walter Oberhuber; Cyrille B. K. Rathgeber; Roberto Tognetti; Václav Treml; et al. (Global Change Biology, 2023)
Despite growing interest in predicting plant phenological shifts, advanced spring phenology by global climate change remains debated. Evidence documenting either small or large advancement of spring phenology to rising temperature over the spatio‐temporal scales implies a potential existence of a thermal threshold in the responses of forests to global warming. We collected a unique data set of xylem cell‐wall‐thickening onset dates in 20 coniferous species covering a broad mean annual temperature (MAT) gradient (−3.05 to 22.9°C) across the Northern Hemisphere (latitudes 23°–66° N). Along the MAT gradient, we identified a threshold temperature (using segmented regression) of 4.9 ± 1.1°C, above which the response of xylem phenology to rising temperatures significantly decline. This threshold separates the Northern Hemisphere conifers into cold and warm thermal niches, with MAT and spring forcing being the primary drivers for the onset dates (estimated by linear and Bayesian mixed‐effect models), respectively. The identified thermal threshold should be integrated into the Earth‐System‐Models for a better understanding of spring phenology in response to global warming and an improved prediction of global climate‐carbon feedbacks.

Gravity disturbance compensation for dual-axis rotary modulation inertial navigation system - Panpan Zhang; Lin Wu; Lifeng Bao; Bo Wang; Hui Liu; Qianqian Li; Yong Wang (Frontiers in Marine Science, 2023)
Gravity disturbance compensation is an important technique for improving the positioning accuracy of high-precision inertial navigation systems (INS). Aiming at the current problems of the resolution of gravity compensation background field and the robustness of gravity compensation algorithm are insufficient for gravity compensation. In this study, the error and frequency characteristics of INS caused by gravity disturbances are investigated. The gravity disturbance with a spatial resolution of 1’ × 1’ from a high-precision satellite altimetry marine gravity field model is preliminarily introduced into the initial alignment and pure INS calculation to implement the gravity compensation of the dual-axis rotary modulation INS. Detailed calculation results show that the east gravity disturbance affects the north attitude, and the north gravity disturbance affects the east attitude in the initial alignment. In the pure INS calculation, the horizontal gravity disturbance causes a navigation error in the form of Schuler oscillation. The INS navigation error caused by horizontal gravity disturbance is mainly affected by its amplitude; however, the horizontal gravity disturbance accuracy from the satellite altimetry model for INS gravity compensation can be ignored in practice. In addition, for low-speed underwater vehicles, the influence of high-frequency gravity disturbance signals on the INS position shows an increasing trend. Finally, the effectiveness of the gravity compensation achieved by the horizontal gravity disturbance from the satellite altimeter model is confirmed by a dynamic shipborne test. The positioning accuracy of the rotary modulation INS is maximally improved by approximately 17.9% after the horizontal gravity disturbance is compensated simultaneously in the pure INS calculation and the initial alignment.

Simulating future land use by coupling ecological security patterns and multiple scenarios - Wenbin Nie; Bin Xu; Fan Yang; Yan Shi; Bintao Liu; Renwu Wu; Wei Lin; Hui Pei; Zhiyi Bao (Science of The Total Environment, 2023)

Marine environmental monitoring with unmanned vehicle platforms: Present applications and future prospects - Shuyun Yuan; Ying Li; Fangwen Bao; Haoxiang Xu; Yuping Yang; Qiushi Yan; Shuqiao Zhong; Haoyang Yin; Jiajun Xu; Ziwei Huang; Jian Lin (Science of The Total Environment, 2023)

Evaluating the human use efficiency of urban built environment and their coordinated development in a spatially refined manner - Yi Bao; Zhou Huang; Linna Li; Han Wang; Jiayuan Lin; Gang Liu (Resources, Conservation and Recycling, 2023)

Metal ions synergize with gangue minerals to remove residual sodium oleate from mineral processing wastewater - Xiangsong Meng; Min Jiang; Shangyong Lin; Zhiyong Gao; Haisheng Han; Li Wang; Chenyang Zhang; Ruohua Liu; Huanjun Bao; Meirong Wu; Gaogui Jing; Wei Sun (Journal of Cleaner Production, 2023)

Heat transfer behavior of an immersed tube with sCO2 working fluid in a hot fluidized bed at high pressure - Yu Huang; Xu Bao; Yuanqiang Duan; Lin Li; Dongdong Fang; Yueming Wang; Lunbo Duan (Fuel, 2023)

Construction of a novel efficient Z-scheme BiVO4/EAQ heterojunction for the photocatalytic inactivation of antibiotic-resistant pathogens: Performance and mechanism - Zitao Lin; Shengjun Ye; Yanbin Xu; Xiaojun Lin; Zuhui Qin; Junyue Bao; Huishi Peng (Chemical Engineering Journal, 2023)

Analysis of microplastics released from plastic take-out food containers based on thermal properties and morphology study - Jia-Ling Hu; Yipin Duan; Huai-Ning Zhong; Qin-Bao Lin; Tianlong Zhang; Chuang-Chuang Zhao; Sheng Chen; Ben Dong; Dan Li; Jing Wang; Ming-Zhen Mo; Jie Chen; et al. (Food Additives & Contaminants: Part A, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Energy and nutrient recovery by spent mushroom substrate-assisted hydrothermal carbonization of sewage sludge - Guangchun Shan; Weiguang Li; Shanshan Bao; Xinhao Hu; Jie Liu; Lin Zhu; Wenbing Tan (Waste Management, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Observer-based dynamic optimal recoil controller design for deepwater drilling riser systems - Wei Zhang; Bao-Lin Zhang; Qing-Long Han; Yue-Ting Sun; Yan Ji; Dawei Zhang; Xian-Ming Zhang (Ocean Engineering, 2023)

A novel all-natural (collagen+pectin)/chitosan aqueous two-phase microcapsule with improved anthocyanin loading capacity - Zhenyang Jiang; Shaojie Zhao; Zhiying Fan; Chengying Zhao; Lin Zhang; Dan Liu; Yuming Bao; Jinkai Zheng (Food Hydrocolloids, 2023)

Large-flake graphene-modified biochar for the removal of bisphenol S from water: rapid oxygen escape mechanism for synthesis and improved adsorption performance - Yurong Gao; Zheng Fang; Wenhui Lin; Hanbo Chen; Amit Bhatnagar; Jianhong Li; Yanhai Xie; Yanping Bao; Junfeng Chen; Hongting Zhao; Jun Meng; Wenfu Chen; et al. (Environmental Pollution, 2023)

Dual-response and lysosome-targeted fluorescent probe for viscosity and sulfur dioxide derivatives - Feng Li; Bang-Zhao Zhou; Wen Yao; Shou-Kang Sun; Jun-Ying Miao; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2023)

Dynamic Analysis and Extreme Response Evaluation of Lifting Operation of the Offshore Wind Turbine Jacket Foundation Using a Floating Crane Vessel - Mingsheng Chen; Guibo Yuan; Chun Bao Li; Xianxiong Zhang; Lin Li (Journal of Marine Science and Engineering, 2022)
The jacket is the most widely-used fixed foundation for offshore wind turbines due to its superior strength and low installation cost in relatively deep waters. Floating crane vessels are commonly used to install jacket foundations. However, the dynamic coupling between the jacket and the floating vessel might generate complex dynamic responses under wave action. The complexity of the multi-body system requires comprehensive time-domain simulations and statistical analysis to obtain reliable results, especially for the evaluation of the operational safety of offshore lift installations of a jacket foundation. In this context, this study performs numerical simulations and statistical analyses to predict the extreme responses and the preliminary allowable sea states for guiding the lowering operation of a jacket using a floating crane vessel. First, ANSYS-AQWA is used to obtain the hydrodynamic coefficients of the vessel in the frequency domain. A nonstationary time-domain simulation of jacket lowering with winches is performed to identify several preliminary critical vertical positions of the jacket from the time series in an irregular wave. The extreme responses of a target probability are evaluated by the extreme distribution model after a large number of steady-state time-domain simulations of the critical vertical positions in irregular waves. The most critical vertical position is determined from three preliminary critical vertical positions by comparing the extreme responses. Eigenvalue analysis and spectrum analysis of the most critical vertical position of the jacket are carried out to find the natural periods of the system and the dynamic coupling characteristics between different components. The influence of wave direction, significant wave height, and spectrum peak period on the dynamic responses are also analyzed in the most critical vertical position. Furthermore, the optimal wave direction is determined as the head sea. Preliminary allowable sea states are derived by comparing the calculated dynamic amplification coefficient with the defined operational criteria.

Research status, challenges and future prospects of renewable synthetic fuel catalysts for CO2 photocatalytic reduction conversion - Yujun Chen; Bin Guan; Xingze Wu; Jiangfeng Guo; Zeren Ma; Jinhe Zhang; Xing Jiang; Shibo Bao; Yiyan Cao; Chengdong Yin; Di Ai; Yuxuan Chen; et al. (Environmental Science and Pollution Research, 2022)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

PCSK9 Knockdown Can Improve Myocardial Ischemia/Reperfusion Injury by Inhibiting Autophagy - Guangwei Huang; Xiyang Lu; Zonggang Duan; Kai Zhang; Lei Xu; Hailong Bao; Xinlin Xiong; Muzhi Lin; Chao Li; Yunquan Li; Haiyan Zhou; Zhenhua Luo; et al. (Cardiovascular Toxicology, 2022)

Prenylaromadendrane-type diterpenoids from the gum resin of Boswellia sacra flueck and their cytotoxic effects - Jia-Jia Wang; Xin-Yue Suo; Hao-Ran Sun; Xue Wang; Ming-Bao Lin; Jin-Hua Wang; Jian-Dong Jiang; Teng-Fei Ji (Natural Product Research, 2022)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Enhanced M-CSF/CSF1R Signaling Closely Associates with PrPSc Accumulation in the Scrapie-Infected Cell Line and the Brains of Scrapie-Infected Experimental Rodents - Ying Xia; Cao Chen; Jia Chen; Chao Hu; Wei Yang; Lin Wang; Lian Liu; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Qi Shi; Zhi-Bao Chen; et al. (Molecular Neurobiology, 2022)

Integrated RNA-seq and RNAi Analysis of the Roles of the Hsp70 and SP Genes in Red-Shell Meretrix meretrix Tolerance to the Pathogen Vibrio parahaemolyticus - Yun Zheng; Shanjie Zha; Weifeng Zhang; Yinghui Dong; Jing He; Zhihua Lin; Yongbo Bao (Marine Biotechnology, 2022)

Temporal and spatial variation in water quality in the Yangtze Estuary from 2012 to 2018 - Lin Chong; Bao Li; Zhilin Sun; Chunhong Hu; Xin Meng; Jian Gao (Environmental Science and Pollution Research, 2022)

Progress of Selenium Deficiency in the Pathogenesis of Arthropathies and Selenium Supplement for Their Treatment - Huan Deng; Haobiao Liu; Zhihao Yang; Miaoye Bao; Xue Lin; Jing Han; Chengjuan Qu (Biological Trace Element Research, 2022)

Wind erodibility indices of aeolian sandy soils impacted by different vegetation restoration: a case study from the Shannan valley of the Yarlung Zangbo River - Bao-jun Zhang; Dong-hong Xiong; Lin Liu; Yong-fa Tang (Journal of Mountain Science, 2022)

Determination of the main alkaloids and their insecticidal activity of extract of Areca catechu nuts against Plutella xylostella - Rui Liu; Minyuan Zheng; Lin Yuan; Zhonglin Liu; Jianqiang Bao; Wenchao Yang; Hailong Kong; Jianguo Feng (International Journal of Tropical Insect Science, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Impacts of Mercury Exposure Levels and Sources on the Demethylation of Methylmercury Through Human Gut Microbiota - Xian-Feng Yang; Shao-Chen Yang; Fu-Li Wen; Lin Feng; Bo Meng; Hai-Yan Hu; Bao-Lin Wang; Jun Li; Alexandre J. Poulain; Ping Li (Bulletin of Environmental Contamination and Toxicology, 2022)

circRERE regulates the expression of GBX2 through miR-1299 and ZC3H13/N6-methyladenosine (m6A) to promote growth and invasion of hepatocellular carcinoma cells - Yong-hua Lin; Bao-yan Zhang; Zhi-chao Chen (Journal of Biosciences, 2022)

Stachybotranes A–D, phenylspirodrimanes from the wetland fungus Stachybotrys chartarum with cytotoxic activities - Yan-Ru Bao; Han-Lin Feng; Xin-Sheng Yao (Natural Product Research, 2022)

Experimental study of energy and frequency characteristics of acoustic emissions induced from tensile and shear cracks in tunnel rockburst process - Yan-Bo Zhang; Peng Liang; Xu-Long Yao; Lin Sun; Bao-Zhu Tian; Xiang-Xin Liu (European Journal of Environmental and Civil Engineering, 2022)

Construction and Biological Evaluation of Multiple Modification Hollow Mesoporous Silicone Doxorubicin Nanodrug Delivery System - Mengru Hu; Wenjing Zhang; Weidong Chen; Yunna Chen; Qianqian Huang; Qianqian Bao; Tongyuan Lin; Lei Wang; Shantang Zhang (AAPS PharmSciTech, 2022)

Sesquiterpene lactones from Carpesium abrotanoides L. and their activity in inducing protective autophagy - Bao-Jia Yang; Juan Wang; Zheng-Quan Zeng; Xu Yang; Ai-Ying Huang; Xiao-Jiang Hao; Xiao Ding; Shun-Lin Li (Natural Product Research, 2022)

Near-Optimal Control for Offshore Structures with Nonlinear Energy Sink Mechanisms - Wei Chen; Xingyu Du; Bao-Lin Zhang; Zhihui Cai; Zhongqiang Zheng (Journal of Marine Science and Engineering, 2022)
To improve the safety and reliability of offshore structures subject to wave loading, the active vibration control problem is always one of significant issues in the field of ocean engineering. This paper deals with the near–optimal control problem of offshore structures with a nonlinear energy sink (NES) mechanism. By taking the dominant vibration mode of the offshore structure with the NES into account, a nonlinear dynamic model of the steel–jacket structure subject to wave loading is presented first. Then, using the parameter perturbation approach to solve a nonlinear two–point boundary value problem, an NES–based optimal controller with the form of infinite series sum is presented to suppress the vibration of the offshore structure. Third, an iteration algorithm is provided to obtain the near–optimal controller. Simulation results demonstrate that the NES–based near–optimal controller can mitigate the oscillation amplitude of offshore structures significantly. Moreover, the NES–based optimal controller outperforms the one based on active tuned mass damper.

Advanced Treatment Technologies for the Removal of Organic Chemical Sunscreens from Wastewater: a Review - ‬Huu-Tuan Tran; Bao-Trong Dang; Le Thi Thu Thuy; Hong-Giang Hoang; Xuan-Thanh Bui; Van-Giang Le; Chitsan Lin; Minh-Ky Nguyen; Kim-Qui Nguyen; Phuong-Thao Nguyen; Quach An Binh; Thi-Phuong Thuy Bui (Current Pollution Reports, 2022)

PrPSc Inhibition and Cellular Protection of DBL on a Prion-Infected Cultured Cell via Multiple Pathways - Wei Yang; Cao Chen; Jia Chen; Ying Xia; Chao Hu; Lin Wang; Yue-Zhang Wu; Qi Shi; Zhi-Bao Chen; Xiao-Ping Dong (Molecular Neurobiology, 2022)

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Effects of Microplastics on Microbial Community in Zhanjiang Mangrove Sediments - Meng-Meng Chen; Fang-Hong Nie; Aftab Qamar; Di-hua Zhu; Yao Hu; Min Zhang; Qing-Lang Song; Hong-Ying Lin; Zhi-Bao Chen; Su-Qing Liu; Jin-Jun Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Soil phosphorus drives plant trait variations in a mature subtropical forest - Erqian Cui; Ruiling Lu; Xiaoni Xu; Huanfa Sun; Yang Qiao; Jiaye Ping; Shuying Qiu; Yihua Lin; Jiehuan Bao; Yutong Yong; Zemei Zheng; Enrong Yan; et al. (Global Change Biology, 2022)
Earth system models are implementing soil phosphorus dynamic and plant functional traits to predict functional changes in global forests. However, the linkage between soil phosphorus and plant traits lacks empirical evidence, especially in mature forests. Here, we examined the soil phosphorus constraint on plant functional traits in a mature subtropical forest based on observations of 9943 individuals from 90 species in a 5‐ha forest dynamic plot and 405 individuals from 15 species in an adjacent 10‐year nutrient‐addition experiment. We first confirmed a pervasive phosphorus limitation on subtropical tree growth based on leaf N:P ratios. Then, we found that soil phosphorus dominated multidimensional trait variations in the 5‐ha forest dynamic plot. Soil phosphorus content explained 44% and 53% of the variance in the traits defining the main functional space across species and communities, respectively. Lastly, we found much stronger phosphorus effects on most plant functional traits than nitrogen at both species and community levels in the 10‐year nutrient‐addition experiment. This study provides evidence for the consistent pattern of soil phosphorus constraint on plant trait variations between the species and community levels in a mature evergreen broadleaf forest in the East Asian monsoon region. These findings shed light on the predominant role of soil phosphorus on plant functional trait variations in mature subtropical forests, providing new insights for models to incorporate soil phosphorus constraint in predicting future vegetation dynamics.

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Geochemistry of rhodonite in the Luziyuan Pb − Zn skarn deposit, Southwestern China - Yulong Yang; Lin Ye; Wei Gao; Tan Bao; Zhenli Li; Yusi Hu; Chen Wei (Mineralogy and Petrology, 2022)

miR-29 family inhibited the proliferation and migration of lung cancer cells by targeting SREBP-1 - Lin Lin; Yongxia Bao; Miao Tian; Qiu Ren; Wei Zhang (Molecular & Cellular Toxicology, 2022)

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

Haloprofundus salilacus sp. nov., Haloprofundus halobius sp. nov. and Haloprofundus salinisoli sp. nov.: three extremely halophilic archaea isolated from salt lake and saline soil - Si-Ya Li; Yu-Jie Xin; Chen-Xi Bao; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Autophagy of hepatic stellate cell induced by Clonorchis sinensis - Bao Zheng; Zhiyan Gao; Liumei Liang; Yunyu Lu; Yongting Kong; Wanting Chen; Keying Lin; Wanqi Chen; Jingying Mai; Yanwen Li; Changling Ma (Molecular Biology Reports, 2022)

Bioactive compounds derived from the marine-derived fungus MCCC3A00951 and their influenza neuraminidase inhibition activity in vitro and in silico - Shun-Zhi Liu; Feng-Ming He; Yan-lin Bin; Chu-Fang Li; Bao-Ying Xie; Xi-Xiang Tang; Ying-Kun Qiu (Natural Product Research, 2021)

Identification and Expression Characterization of the Smad3 Gene and SNPs Associated with Growth Traits in the Hard Clam (Meretrix meretrix) - Lulu Fu; Qiudie Chi; Yongbo Bao; Hanhan Yao; Zhihua Lin; Yinghui Dong (Fishes, 2021)
It has been demonstrated that the sekelsky mothers against decapentaplegic homolog 3 (Smad3) plays an important role in the growth and development of vertebrates. However, little is known about the association between the Smad3 gene and the growth traits of mollusks. In this study, Smad3 from the hard clam Meretrix meretrix (Mm-Smad3) was cloned, characterized, and screened for growth-related single nucleotide polymorphisms (SNPs) in its exons. The full-length cDNA of Mm-Smad3 was 1938 bp, encoding a protein with 428 amino acid residues. The protein sequence included an MH1 (27–135 aa) and MH2 domain (233–404 aa). Promoter analysis showed that the promoter sequence of Mm-Smad3 was 2548 bp, and the binding sites of Pit-1a, Antp, Hb, and other transcription factors are related to the growth and development of hard clams. The phylogenetic tree was divided into two major clusters, including mollusks and vertebrate. The expression level of Mm-Smad3 was predominantly detected in the mantle and foot, while extremely less expression was observed in the digestive gland. The low expression level of Mm-Smad3 was detected at the stages of unfertilized mature eggs, fertilized eggs, four-cell embryos, blastula, gastrulae, trochophore, and D-shaped larvae, whereas an opposite trend was observed regarding the highest expression at the umbo larvae stage (p T, c.660 C > T, c.792 A > T) were significantly related to the growth traits of clam (p

Evolutionary characteristics and phylogeny of cotton chloroplast tRNAs - Ning Wang; Wan-Lin Dong; Xiao-Jing Zhang; Tong Zhou; Xiao-Juan Huang; Bao-Guo Li; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Planta, 2021)

Silencing of H19 alleviates oxygen–glucose deprivation/reoxygenation-triggered injury through the regulation of the miR-1306-5p/BCL2L13 axis - Yuxing Huang; Lisha Deng; Lin Zeng; Shanlin Bao; Kun Ye; Chengxun Li; Xiaolin Hou; Yuan Yao; Dingjun Li; Zhen Xiong (Metabolic Brain Disease, 2021)

On the Diurnal Cycle of Heavy Rainfall over the Sichuan Basin during 10–18 August 2020 - Rudi Xia; Yali Luo; Da-Lin Zhang; Mingxin Li; Xinghua Bao; Jisong Sun (Advances in Atmospheric Sciences, 2021)
A sustained heavy rainfall event occurred over the Sichuan basin in southwest China during 10–18 August 2020, showing pronounced diurnal rainfall variations with nighttime peak and afternoon minimum values, except on the first day. Results show that the westward extension of the anomalously strong western Pacific subtropical high was conducive to the maintenance of a southerly low-level jet (LLJ) in and to the southeast of the basin, which favored continuous water vapor transport and abnormally high precipitable water in the basin. The diurnal cycle of rainfall over the basin was closely related to the periodic oscillation of the LLJ in both wind speed and direction that was caused by the combination of inertial oscillation and terrain thermal forcing. The nocturnally enhanced rainfall was produced by moist convection mostly initiated during the evening hours over the southwest part of the basin where high convective available potential energy with moister near-surface moist air was present. The convective initiation took place as cold air from either previous precipitating clouds from the western Sichuan Plateau or a larger-scale northerly flow met a warm and humid current from the south. It was the slantwise lifting of the warm, moist airflow above the cold air, often facilitated by southwest vortices and quasi-geostrophic ascent, that released the convective instability and produced heavy rainfall.

Termite mound formation reduces the abundance and diversity of soil resistomes - Zhen‐Zhen Yan; Qing‐Lin Chen; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Yong‐Guan Zhu; Ji‐Zheng He; Hang‐Wei Hu (Environmental Microbiology, 2021)
Summary Termites are pivotal ecosystem engineers in tropical and subtropical habitats, where they construct massive nests (‘mounds’) that substantially modify soil properties and promote nutrient cycling. Yet, little is known about the roles of termite nesting activity in regulating the spread of antimicrobial resistance (AMR), one of the major Global Health challenges. Here, we conducted a large‐scale (> 1500 km) investigation in northern Australia and found distinct resistome profiles in termite mounds and bulk soils. By profiling a wide spectrum of ARGs, we found that the abundance and diversity of antibiotic resistance genes (ARGs) were significantly lower in termite mounds than in bulk soils ( P P

Precipitation increases the abundance of fungal plant pathogens in Eucalyptus phyllosphere - Qing‐Lin Chen; Hang‐Wei Hu; Zhen‐Zhen Yan; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Yong‐Guan Zhu; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Understanding the current and future distributions of plant pathogens is critical to predict the plant performance and related economic benefits in the changing environment. Yet, little is known about the roles of environmental drivers in shaping the profiles of fungal plant pathogens in phyllosphere, an important habitat of microbiomes on Earth. Here, using a large‐scale investigation of Eucalyptus phyllospheric microbiomes in Australia and the multiple linear regression model, we show that precipitation is the most important predictor of fungal taxonomic diversity and abundance. The abundance of fungal plant pathogens in phyllosphere exhibited a positive linear relationship with precipitation. With this empirical dataset, we constructed current and future atlases of phyllosphere plant pathogens to estimate their spatial distributions under different climate change scenarios. Our atlases indicate that the abundance of fungal plant pathogens would increase especially in the coastal regions with up to 100‐fold increase compared with the current abundance. These findings advance our understanding of the distributions of fungal plant pathogens in phyllospheric microbiomes under the climate change, which can improve our ability to predict and mitigate their impacts on plant productivity and economic losses.

Characterization and identification of SFDC ‐1, a novel AmpC ‐type β‐lactamase in Serratia fonticola - Xu Dong; Peiyao Zhang; Kexin Zhou; Jialei Liang; Qiaoling Li; Xueya Zhang; Danying Zhou; Wei Lu; Zhewei Sun; Hongmao Liu; Junwan Lu; Xi Lin; et al. (Environmental Microbiology, 2021)
Summary The clinical and environmental infections caused by AmpC β‐lactamases have been increasingly reported recently. In this study, we characterize the novel chromosome‐encoded AmpC β‐lactamase SFDC‐1 identified in Serratia fonticola strain R28, which was isolated from a rabbit raised on a farm in southern China. SFDC‐1 shared the highest amino acid identity of 79.6% with the functionally characterized AmpC β‐lactamase gene bla YRC‐1 , although it had highly homologous functionally uncharacterized relatives in the same species from different sources, including some of the clinical significance. The cloned bla SFDC‐1 exhibited resistance to a broad spectrum of β‐lactam antibiotics, including most cephalosporins with the highest resistance to ampicillin, cefazolin and ceftazidime, with increased MIC levels ≥128‐fold compared with the control strains. The purified SFDC‐1 showed catalytic activities against β‐lactams with the highest catalytic activity to cefazolin. The genetic context of bla SFDC‐1 and its relatives was conserved in the chromosome, and no mobile genetic elements were found surrounding them.

Molecular Characterization and Expression of the LAP3 Gene and Its Association with Growth Traits in the Blood Clam Tegillarca granosa - Hanhan Yao; Fuzhen Ren; Yongbo Bao; Yinghui Dong; Zhihua Lin (Fishes, 2021)
Leucine aminopeptidase 3 (LAP3) is a metallopeptidase that cleaves N-terminal residues and is involved in protein maturation and degradation. In this study, we characterized the leucine aminopeptidase 3 (LAP3) gene from Tegillarca granosa (Tg-LAP3 for short), which appeared to consist of 15,731 nucleotides encoding 530 amino acids. We identified 12 introns and 13 exons in the Tg-LAP3 gene, suggesting a highly conserved genomic structure. The proximal promoter sequence consists of 1922 bps with a typical TATA box structure, which is the general structural characteristic of core promoters in eukaryotes. We found two functional domains in the Tg-LAP3 protein, including an N-terminal domain (41–174aa) and a peptidase_M17 catalytic domain (209–522aa). Multiple alignment showed that Tg-LAP3 shares 73.4% identity with LAP3 of Mizuhopecten yessoensis and 55.2–70.7% identity with LAP3 of other species. Quantitative analysis of Tg-LAP3 in embryos/larvae and adult tissues indicated that the highest expression occurred in eyebot larva, with limited expression in other stages; among tissues, the highest expression was found in the liver (p G, g.-1123C > T, and g.-1304C > A) in the proximal promoter were successfully typed, but there was no significant difference in growth traits (body weight, shell length, shell width, and shell height) among these genotypes. The results of our study demonstrate the functional roles of the Tg-LAP3 gene and provide valuable information for molecular marker-assisted selection (MAS) of the blood clam.

Characterization and Function Analysis of β, β-carotene-9′, 10′-oxygenase 2 (BCDO2) Gene in Carotenoid Metabolism of the Red Shell Hard Clam (Meretrix meretrix) - Lulu Fu; Heming Shi; Wenfang Dai; Hanhan Yao; Yongbo Bao; Zhihua Lin; Yinghui Dong (Frontiers in Marine Science, 2021)
The relationship between carotenoid and shellfish shell color has gained increasing attention. β, β-carotene-9′,10′-oxygenase 2 (BCDO2) is a key enzyme in animal carotenoid metabolism, and its accumulation affects the change in body color, as demonstrated in mammals, birds, and fish. However, it is unclear whether BCDO2 is involved in the formation of the red shell color of clam. To explore the molecular structure and biological function of BCDO2 gene in the process of carotenoids accumulation, in this study, the BCDO2 from hard clam Meretrix meretrix (designated as Mm-BCDO2 ) was cloned and characterized, and the single-nucleotide polymorphisms (SNPs) associated with shell color were detected. The results of qRT-PCR indicated that Mm-BCDO2 gene was expressed in all six tested tissues, and the expression of mantle was significantly higher than other tissues ( P < 0.05). The association analysis identified 20 SNPs in the exons of Mm-BCDO2 , among which three loci (i.e., c.984A > C, c.1148C > T, and c.1187A > T) were remarkably related ( P < 0.05) to the shell color of clam. The western blot analysis revealed that the expression level of Mm-BCDO2 in the mantle of red shell clams was stronger than that of white shell clams ( P < 0.05). Further, the immunofluorescence analysis indicated that the single-layer columnar cells at the edge of the mantle were the major sites for the Mm-BCDO2 secretion. This study explored the potential impacts of BCDO2 gene on the shell color of M. meretrix , which provided a theoretical basis for a better understanding of the important role of BCDO2 in carotenoid metabolism.

Efficiently immobilizing uranium (VI) by oxidized carbon foam - Hongliang Bao; Chunyu Xie; Ling Han; Zenghui Yue; Yuan Qian; Linjuan Zhang; Zi-Jian Li; Huangjie Lu; Jian Lin; Jian-Qiang Wang (Environmental Science and Pollution Research, 2021)

Seasonal variation of flavonoid metabolites in leaves of Liquidambar formosana ‘Nanlinhong’ trees revealed by UPLC-ESI–MS/MS - Jiu-Xin Lai; Fu-Rong Lin; Ping Huang; Wen-Ying Guo; Lie-Bao Han; Yong-Qi Zheng (Brazilian Journal of Botany, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Optimal estimates for dissolved and suspended particulate material fluxes in the Yangtze River, China - Tiantian Yang; Lin Zhang; Yao Yue; Bao Qian; Yuhong Zeng; Xiaofeng Zhang (Environmental Science and Pollution Research, 2021)

Present in-situ stress distribution characteristics of strike-slip in SH Oilfield, Tarim Basin - Teng Zhao; Wenge Hu; Rui Zhao; Min Yang; Qiang Wang; Huixi Lin; Zhixing Ru; Dian Bao; Fei Cao (Arabian Journal of Geosciences, 2021)

Secondary Structural Transformation of Bovine Lactoferricin Affects Its Antibacterial Activity - Jie Pei; Lin Xiong; Pengjia Bao; Min Chu; Ping Yan; Xian Guo (Probiotics and Antimicrobial Proteins, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Genome-wide identification and expression analysis of the MADS-box transcription factor family in Camellia sinensis - Zai-Bao Zhang; Yuan-Jin Jin; Hou-Hong Wan; Lin Cheng; Zhi-Guo Feng (Journal of Applied Genetics, 2021)

Termite mounds reduce soil microbial diversity by filtering rare microbial taxa - Qing‐Lin Chen; Hang‐Wei Hu; Zhen‐Zhen Yan; Chao‐Yu Li; Bao‐Anh Thi Nguyen; Yong Zheng; Yong‐Guan Zhu; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Termites are ubiquitous insects in tropical and subtropical habitats, and some of them construct massive nests (‘mounds’), which substantially promote substrate heterogeneity by altering soil properties. Yet, the role of termite nesting process in regulating the distribution and diversity of soil microbial communities remains poorly understood, which introduces uncertainty in predictions of ecosystem functions of termite mounds in a changing environment. Here, by using amplicon sequencing, we conducted a survey of 134 termite mounds across >1500 km in northern Australia and found that termite mounds significantly differed from bulk soils in the microbial diversity and community compositions. Compared with bulk soils, termite nesting process decreased the microbial diversity and the relative abundance of rare taxa. Rare taxa had a narrower habitat niche breadth than dominant taxa and might be easier to be filtered by the potential intensive microbial competition during the nesting processes. We further demonstrated that the shift in pH induced by termite nesting process was a major driver shaping the microbial community profiles in termite mounds. Together, our work provides novel evidence that termite nesting is an important process in regulating soil microbial diversity, which advances our understanding of the functioning of termite mounds.

Three new acenaphthene derivatives from rhizomes of Musa basjoo and their cytotoxic activity - Li Jiang; Bao Zhang; Yang Wang; Jia Sun; Xue Ma; Guangcheng Wang; Sihong Fu; Changhu Lin; YongJun Li (Natural Product Research, 2021)

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Prestack seismic stochastic inversion based on statistical characteristic parameters - Wang Bao-Li; Lin Ying; Zhang Guang-Zhi; Yin Xing-Yao; Zhao Chen (Applied Geophysics, 2021)

Cu2+ Inhibits the Peroxidase and Antibacterial Activity of Homodimer Hemoglobin From Blood Clam Tegillarca granosa by Destroying Its Heme Pocket Structure - Sufang Wang; Xiaopei Yu; Shunqin Zhang; Hongyu Jin; Zhongfa Chen; Zhihua Lin; Yongbo Bao (Frontiers in Marine Science, 2021)
Beyond its role as an oxygen transport protein, the homodimer hemoglobin of blood clam Tegillarca granosa (Tg-HbI) has been found to possess antibacterial activity. However, the mechanism of antibacterial activity of Tg-HbI remain to be investigated. In this study, we investigated the effects of Cu 2+ on the structure, peroxidase activity, and antibacterial ability of Tg-HbI. Tg-HbI was significantly inactivated by Cu 2+ in a non-competitive inhibition manner, following first-order reaction kinetics. The Spectroscopy results showed that Cu 2+ changed the iron porphyrin ring and the coordination of heme with proximal histidine of Tg-HbI, and increased the hydrophobicity of heme pocket. We found that proline could stabilize the heme pocket structure of Tg-HbI, hence, protect peroxidase activity and antimicrobial activity of Tg-HbI against damage by Cu 2+ . Our results suggest that Cu 2+ inhibits the peroxidase and antibacterial activity of Tg-HbI by destroying its heme pocket structure and Tg-HbI probably plays an antibacterial role through its peroxidase activity. This result could provide insights into the antibacterial mechanism of Tg-HbI.

Soil anti-scourability enhanced by herbaceous species roots in a reservoir water level fluctuation zone - Wen-xiu Xu; Ling Yang; Yu-hai Bao; Jin-lin Li; Jie Wei (Journal of Mountain Science, 2021)

Datasets for the CMIP6 Scenario Model Intercomparison Project (ScenarioMIP) Simulations with the Coupled Model CAS FGOALS-f3-L - Shuwen Zhao; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Yuyang Guo; Lijuan Hua; Kangjun Chen; Xiaowei Wang (Advances in Atmospheric Sciences, 2021)
The datasets for the tier-1 Scenario Model Intercomparison Project (ScenarioMIP) experiments from the Chinese Academy of Sciences (CAS) Flexible Global Ocean-Atmosphere-Land System model, finite-volume version 3 (CAS FGOALS-f3-L) are described in this study. ScenarioMIP is one of the core MIP experiments in phase 6 of the Coupled Model Intercomparison Project (CMIP6). Considering future CO 2 , CH 4 , N 2 O and other gases’ concentrations, as well as land use, the design of ScenarioMIP involves eight pathways, including two tiers (tier-1 and tier-2) of priority. Tier-1 includes four combined Shared Socioeconomic Pathways (SSPs) with radiative forcing, i.e., SSP1-2.6, SSP2-4.5, SSP3-7.0 and SSP5-8.5, in which the globally averaged radiative forcing at the top of the atmosphere around the year 2100 is approximately 2.6, 4.5, 7.0 and 8.5 W m −2 , respectively. This study provides an introduction to the ScenarioMIP datasets of this model, such as their storage location, sizes, variables, etc. Preliminary analysis indicates that surface air temperatures will increase by about 1.89°C, 3.07°C, 4.06°C and 5.17°C by around 2100 under these four scenarios, respectively. Meanwhile, some other key climate variables, such as sea-ice extension, precipitation, heat content, and sea level rise, also show significant long-term trends associated with the radiative forcing increases. These datasets will help us understand how the climate will change under different anthropogenic and radiative forcings.

Genetic diversity and population structure in bearded iris cultivars derived from Iris × germanica L. and its related species I. pumila L., I. variegata L., I. pallida Lam. - Fengtong Li; Ye Sun; Chungui Liu; Yuan Yuan; Lin Zheng; Xiulan Chen; Jianzhong Bao (Genetic Resources and Crop Evolution, 2020)

Development of 85 SNP markers for the endangered plant species Prunus mira (Rosaceae) based on restriction site-associated DNA sequencing (RAD-seq) - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Yu-e Bai (Conservation Genetics Resources, 2020)

Wind speed inversion and in-orbit assessment of the imaging altimeter on Tiangong-2 space station - Youguang Zhang; Qingliu Bao; Mingsen Lin; Shuyan Lang (Acta Oceanologica Sinica, 2020)

Simulation and Improvements of Oceanic Circulation and Sea Ice by the Coupled Climate System Model FGOALS-f3-L - Yuyang Guo; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Bo An; Shuwen Zhao; Lijuan Hua (Advances in Atmospheric Sciences, 2020)

Overview of the CMIP6 Historical Experiment Datasets with the Climate System Model CAS FGOALS-f3-L - Yuyang Guo; Yongqiang Yu; Pengfei Lin; Hailong Liu; Bian He; Qing Bao; Shuwen Zhao; Xiaowei Wang (Advances in Atmospheric Sciences, 2020)
The three-member historical simulations by the Chinese Academy of Sciences Flexible Global Ocean-Atmosphere-Land System model, version f3-L (CAS FGOALS-f3-L), which is contributing to phase 6 of the Coupled Model Intercomparison Project (CMIP6), are described in this study. The details of the CAS FGOALS-f3-L model, experiment settings and output datasets are briefly introduced. The datasets include monthly and daily outputs from the atmospheric, oceanic, land and sea-ice component models of CAS FGOALS-f3-L, and all these data have been published online in the Earth System Grid Federation (ESGF, https://esgf-node.llnl.gov/projects/cmip6/ ). The three ensembles are initialized from the 600th, 650th and 700th model year of the preindustrial experiment (piControl) and forced by the same historical forcing provided by CMIP6 from 1850 to 2014. The performance of the coupled model is validated in comparison with some recent observed atmospheric and oceanic datasets. It is shown that CAS FGOALS-f3-L is able to reproduce the main features of the modern climate, including the climatology of air surface temperature and precipitation, the long-term changes in global mean surface air temperature, ocean heat content and sea surface steric height, and the horizontal and vertical distribution of temperature in the ocean and atmosphere. Meanwhile, like other state-of-the-art coupled GCMs, there are still some obvious biases in the historical simulations, which are also illustrated. This paper can help users to better understand the advantages and biases of the model and the datasets.

Tyrosine Hydroxylase Gene Polymorphisms Contribute to Opioid Dependence and Addiction by Affecting Promoter Region Function - Jun-lin Liu; Shao-qing Li; Feng Zhu; Yu-xiang Zhang; Ya-nan Wu; Jing-si Yang; Bao Zhang; Chun-xia Yan (NeuroMolecular Medicine, 2020)

Enhanced Biosorption of Sb(III) onto Living Rhodotorula mucilaginosa Strain DJHN070401: Optimization and Mechanism - Chang-sheng Jin; Ren-jian Deng; Bo-zhi Ren; Bao-lin Hou; Andrew S. Hursthouse (Current Microbiology, 2020)

Development and characterization of 72 SNP markers in Armeniaca sibirica based on transcriptomics - Wenquan Bao; Dun Ao; Tana Wuyun; Lin Wang; Shulan Bai; Yu-e Bai (Conservation Genetics Resources, 2020)

Functional community composition has less environmental variability than taxonomic composition in straw-degrading bacteria - Yuanyuan Bao; Zhiying Guo; Ruirui Chen; Meng Wu; Zhongpei Li; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2020)

Emergence of a hybrid PKS‐NRPS secondary metabolite cluster in a clonal population of the rice blast fungus Magnaporthe oryzae - Zhenhui Zhong; Lianyu Lin; Huakun Zheng; Jiandong Bao; Meilian Chen; Limei Zhang; Wei Tang; Daniel J. Ebbole; Zonghua Wang (Environmental Microbiology, 2020)
Summary Secondary metabolites (SMs) are crucial for fungi and vary in function from beneficial antibiotics to pathogenicity factors. To generate diversified SMs that enable different functions, SM‐coding regions rapidly evolve in fungal genomes. However, the driving force and genetic mechanism of fungal SM diversification in the context of host‐pathogen interactions remain largely unknown. Previously, we grouped field populations of the rice blast fungus Magnaporthe oryzae (syn: Pyricularia oryzae ) into three major globally distributed clades based on population genomic analyses. Here, we characterize a recent duplication of an avirulent gene‐containing SM cluster, ACE1, in a clonal M . oryzae population (Clade 2). We demonstrate that the ACE1 cluster is specifically duplicated in Clade 2, a dominant clade in indica rice‐growing areas. With long‐read sequencing, we obtained chromosome‐level genome sequences of four Clade 2 isolates, which displayed differences in genomic organization of the ACE1 duplication process. Comparative genomic analyses suggested that the original ACE1 cluster experienced frequent rearrangement in Clade 2 isolates and revealed that the new ACE1 cluster is located in a newly formed and transposable element‐rich region. Taken together, these results highlight the frequent mutation and expansion of an avirulent gene‐containing SM cluster through transposable element‐mediated whole‐cluster duplication in the context of host‐pathogen interactions.

Delayed Fuzzy Output Feedback H∞ Control for Offshore Structures - Hua-Nv Feng; Bao-Lin Zhang; Qing Li; Gong-You Tang (Journal of Marine Science and Engineering, 2020)
Vibration damping of jacket platforms is among the significant issues in marine science and engineering, and the design of active vibration control schemes is very important to ensure the stability and safety of the jacket platforms against external loadings. This paper provides three fuzzy output feedback H ∞ controllers of the jacket platforms for irregular wave forces. By considering time-varying masses of jacket platforms, a Takagi-Sugeno (T-S) fuzzy dynamic model of the structure is established. Then fuzzy output feedback H ∞ control schemes are developed via using output signals of the platform with current and/or are delayed. Several existence conditions of fuzzy output feedback H ∞ controllers are derived. Simulation results demonstrate that the fuzzy output feedback H ∞ control strategies are remarkable to suppress the vibration of structure. Moreover, by choosing proper delayed output information of the system, the presented delayed fuzzy output feedback H ∞ control schemes outperform the conventional fuzzy output feedback H ∞ control approach.

bHLH genes polymorphisms and their association with growth traits in the Pacific oyster Crassostrea gigas - Na Chen; Li Li; Chenghua Li; Zhihua Lin; Jie Meng; Sheng Liu; Kai Song; Yongbo Bao (Journal of Oceanology and Limnology, 2020)

A Simple Approach to the Toxicity Prediction of Anilines and Phenols Towards Aquatic Organisms - Jules Muhire; Bao Qiong Li; Hong Lin Zhai; Sha Sha Li; Jia Ying Mi (Archives of Environmental Contamination and Toxicology, 2020)

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

High prevalence and viremia of human pegivirus 2 in the HIV-infected population in Honghe Prefecture, Yunnan Province - Tianyi Li; Shixing Tang; Yingying Su; Zuoyi Bao; Xiaolin Wang; Yongjian Liu; Hanping Li; Jingwan Han; Zhichao Pei; Zhengwei Wan; Hang Fan; Yigang Tong; et al. (Archives of Virology, 2020)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Validation of micrografting to analyze compatibility, shoot growth, and root formation in micrografts of kiwifruit (Actinidia spp.) - Wen-Wu Bao; Xiao-Chen Zhang; A-Lin Zhang; Lei Zhao; Qiao-Chun Wang; Zhan-De Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

NRG1–ErbB4 signaling promotes functional recovery in a murine model of traumatic brain injury via regulation of GABA release - Weike Deng; Fei Luo; Bao-ming Li; Lin Mei (Experimental Brain Research, 2019)

An extra insertion of tandem repeat sequence in African swine fever virus, China, 2019 - Shengqiang Ge; Yutian Liu; Lin Li; Qinghua Wang; Jinming Li; Weijie Ren; Chunju Liu; Jingyue Bao; Xiaodong Wu; Zhiliang Wang (Virus Genes, 2019)

Climate warming alters subsoil but not topsoil carbon dynamics in alpine grassland - Juan Jia; Zhenjiao Cao; Chengzhu Liu; Zhenhua Zhang; Li Lin; Yiyun Wang; Negar Haghipour; Lukas Wacker; Hongyan Bao; Thorston Dittmar; Myrna J. Simpson; Huan Yang; et al. (Global Change Biology, 2019)
Subsoil contains more than half of soil organic carbon (SOC) globally and is conventionally assumed to be relatively unresponsive to warming compared to the topsoil. Here, we show substantial changes in carbon allocation and dynamics of the subsoil but not topsoil in the Qinghai‐Tibetan alpine grasslands over 5 years of warming. Specifically, warming enhanced the accumulation of newly synthesized ( 14 C‐enriched) carbon in the subsoil slow‐cycling pool (silt‐clay fraction) but promoted the decomposition of plant‐derived lignin in the fast‐cycling pool (macroaggregates). These changes mirrored an accumulation of lipids and sugars at the expense of lignin in the warmed bulk subsoil, likely associated with shortened soil freezing period and a deepening root system. As warming is accompanied by deepening roots in a wide range of ecosystems, root‐driven accrual of slow‐cycling pool may represent an important and overlooked mechanism for a potential long‐term carbon sink at depth. Moreover, given the contrasting sensitivity of SOC dynamics at varied depths, warming studies focusing only on surface soils may vastly misrepresent shifts in ecosystem carbon storage under climate change.

Correction to: Occurrence of 25 pharmaceuticals in Taihu Lake and their removal from two urban drinking water treatment plants and a constructed wetland - Xia-Lin Hu; Yi-Fan Bao; Jun-Jian Hu; You-Yu Liu; Da-Qiang Yin (Environmental Science and Pollution Research, 2019)

Fractal characterization of sediment particle size distribution in the water-level fluctuation zone of the Three Gorges Reservoir, China - Jin-lin Li; Yu-hai Bao; Jie Wei; Xiu-bin He; Qiang Tang; Jean de Dieu Nambajimana (Journal of Mountain Science, 2019)

Extensive changes in gene expression and alternative splicing due to homoeologous exchange in rice segmental allopolyploids - Zhibin Zhang; Tiansi Fu; Zhijian Liu; Xutong Wang; Hongwei Xun; Guo Li; Baoxu Ding; Yuzhu Dong; Xiuyun Lin; Karen A. Sanguinet; Bao Liu; Ying Wu; et al. (Theoretical and Applied Genetics, 2019)

Spatial Distribution of Organophosphorus and Brominated Flame Retardants in Surface Water, Sediment, Groundwater, and Wild Fish in Chengdu, China - Lin Hou; Jingyan Jiang; Zhiwei Gan; YuanYuan Dai; Ping Yang; Yan Yan; Sanglan Ding; Shijun Su; Xiaoming Bao (Archives of Environmental Contamination and Toxicology, 2019)

The Anti-bacterial and Anti-adherent Effects of Pentraxin-3 on Porcine Kidney Epithelial PK15 Cells Against Staphylococcus aureus Infection - Bao-Hong Lee; Wei-Hsuan Hsu; Cheng-Hui Lin (International Journal of Peptide Research and Therapeutics, 2019)

Development and validation of nomogram estimating post-surgery hospital stay of lung cancer patients: relevance for predictive, preventive, and personalized healthcare strategies - Xiang-Lin Hu; Song-Tao Xu; Xiao-Cen Wang; Jin-Long Luo; Dong-Ni Hou; Xiao-Min Zhang; Chen Bao; Dong Yang; Yuan-Lin Song; Chun-Xue Bai (EPMA Journal, 2019)

Bacterial communities involved directly or indirectly in the anaerobic degradation of cellulose - Yuanyuan Bao; Jan Dolfing; Baozhan Wang; Ruirui Chen; Miansong Huang; Zhongpei Li; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2019)

Sulfide Rb-Sr and Zircon U-Pb Dating of the ~825 Ma Liujiaping Cu-Zn deposit in the Northwestern Yangtze Block (China) and its tectonic implications - Yan-Ping Su; Bao-Lin Zhang; Hui-Zhong Li; Ya-Na Miao; Xiao-Li Shen (International Geology Review, 2019)

Anthropogenic impacts in the Changbai Mountain region of NE China over the last 150 years: geochemical records of peat and altitude effects - Kunshan Bao; Guoping Wang; Lin Jia; Wei Xing (Environmental Science and Pollution Research, 2019)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

Experimental and numerical analyses on working performance of a high arch dam with deep-seated joints: Yebatan arch dam, China - Wen Zhang; Yuan Chen; Bao-quan Yang; Lin Zhang; Chong Zhang; Xiao-qiang Liu (Arabian Journal of Geosciences, 2019)

Ornithinimicrobium cavernae sp. nov., an actinobacterium isolated from a karst cave - Ling-Yu Zhang; Hong Ming; Xiao-Lin Meng; Bao-Zhu Fang; Jian-Yu Jiao; Nimaichand Salam; Xiao-Tong Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2019)

Evolutionary history of the scorpionfly Dicerapanorpa magna (Mecoptera, Panorpidae) - Gui‐Lin Hu; Yuan Hua; Paul D. N. Hebert; Bao‐Zhen Hua (Zoologica Scripta, 2019)
Climate changes can have fundamental impacts on the distributional patterns of montane species, and range shifts frequently lead to allopatric divergence followed by the establishment of secondary contact zones. Many European and North American organisms have retreated to southern refugia during glacial periods and colonized northward during postglacial periods, but little is known about the evolutionary response of cold‐adapted insects to Pleistocene climate changes in eastern Asia. The scorpionfly Dicerapanorpa magna (Chou), with cold temperate habitat preference and weak dispersal ability, provides a good model system to explore how climate changes have influenced the distribution and divergence of cold‐adapted insects in eastern Asia. This study reconstructed the demographic dynamics and evolutionary history of D. magna with phylogeographic approaches, and predicted the species’ suitable areas under the Last Glacial Maximum (LGM) and current scenarios with the ecological niche modelling analysis. The mitochondrial cytochrome c oxidase subunit I resolved three phylogenetic lineages in D. magna dating back to Pleistocene, corresponding well with the geographically isolated Qinling, Bashan and Minshan Mountains. The ecological niche modelling recovered the suitable habitats for D. magna were the Qinling and Bashan Mountains under LGM and current conditions. The three lineages of D. magna might be in a process of incipient speciation, and likely derived their current distribution from separate glacial origins, followed by vicariance and divergence.

RETRACTED ARTICLE: Tetraspanin 1 inhibits TNFα-induced apoptosis via NF-κB signaling pathway in alveolar epithelial cells - Lawei Yang; Yahong Wang; Zhanchun Pan; Shenglan Gao; Bao’an Zou; Ziying Lin; Dehui Feng; Changmei HuangFu; Gang Liu (Inflammation Research, 2018)

The complete mitochondrial genome of Shigaste humped cattle (Bos taurus) - Xian Guo; Jie Pei; Lin Xiong; Pengjia Bao; Yanbin Zhu; Basang Wangdui; Xiaoyun Wu; Min Chu; Ping Yan; Xuezhi Ding (Conservation Genetics Resources, 2018)

Rapid classification of virgin and recycled EPS containers by Fourier transform infrared spectroscopy and chemometrics - Xue-Chao Song; Qin-Bao Lin; Yi-Cai Zhang; Zhong Li; Yu Zeng; Zhi-Feng Chen (Food Additives & Contaminants: Part A, 2018)

Endogenous Hydrogen Sulfide Promotes Apoptosis via Mitochondrial Pathways in the Livers of Broilers with Selenium Deficiency Exudative Diathesis Disease - Shu-fang Zheng; Rong-kun Bao; Qiao-jian Zhang; Sheng-chen Wang; Hong-jin Lin (Biological Trace Element Research, 2018)

Drift analysis of MH370 debris in the southern Indian Ocean - Jia Gao; Lin Mu; Xianwen Bao; Jun Song; Yang Ding (Frontiers of Earth Science, 2018)

The complete mitochondrial genome of Zhangmu cattle (Bos taurus) - Xian Guo; Pengjia Bao; Lin Xiong; Yanbin Zhu; Basang Wangdui; Xiaoyun Wu; Xuezhi Ding; Jie Pei; Ping Yan (Conservation Genetics Resources, 2018)

Complete mitochondrial genome of Anxi cattle (Bos taurus) - Xian Guo; Xuezhi Ding; Xiaoyun Wu; Pengjia Bao; Lin Xiong; Ping Yan; Jie Pei (Conservation Genetics Resources, 2018)

Multiscale analyses on a massive immigration process of Sogatella furcifera (Horváth) in south-central China: influences of synoptic-scale meteorological conditions and topography - Qiu-Lin Wu; John K. Westbrook; Gao Hu; Ming-Hong Lu; Wan-Cai Liu; Gregory A. Sword; Bao-Ping Zhai (International Journal of Biometeorology, 2018)

Taraxasterol suppresses the growth of human liver cancer by upregulating Hint1 expression - Tianhao Bao; Yang Ke; Yifan Wang; Weiwei Wang; Yuehua Li; Yan Wang; Xiang Kui; Qixin Zhou; Han Zhou; Cheng Zhang; Dongming Zhou; Lin Wang; et al. (Journal of Molecular Medicine, 2018)

Mechanisms of influence of invasive grass litter on germination and growth of coexisting species in California - Bao-Ming Chen; Carla M. D’Antonio; Nicole Molinari; Shao-Lin Peng (Biological Invasions, 2018)

Aneuploidization under segmental allotetraploidy in rice and its phenotypic manifestation - Ying Wu; Yue Sun; Shuai Sun; Guo Li; Jie Wang; Bin Wang; Xiuyun Lin; Meng Huang; Zhiyun Gong; Karen A. Sanguinet; Zhiwu Zhang; Bao Liu (Theoretical and Applied Genetics, 2018)

Cabergoline versus bromocriptine for the treatment of giant prolactinomas: A quantitative and systematic review - Hai Yan Huang; Shao Jian Lin; Wei Guo Zhao; Zhe Bao Wu (Metabolic Brain Disease, 2018)

Interaction of two shallow non-circular tunnels with imperfect interfaces subjected to shear waves - He-Xin Jin; Xue-Qian Fang; Yang Wang; Bao-Lin Wang (European Journal of Environmental and Civil Engineering, 2018)

Atg7-Mediated Autophagy Is Involved in the Neural Crest Cell Generation in Chick Embryo - Guang Wang; En-ni Chen; Chang Liang; Jianxin Liang; Lin-rui Gao; Manli Chuai; Andrea Münsterberg; Yongping Bao; Liu Cao; Xuesong Yang (Molecular Neurobiology, 2018)

The complete mitochondrial genome of Odorrana hainanensis (Anura: Ranidae) - Yongjie Huang; Wei Zhao; Xinkang Bao; Jiabin Lu; Fengtang Wang; Dandan Liu; Yinghua Lin (Conservation Genetics Resources, 2018)

Selenium Supplementation Changes the Ion Profile in the Pancreas of Chickens Treated with Cadmium - Rongkun Bao; Xinyue Wang; Shufang Zheng; Qiaojian Zhang; Hongjin Lin; Shu Li (Biological Trace Element Research, 2018)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

Modification of rock mass strength assessment methods and their application in geotechnical engineering - Daming Lin; Kaiyang Wang; Kun Li; Wantong He; Weixing Bao; Renmao Yuan; Yanjun Shang (Bulletin of Engineering Geology and the Environment, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Segmental allotetraploidy generates extensive homoeologous expression rewiring and phenotypic diversity at the population level in rice - Yue Sun; Ying Wu; Chunwu Yang; Shuai Sun; Xiuyun Lin; Lixia Liu; Chunming Xu; Jonathan F. Wendel; Lei Gong; Bao Liu (Molecular Ecology, 2017)
Allopolyploidization, that is, concomitant merging and doubling of two or more divergent genomes in a common nucleus/cytoplasm, is known to instantly alter genomewide transcriptome dynamics, a phenomenon referred to as “transcriptomic shock.” However, the immediate effects of transcriptomic alteration in generating phenotypic diversity at the population level remain underinvestigated. Here, we employed the MassARRAY‐based Sequenom platform to assess and compare orthologous, allelic and homoeologous gene expression status in two tissues (leaf and root) of a set of randomly chosen individuals from populations of parental rice subspecies ( indica and japonica ), in vitro “hybrids” (parental mixes), reciprocal F1 hybrids and reciprocal tetraploids at the 5th‐selfed generation (S5). We show that hybridization and whole genome duplication ( WGD ) have opposing effects on allelic and homoeologous expression in the F1 hybrids and tetraploids, respectively. Whereas hybridization exerts strong attenuating effects on allelic expression differences in diploid hybrids, WGD augments the intrinsic parental differences and generates extensive and variable homoeolog content which triggers diversification in expression patterning among the tetraploid plants. Coupled with the vast phenotypic diversity observed among the tetraploid individuals, our results provide experimental evidence in support of the notion that allopolyploidy catalyses rapid phenotypic diversification in higher plants. Our data further suggest that largely stochastic homoeolog content reshuffling rather than alteration in total expression level may be an important feature of evolution in young segmental allopolyploids, which underlies rapid expression diversity at the population level.

The Effect of Sodium Fluoride on Cell Apoptosis and the Mechanism of Human Lung BEAS-2B Cells In Vitro - Jun Ying; Jie Xu; Liping Shen; Zhijie Mao; Jingchen Liang; Shuangxiang Lin; Xinyan Yu; Ruowang Pan; Chunxia Yan; Shengbin Li; Qiyu Bao; Peizhen Li (Biological Trace Element Research, 2017)

An ocean current inversion accuracy analysis based on a Doppler spectrum model - Qingliu Bao; Youguang Zhang; Mingsen Lin; Peng Gong (Acta Oceanologica Sinica, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Adjuvant effects mediated by the carbohydrate recognition domain of Agrocybe aegerita lectin interacting with avian influenza H9N2 viral surface glycosylated proteins - Li-bao Ma; Bao-yang Xu; Min Huang; Lv-hui Sun; Qing Yang; Yi-jie Chen; Ya-lin Yin; Qi-gai He; Hui Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Two new flavans from the roots of Dianella ensifolia (L.) DC - Ben-Qin Tang; Shu-Sheng Huang; Ye-Er Liang; Jian-Bo Sun; Yan Ma; Bao Zeng; Simon Ming-Yuen Lee; Jian-Lin Lu (Natural Product Research, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Molecular dynamics simulation of three plastic additives’ diffusion in polyethylene terephthalate - Bo Li; Zhi-Wei Wang; Qin-Bao Lin; Chang-Ying Hu (Food Additives & Contaminants: Part A, 2017)

Superoxide generated in the chloroplast stroma causes photoinhibition of photosystem I in the shade-establishing tree species Psychotria henryi - Wei Huang; Ying-Jie Yang; Jiao-Lin Zhang; Hong Hu; Shi-Bao Zhang (Photosynthesis Research, 2017)

HCV core inhibits hepatocellular carcinoma cell replicative senescence through downregulating microRNA-138 expression - Tzu-Yue Shiu; Yu-Lueng Shih; An-Chieh Feng; Hsuan-Hwai Lin; Shih-Ming Huang; Tien-Yu Huang; Chung-Bao Hsieh; Wei-Kuo Chang; Tsai-Yuan Hsieh (Journal of Molecular Medicine, 2017)

Occurrence of 25 pharmaceuticals in Taihu Lake and their removal from two urban drinking water treatment plants and a constructed wetland - Xia-Lin Hu; Yi-Fan Bao; Jun-Jian Hu; You-Yu Liu; Da-Qiang Yin (Environmental Science and Pollution Research, 2017)
Pharmaceuticals in drinking water sources have raised significant concerns due to their persistent input and potential human health risks. The seasonal occurrence of 25 pharmaceuticals including 23 antibiotics, paracetamol (PAR), and carbamazepine (CMZ) in Taihu Lake was investigated; meanwhile, the distribution and removal of these pharmaceuticals in two drinking water treatment plants (DWTPs) and a constructed wetland were evaluated. A high detection frequency (>70%) in the Taihu Lake was observed for nearly all the 25 pharmaceutics. Chlortetracycline (234.7 ng L −1 ), chloramphenicol (27.1 ng L −1 ), erythromycin (72.6 ng L −1 ), PAR (71.7 ng L −1 ), and CMZP (23.6 ng L −1 ) are compounds with both a high detection frequency (100%) and the highest concentrations, suggesting their wide use in the Taihu Basin. Higher concentrations of chloramphenicols, macrolides, PAR, and CMZP were observed in dry season than in wet season, probably due to the low flow conditions of the lake in winter and the properties of pharmaceuticals. The overall contamination levels of antibiotic pharmaceutics (0.2–74.9 ng L −1 ) in the Taihu Lake were lower than or comparable to those reported worldwide. However, for nonantibiotic pharmaceutics, PAR (45.0 ng L −1 ) and CMZP (14.5 ng L −1 ), significantly higher concentrations were observed in the Taihu Lake than at a global scale. High detection frequencies of 25 pharmaceuticals were observed in both the two DWTPs (100%) and the wetland (>60%) except for florfenicol and sulfapyridine. The removal efficacies of the studied pharmaceuticals in DWTP B with advanced treatment processes including ozonation and granular activated carbon filtration (16.7–100%) were superior to DWTP A with conventional treatment processes (2.9–100%), except for sulfonamides. Wetland C with the constructed root channel technology was efficient (24.2–100%) for removing most pharmaceuticals. This work suggests that the application of cost-effective technologies such as constructed wetlands should be considered as an efficient alternative for removing pharmaceuticals from water supply sources.

Identification and expression patterns of 20-hydroxyecdysone-responsive genes from Procambarus clarkii - Bao-Jian Zhu; Lin Tang; Ying-Ying Yu; Dao-Jun Wang; Chao-Liang Liu (Genes & Genomics, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Naturally occurring furanoditerpenoids: distribution, chemistry and their pharmacological activities - Han Bao; Qingwen Zhang; Yang Ye; Ligen Lin (Phytochemistry Reviews, 2017)

Retraction Note to: Explanation of liquefaction in after shock of the 2011 great east Japan earthquake using numerical analysis - Xiao-Hua Bao; Guan-Lin Ye; Bin Ye (Natural Hazards, 2017)

Deformation and failure of a tunnel in the restraining bend of a strike–slip fault zone: an example from Hengshan Mountain, Shanxi Province, China - Daming Lin; Renmao Yuan; Yanjun Shang; Weixing Bao; Kaiyang Wang; Zhongjian Zhang; Kun Li; Wantong He (Bulletin of Engineering Geology and the Environment, 2017)

Migration of styrene and ethylbenzene from virgin and recycled expanded polystyrene containers and discrimination of these two kinds of polystyrene by principal component analysis - Qin-Bao Lin; Xue-Chao Song; Hong Fang; Yu-Mei Wu; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2017)

Inhibitory Effect of Endomorphin-2 Binding to the μ-Opioid Receptor in the Rat Pre-Bötzinger Complex on the Breathing Activity - Jian Qi; Hui Li; Ting-Bao Zhao; Ya-Cheng Lu; Ting Zhang; Jin-Lian Li; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2017)

Genome-Wide Discovery of Tissue-Specific Genes in Maize - Feng Lin; Huabin Bao; Jun Yang; Yuhe Liu; Huixue Dai; Han Zhao (Plant Molecular Biology Reporter, 2016)

Ten polymorphic microsatellite markers characterized for Schizothorax pseudaksaiensis and applied for population genetic analysis - MING MING BAO; QIONG ZHOU; CONG XIN XIE; LIN GANG CAI; JIAN GONG NIU; HONG LI (Journal of Genetics, 2016)

Secondary metabolites from marine-derived Streptomyces antibioticus strain H74-21 - Shuna Fu; Fan Wang; Hongyu Li; Yixuan Bao; Yu Yang; Huifang Shen; Birun Lin; Guangxiong Zhou (Natural Product Research, 2016)

Research on China export structure adjustment: an embodied carbon perspective - Pi-qin Gong; Bao-jun Tang; Yu-chong Xiao; Gao-jie Lin; Jian-yun Liu (Natural Hazards, 2016)

Alleviation of Lead-Induced Apoptosis by Puerarin via Inhibiting Mitochondrial Permeability Transition Pore Opening in Primary Cultures of Rat Proximal Tubular Cells - Zhong-Kun Wang; Xue-Lei Zhou; Xiang-Bin Song; Dong-Ming Zhuang; Zhen-Yong Wang; Du-Bao Yang; Lin Wang (Biological Trace Element Research, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

A genome-wide analysis of the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) gene family in barley (Hordeum vulgare L.) - Bao-jian Guo; Jun Wang; Shen Lin; Zheng Tian; Kai Zhou; Hai-ye Luan; Chao Lyu; Xin-zhong Zhang; Ru-gen Xu (Journal of Zhejiang University-SCIENCE B, 2016)

An Epigenetic Mechanism of High Gdnf Transcription in Glioma Cells Revealed by Specific Sequence Methylation - Bao-Le Zhang; Jie Liu; Yu Lei; Ye Xiong; Heng Li; Xiaoqian Lin; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2016)

Historical biogeography of the short‐faced scorpionflies (Insecta: Mecoptera: Panorpodidae) - Gui‐Lin Hu; Bao‐Zhen Hua (Journal of Biogeography, 2016)
Aim Panorpodidae is a species‐poor family of Mecoptera, containing only 13 species in its two genera, Panorpodes and Brachypanorpa . They are found disjunctly in eastern Asia and North America, and this distribution has been deeply affected by the region's complex geological and climatic history. We calculate a time‐calibrated molecular phylogeny and use it to reconstruct the historical biogeography of the Panorpodidae, in order to explore the family's phylogenetic origin and the biogeographical process that resulted in the present disjunct distribution. Location Eastern Asia and North America. Methods Sequence data from mitochondrial ( COI and COII ) and nuclear DNA ( 28S and EF ‐1 α) were assembled from eight ingroup species. A phylogeny was reconstructed using maximum‐likelihood analysis and Bayesian inference, and divergence times were estimated using fossil‐calibrated Bayesian analysis. Ancestral areas were reconstructed with rasp 3.02, implementing dispersal–vicariance analysis, dispersal–extinction–cladogenesis and Bayesian binary MCMC . Results The initial diversification of Panorpodidae occurred during the Ypresian ( c. 53.9 Ma). A wide ancestral distribution in eastern Asia and western North America was inferred from the biogeographical analyses. The original range of Panorpodes across eastern Asia and western North America was fragmented by intercontinental vicariance. The genus Brachypanorpa was initially restricted to western North America and subsequently dispersed into eastern regions of North America. Main conclusions Two alternative biogeographical patterns were recovered. Either Panorpodidae was restricted to western North America in the Eocene and subsequently dispersed into eastern Asia or – more reasonably – it was widely distributed in western North America, eastern Asia and Europe during the Eocene. Our biogeographical reconstructions corroborate the significant role of vicariance in shaping the current eastern Asian and North American disjunction in Panorpodes . The geographical separation of western and eastern North American Brachypanorpa species is likely to have resulted from the uplift of the Rocky Mountains and the emergence of grassland biomes in central North America.

Recent research progress and prospects in tourism geography of China - Lin Lu; Jie Bao; Jianfeng Huang; Qijing Zhu; Chenglin Mu; Xiaole Chu; Yan Xu; Xiaoli Zha (Journal of Geographical Sciences, 2016)

Microbial community in a multi-trophic aquaculture system of Apostichopus japonicus, Styela clava and microalgae - Jian Lin; Bao Ju; Yanan Yao; Xiaoming Lin; Ronglian Xing; Li Teng; Aili Jiang (Aquaculture International, 2016)

PSI photoinhibition is more related to electron transfer from PSII to PSI rather than PSI redox state in Psychotria rubra - Wei Huang; Ying-Jie Yang; Jiao-Lin Zhang; Hong Hu; Shi-Bao Zhang (Photosynthesis Research, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Paleoclimatic record from Chumbur-Kosa section in Sea of Azov region since Marine Isotope Stage 11 - Ye Liang; Tai-bao Yang; Andrey Aleksevitch Velichko; Biao Zeng; Pei-hong Shi; Lin-dong Wang; Yi He; Jie Chen; Yu Chen (Journal of Mountain Science, 2016)

Transcriptomic analysis of the succulent xerophyte Zygophyllum xanthoxylum in response to salt treatment and osmotic stress - Qing Ma; Ai-Ke Bao; Wei-Wei Chai; Wen-Ying Wang; Jin-Lin Zhang; Yi-Xiao Li; Suo-Min Wang (Plant and Soil, 2016)

Interpreting sedimentation dynamics at Longxi catchment in the Three Gorges Area, China, using Cs-137 activity, particle size and rainfall erosivity - Jin-zhang Gao; Yi Long; Xin-bao Zhang; Adrian L. Collins; Xiu-bin He; Yun-qi Zhang; Zhong-lin Shi (Journal of Mountain Science, 2016)

Mitochondrial permeability transition and its regulatory components are implicated in apoptosis of primary cultures of rat proximal tubular cells exposed to lead - Gang Liu; Zhong-Kun Wang; Zhen-Yong Wang; Du-Bao Yang; Zong-Ping Liu; Lin Wang (Archives of Toxicology, 2016)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Heterologous expression of two Physcomitrella patens group 3 late embryogenesis abundant protein (LEA3) genes confers salinity tolerance in arabidopsis - Jing Du; Lei Wang; Xiaochen Zhang; Xuan Xiao; Fang Wang; Pingliang Lin; Fang Bao; Yong Hu; Yikun He (Journal of Plant Biology, 2016)

Differential expression of ATP-gated P2X receptors in DRG between chronic neuropathic pain and visceralgia rat models - Lin Chen; Yu-wei Liu; Kai Yue; Qin Ru; Qi Xiong; Bao-miao Ma; Xiang Tian; Chao-ying Li (Purinergic Signalling, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Influence of water-dispersible colloids from organic manure on the mechanism of metal transport in historically contaminated soils: coupling colloid fractionation with high-energy synchrotron analysis - Qi Lin; Xin Xu; Qibei Bao; Kokyo Oh; Dongling Chen; Lijuan Zhang; Xiaodong Shen (Journal of Soils and Sediments, 2016)

Scutellarin Alleviates Behavioral Deficits in a Mouse Model of Multiple Sclerosis, Possibly Through Protecting Neural Stem Cells - Wei-Wei Wang; Lin Lu; Tian-Hao Bao; Hong-Miao Zhang; Jing Yuan; Wei Miao; Shu-Fen Wang; Zhi-Cheng Xiao (Journal of Molecular Neuroscience, 2016)

Neuroprotective Effect Is Driven Through the Upregulation of CB1 Receptor in Experimental Autoimmune Encephalomyelitis - Zhi-Yin Lou; Wen-Bo Yu; Jie Chen; Lin Li; Li-Sheng Jiang; Bao-Guo Xiao; Zhen-Guo Liu (Journal of Molecular Neuroscience, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The complete mitochondrial genome of fall armyworm Spodoptera frugiperda (Lepidoptera:Noctuidae) - Qiu-Ning Liu; Xin-Yue Chai; Dan-Dan Bian; Bao-Ming Ge; Chun-Lin Zhou; Bo-Ping Tang (Genes & Genomics, 2016)

RETRACTED ARTICLE: Effects of Repetitive Transcranial Magnetic Stimulation on Cognitive Impairment in Stroke Patients: A Meta-Analysis - Lei Cao; Rui Zhao; Su Huo; Ju-Bao Du; Lin Liu; Yan-Ming Zhang; Wei-Qun Song (Molecular Neurobiology, 2015)

Effects of 3,5-Diiodotyrosine and Potassium Iodide on Thyroid Function and Oxidative Stress in Iodine-Excess Wistar Rats - Dan Liu; Xinying Lin; Fugui Yu; Man Zhang; Hongxia Chen; Wei Bao; Xia Wang (Biological Trace Element Research, 2015)

Soil labile organic carbon fractions in rhizosphere soil in citrus plantations in the Three Gorges Reservoir Area - Guo-Mei Jia; Bao-Lin Zhang; Jun-Tao Niu; Li-Ming Wang; Fang-Qing Chen (Agroforestry Systems, 2015)

DNA Methylation Changes Induced in Rice by Exposure to High Concentrations of the Nitric Oxide Modulator, Sodium Nitroprusside - Xiufang Ou; Tingting Zhuang; Wenchao Yin; Yiling Miao; Bo Wang; Yunhong Zhang; Xiuyun Lin; Chunming Xu; Diter von Wettstein; Sachin Rustgi; Bao Liu (Plant Molecular Biology Reporter, 2015)

Mobilization of Diverse Transposable Elements in Rice Induced by Alien Pollination Without Entailing Genetic Introgression - Ying Wu; Tingting Jiang; Yue Sun; Zeyang Wang; Guizhen Guo; Shuai Sun; Jie Wang; Ning Li; Zhenhui Wang; Di Zhang; Yan Bai; Yang Gao; et al. (Plant Molecular Biology Reporter, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Effect of antioxidants and light stabilisers on silver migration from nanosilver-polyethylene composite packaging films into food simulants - Qi-Zhi Su; Qin-Bao Lin; Chao-Fang Chen; Yu-Mei Wu; Li-Bing Wu; Xiao-Qing Chen; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2015)

Subjective present: a window of temporal integration indexed by mismatch negativity - Lingyan Wang; Xiaoxiong Lin; Bin Zhou; Ernst Pöppel; Yan Bao (Cognitive Processing, 2015)

Pseudonocardia nematodicida sp. nov., isolated from mangrove sediment in Hainan, China - Min Liu; Shan-shan Xing; Wei-dao Yuan; Hua Wei; Qian-guang Sun; Xiang-zhi Lin; Hui-qin Huang; Shi-xiang Bao (Antonie van Leeuwenhoek, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

A Systematic Study of Topography Effect of ERT Based on 3-D Modeling and Inversion - De-Bao Lu; Qi-You Zhou; S. A. Junejo; An-Lin Xiao (Pure and Applied Geophysics, 2015)

Phylogeny and taxonomy of the genus Abundisporus (Polyporales, Basidiomycota) - Chang-Lin Zhao; Hong Chen; Jie Song; Bao-Kai Cui (Mycological Progress, 2015)

Development of 90 EST-SNP markers in blood clam (Tegillarca granosa) using high resolution melting (HRM) - Yinghui Dong; Songfu Shi; Yongbo Bao; Hanhan Yao; Yan Jing; Zhihua Lin (Conservation Genetics Resources, 2015)

Nocardiopsis mangrovei sp. nov., isolated from mangrove sediment - Hui-qin Huang; Shan-shan Xing; Wei-dao Yuan; Ying Wang; Min Liu; Qian-guang Sun; Xiang-zhi Lin; Shi-xiang Bao (Antonie van Leeuwenhoek, 2015)

Prefrontal cortical α2A-adrenoceptors and a possible primate model of attention deficit and hyperactivity disorder - Chao-Lin Ma; Xuan Sun; Fei Luo; Bao-Ming Li (Neuroscience Bulletin, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

17β-Estradiol protects against apoptosis induced by interleukin-1β in rat nucleus pulposus cells by down-regulating MMP-3 and MMP-13 - Si-Dong Yang; Da-Long Yang; Ya-Peng Sun; Bao-Lin Wang; Lei Ma; Shi-Qing Feng; Wen-Yuan Ding (Apoptosis, 2015)

A Brassica napus PHT1 phosphate transporter, BnPht1;4, promotes phosphate uptake and affects roots architecture of transgenic Arabidopsis - Feng Ren; Cai-Zhi Zhao; Chun-Sen Liu; Ke-Lin Huang; Qian-Qian Guo; Li-Li Chang; Huan Xiong; Xue-Bao Li (Plant Molecular Biology, 2014)

RETRACTED ARTICLE: Explanation of liquefaction in after shock of the 2011 great east Japan earthquake using numerical analysis - Xiao-Hua Bao; Guan-Lin Ye; Bin Ye (Natural Hazards, 2014)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Correlated evolution in traits influencing leaf water balance in Dendrobium (Orchidaceae) - Mei Sun; Shi-Jian Yang; Jiao-Lin Zhang; Megan Bartlett; Shi-Bao Zhang (Plant Ecology, 2014)

Trehalose Alleviates PC12 Neuronal Death Mediated by Lipopolysaccharide-Stimulated BV-2 Cells via Inhibiting Nuclear Transcription Factor NF-κB and AP-1 Activation - Qing He; Ying Wang; Wei Lin; Qiong Zhang; Jue Zhao; Feng-Tao Liu; Yi-Lin Tang; Bao-guo Xiao; Jian Wang (Neurotoxicity Research, 2014)

The low expression of Dmrt7 is associated with spermatogenic arrest in cattle-yak - Ping Yan; Lin Xiang; Xian Guo; Peng-Jia Bao; Shuai Jin; Xiao-Yun Wu (Molecular Biology Reports, 2014)

Analytical Theory for One-Dimensional Consolidation of Soil Induced by Time-Dependent Pumping and Loading - Kang-He Xie; Da-Zhong Huang; Yu-Lin Wang; Yue-Bao Deng (Marine Georesources & Geotechnology, 2014)

Effects of extreme temperature on seedling establishment of nonnative invasive plants - Qian-Qian Hou; Bao-Ming Chen; Shao-Lin Peng; Lei-Yi Chen (Biological Invasions, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Flammeopellis bambusicola gen. et. sp. nov. (Polyporales, Basidiomycota) evidenced by morphological characters and phylogenetic analysis - Chang-Lin Zhao; Xin-Sheng He; Kun-Yuan Wanghe; Bao-Kai Cui; Yu-Cheng Dai (Mycological Progress, 2014)

Migration of Ti from nano-TiO 2 -polyethylene composite packaging into food simulants - Qin-Bao Lin; He Li; Huai-Ning Zhong; Quan Zhao; Da-Hui Xiao; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2014)

Sorafenib Inhibition of Hepatic Stellate Cell Proliferation in Tumor Microenvironment of Hepatocellular Carcinoma: A Study of the Sorafenib Mechanisms - Zhi-min Geng; Rajiv Kumar Jha; Bo Li; Chen Chen; Wen-zhi Li; Jian-bao Zheng; Lin Wang; Sha Huanchen (Cell Biochemistry and Biophysics, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Microscopic research on a multi-source traditional Chinese medicine, Astragali Radix - Kun-Zi Yu; Jing Liu; Bao-Lin Guo; Zhong-Zhen Zhao; Hao Hong; Hu-Biao Chen; Shao-Qing Cai (Journal of Natural Medicines, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Construction of an integrative linkage map and QTL mapping of grain yield-related traits using three related wheat RIL populations - Fa Cui; Chunhua Zhao; Anming Ding; Jun Li; Lin Wang; Xingfeng Li; Yinguang Bao; Junming Li; Honggang Wang (Theoretical and Applied Genetics, 2014)

Genetic diversity analysis of yams (Dioscorea spp.) cultivated in China using ISSR and SRAP markers - Zhi Gang Wu; Xiao Xia Li; Xin Chun Lin; Wu Jiang; Zheng Ming Tao; Nitin Mantri; Chuan Yin Fan; Xiao Qing Bao (Genetic Resources and Crop Evolution, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

Nanomedicine: Tiny Particles and Machines Give Huge Gains - Sheng Tong; Eli J. Fine; Yanni Lin; Thomas J. Cradick; Gang Bao (Annals of Biomedical Engineering, 2014)

ZxSOS1 is essential for long-distance transport and spatial distribution of Na+ and K+ in the xerophyte Zygophyllum xanthoxylum - Qing Ma; Yi-Xiao Li; Hui-Jun Yuan; Jing Hu; Li Wei; Ai-Ke Bao; Jin-Lin Zhang; Suo-Min Wang (Plant and Soil, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Characterization of the Zhikong Scallop (Chlamys farreri) Mantle Transcriptome and Identification of Biomineralization-Related Genes - Mingjun Shi; Ya Lin; Guangrui Xu; Liping Xie; Xiaoli Hu; Zhenmin Bao; Rongqing Zhang (Marine Biotechnology, 2013)

EGCG inhibit chemical reactivity of iron through forming an Ngal–EGCG–iron complex - Guan-Hu Bao; Jie Xu; Feng-Lin Hu; Xiao-Chun Wan; Shi-Xian Deng; Jonathan Barasch (BioMetals, 2013)

A tandem-repeat galectin from blood clam Tegillarca granosa and its induced mRNA expression response against bacterial challenge - Yongbo Bao; Haoping Shen; Huashan Zhou; Yinghui Dong; Zhihua Lin (Genes & Genomics, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Genetic and epigenetic differentiation between natural Betula ermanii (Betulaceae) populations inhabiting contrasting habitats - Wei-Qing Wu; Ma Re Yi; Xin-Feng Wang; Li-Li Ma; Lily Jiang; Xi-Wen Li; Hong-Xing Xiao; Ming-Zhou Sun; Lin-Feng Li; Bao Liu (Tree Genetics & Genomes, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Conditional and unconditional QTL mapping of drought-tolerance-related traits of wheat seedling using two related RIL populations - HONG ZHANG; FA CUI; LIN WANG; JUN LI; ANMING DING; CHUNHUA ZHAO; YINGUANG BAO; QIUPING YANG; HONGGANG WANG (Journal of Genetics, 2013)

Potential hydraulic efficiency in angiosperm trees increases with growth‐site temperature but has no trade‐off with mechanical strength - Shi‐Bao Zhang; Kun‐Fang Cao; Ze‐Xin Fan; Jiao‐Lin Zhang (Global Ecology and Biogeography, 2013)
Aim Xylem structures are closely related to a tree's hydraulic efficiency and mechanical stability, both of which affect the life history and ecological strategy of a species. Although mechanical strength and hydraulic capacity can be shaped by the environment, no such associations between hydraulic efficiency and climatic variables have been reported across a wide range of tree species. Location Y unnan, south‐west C hina. Methods We compiled a data set for vessel density, vessel diameter ( D ), potential hydraulic conductivity ( K p ), wood density ( WD ), modulus of rupture ( MOR ) and modulus of elasticity ( MOE ) from 316 angiosperm tree species. Our objective was to examine the correlations among xylem traits and climatic variables. We hypothesized that both hydraulic efficiency and mechanical strength would vary along climatic gradients, but that a trade‐off would occur between them. Results All xylem traits varied significantly across species, but the magnitudes of variation were greater for vessel traits than for mechanical properties. Values for K p and D increased with mean annual temperature ( MAT ) in both evergreen and deciduous trees, but they were significantly correlated with aridity index ( AI ) in evergreen species only. Both WD and MOR were significantly correlated with MAT only in evergreen trees. MOR decreased with increasing AI in the evergreens, but not in deciduous trees. These findings indicated that xylem development in evergreens is more sensitive to environmental changes than in deciduous trees. However, stem hydraulic traits are independent of mechanical properties. Main conclusions Consistent with our hypothesis, both hydraulic efficiency and mechanical strength of angiosperm trees are influenced by the environment, with temperature having a more important effect on hydraulic efficiency than precipitation. However, no trade‐off exists between efficiency and strength. This absence of a link is explained because angiosperms have xylem tissue that specifically functions in either mechanical strength or water transport.

Quantitative analysis of the association between interleukin-10 1082A/G polymorphism and susceptibility to sepsis - Lin Ouyang; You-Di Lv; Can Hou; Guo-Bao Wu; Zhi-Hui He (Molecular Biology Reports, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

The Flexible Global Ocean-Atmosphere-Land system model, Spectral Version 2: FGOALS-s2 - Qing Bao; Pengfei Lin; Tianjun Zhou; Yimin Liu; Yongqiang Yu; Guoxiong Wu; Bian He; Jie He; Lijuan Li; Jiandong Li; Yangchun Li; Hailong Liu; et al. (Advances in Atmospheric Sciences, 2013)

The flexible global ocean-atmosphere-land system model, Grid-point Version 2: FGOALS-g2 - Lijuan Li; Pengfei Lin; Yongqiang Yu; Bin Wang; Tianjun Zhou; Li Liu; Jiping Liu; Qing Bao; Shiming Xu; Wenyu Huang; Kun Xia; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

Pseudomonas aeruginosa isolates of distinct sub-genotypes exhibit similar potential of antimicrobial resistance by drugs exposure - Zhen-Hong Liu; Yan Xu; Li-Bo Duo; Yu Liu; Zhao-Zhen Xu; Jane L. Burns; Gui-Rong Liu; Bao-Feng Yang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2013)

Protection of guinea pigs by vaccination with a recombinant swinepox virus co-expressing HA1 genes of swine H1N1 and H3N2 influenza viruses - Jiarong Xu; Deji Yang; Dongyan Huang; Jiaping Xu; Shichao Liu; Huixing Lin; Haodan Zhu; Bao Liu; Chengping Lu (Archives of Virology, 2013)

MicroRNA-384-5p regulates ischemia-induced cardioprotection by targeting phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit delta (PI3K p110δ) - Yanyan Bao; Chengren Lin; Junguo Ren; Jianxun Liu (Apoptosis, 2013)

Removal of anionic azo dye from aqueous solution via an adsorption–photosensitized regeneration process on a TiO2 surface - Nan Bao; Yuan Li; Xiao-Hong Yu; Jun-Jian Niu; Guo-Lin Wu; Xiao-Hong Xu (Environmental Science and Pollution Research, 2013)

The antidepressant effect of secoisolariciresinol, a lignan-type phytoestrogen constituent of flaxseed, on ovariectomized mice - Ying-Feng Wang; Zhi-Kun Xu; Dong-Hui Yang; Hai-Yan Yao; Bao-Shan Ku; Xiao-Qing Ma; Cheng-Zhi Wang; Shu-Lin Liu; Shao-Qing Cai (Journal of Natural Medicines, 2013)

The application of flux-form semi-Lagrangian transport scheme in a spectral atmosphere model - Xiaocong Wang; Yimin Liu; Guoxiong Wu; Shian-Jiann Lin; Qing Bao (Advances in Atmospheric Sciences, 2013)

Characterization and Expression of a Phytochelatin Synthase Gene in Birch-leaf Pear (Pyrus betulaefolia Bunge) - You Hong Chang; Hui Li; Yu Cong; Jing Lin; Bao Long Sheng (Plant Molecular Biology Reporter, 2012)

Identification of a new gene encoding 5-enolpyruvylshikimate-3-phosphate synthase using genomic library construction strategy - Chang-Yan Zhou; Yong-Sheng Tian; Zhi-Sheng Xu; Wei Zhao; Chen Chen; Wen-Hua Bao; Lin Bian; Run Cai; Ai-Zhong Wu (Molecular Biology Reports, 2012)

Characterization of 62 polymorphic EST-SSR markers in the blood clam (Tegillarca granosa) and their cross-amplification in Scapharca subcrenata - Yinghui Dong; Hanhan Yao; Zhihua Lin; Lingling Zhang; Zhenmin Bao (Conservation Genetics Resources, 2012)

Dramatic genotypic difference in, and effect of genetic crossing on, tissue culture-induced mobility of retrotransposon Tos17 in rice - Chunjing Lin; Xiuyun Lin; Lanjuan Hu; Jingjing Yang; Tianqi Zhou; Likun Long; Chunming Xu; Shaochen Xing; Bao Qi; Yingshan Dong; Bao Liu (Plant Cell Reports, 2012)

The Response of Soil Nematode Community to Nitrogen, Water, and Grazing History in the Inner Mongolian Steppe, China - Wei-bin Ruan; Yuan Sang; Qing Chen; Xiang Zhu; Shan Lin; Yu-bao Gao (Ecosystems, 2012)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Molecular characterization and phylogenetic analysis of Sugarcane yellow leaf virus isolates from China - San-Ji Gao; Yi-Hua Lin; Yong-Bao Pan; Mona B. Damaj; Qin-Nan Wang; T. Erik Mirkov; Ru-Kai Chen (Virus Genes, 2012)

Is the Evolution of Viviparity Accompanied by a Relative Increase in Maternal Abdomen Size in Lizards? - Yan-Yan Sun; Yu Du; Jing Yang; Tian-Bao Fu; Chi-Xian Lin; Xiang Ji (Evolutionary Biology, 2012)

Juglanthraquinone C, a novel natural compound derived from Juglans mandshurica Maxim, induces S phase arrest and apoptosis in HepG2 cells - Yao Yao; Yu-Wei Zhang; Lu-Guo Sun; Biao Liu; Yong-Li Bao; Hua Lin; Yu Zhang; Li-Hua Zheng; Ying Sun; Chun-Lei Yu; Yin Wu; Guan-Nan Wang; et al. (Apoptosis, 2012)

Leaf element concentrations of terrestrial plants across China are influenced by taxonomy and the environment - Shi‐Bao Zhang; Jiao‐Lin Zhang; J. W. Ferry Slik; Kun‐Fang Cao (Global Ecology and Biogeography, 2012)
Aim The productivity, functioning and biogeochemical cycles of terrestrial ecosystems are strongly affected by leaf element concentrations. Understanding the biological and ecological factors affecting leaf element concentrations is therefore important for modelling the productivity and nutrient fluxes of ecosystems and their responses to global change. The present study aimed to determine how leaf element concentrations are linked to taxonomy and the environment. Location China. Methods The concentrations of 10 leaf elements of 702 terrestrial plant species from different biomes were extracted from publications. The links between environmental variables, taxonomy and leaf elements were analyzed using phylogenetically comparative methods and partial Mantel tests. Results Taxonomy had stronger effects on leaf S and SiO 2 than latitude, explaining 40.2–43.9% of total variation, whereas latitude had stronger effects on leaf N, P, K, Fe, Al, Mn, Na and Ca concentrations, explaining 19.5–52.1% of total variation. Leaf N, S, Al, Fe and Na concentrations were correlated with mean annual precipitation (MAP), while leaf N, P and Fe concentrations were correlated with mean annual temperature (MAT). Latitude, MAP and MAT were significantly correlated with the first axis of a principal components analysis (PCA). This first axis was associated with leaf elements involved in protein synthesis and photosynthesis. The other PCA axes, which were not correlated with MAT, latitude and MAP, were associated with leaf elements responsible for cell structure and enzymes. Main conclusions Leaf element concentrations of terrestrial plants in China were correlated with climate, latitude and taxonomy. With the exception of S and SiO 2 , the environmental factors were more important in explaining leaf element variation than taxonomy. Therefore, changes in temperature and precipitation will directly affect the spatial patterns of leaf elements and thus the associated nutrient fluxes and ecosystem functioning.

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

miR-15b and miR-16 regulate TNF mediated hepatocyte apoptosis via BCL2 in acute liver failure - Fangmei An; Bangdong Gong; Hui Wang; Dongshan Yu; Gangde Zhao; Lanyi Lin; Weiliang Tang; Hong Yu; Shisan Bao; Qing Xie (Apoptosis, 2012)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

A new species of Perenniporia (Polyporales, Basidiomycota) described from southern China based on morphological and molecular characters - Chang-Lin Zhao; Bao-Kai Cui (Mycological Progress, 2012)

Pt and Pd in sediments from the Pearl River Estuary, South China: background levels, distribution, and source - Li-feng Zhong; Wen Yan; Jie Li; Xiang-lin Tu; Bao-ming Liu; Zhen Xia (Environmental Science and Pollution Research, 2012)

Membrane Bioreactors for Industrial Wastewater Treatment: A Critical Review - Hongjun Lin; Weijue Gao; Fangang Meng; Bao-Qiang Liao; Kam-Tin Leung; Leihong Zhao; Jianrong Chen; Huachang Hong (Critical Reviews in Environmental Science and Technology, 2012)

Cyclic electron flow plays an important role in photoprotection for the resurrection plant Paraboea rufescens under drought stress - Wei Huang; Shi-Jian Yang; Shi-Bao Zhang; Jiao-Lin Zhang; Kun-Fang Cao (Planta, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

Water Resources Flows Related to Urbanization in China: Challenges and Perspectives for Water Management and Urban Development - Chao Bao; Chuang-lin Fang (Water Resources Management, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Olig1 and ID4 interactions in living cells visualized by bimolecular fluorescence complementation technique - Shu-Jun Guo; Jian-Guo Hu; Bao-Ming Zhao; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü (Molecular Biology Reports, 2011)

Winter heat budget in the Huanghai Sea and the effect from Huanghai Warm Current (Yellow Sea Warm Current) - Lulu Qiao; Xiaohua Wang; Yongzhi Wang; Dexing Wu; Xianwen Bao; Lin Mu (Acta Oceanologica Sinica, 2011)

Vertical structure and seasonal variation of tidal and residual currents in the northern Huanghai Sea - Jun Song; Junru Guo; Lulu Qiao; Lin Mu; Zhigang Yao; Yang Liu; Huan Li; Xianwen Bao; Xiaoyan Sun; Jia Gao (Acta Oceanologica Sinica, 2011)

Tetraethylammonium enhances the rectal and colonic motility in rats and human in vitro - Zhe Li; Zhi-Lin Xu; Jing Liang; Ji-Chao Wu; Chao-Wei Hu; Hui Xie; Wen-Chao Ma; Hong-Chi Jiang; Bao-Feng Yang; De-Li Dong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Collateral vessel growth induced by femoral artery ligature is impaired by denervation - Ming-ying Luo; Bao-lin Yang; Feng Ye; Xiaoqiong Wu; Song Peng; Bin Yi; Wei Wang; Wu Zhu; Hua Luo; Jian-Guo Wen; Wei-Jun Cai; Jutta Schaper; et al. (Molecular and Cellular Biochemistry, 2011)

Mapping of quantitative trait loci for fiber and lignin contents from an interspecific cross Oryza sativa × Oryza rufipogon - Jian-kun Xie; Xiang-li Kong; Jie Chen; Biao-lin Hu; Piao Wen; Jie-yun Zhuang; Jin-song Bao (Journal of Zhejiang University-SCIENCE B, 2011)

Conditional QTL mapping for plant height with respect to the length of the spike and internode in two mapping populations of wheat - Fa Cui; Jun Li; Anming Ding; Chunhua Zhao; Lin Wang; Xiuqin Wang; Sishen Li; Yinguang Bao; Xingfeng Li; Deshun Feng; Lingrang Kong; Honggang Wang (Theoretical and Applied Genetics, 2011)

Molecular tagging of a stripe rust resistance gene in Aegilops tauschii - Lin Huang; Lian-Quan Zhang; Bao-Long Liu; Ze-Hong Yan; Bo Zhang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Euphytica, 2011)

Toxic effect of tetracycline exposure on growth, antioxidative and genetic indices of wheat (Triticum aestivum L.) - Xiujie Xie; Qixing Zhou; Dasong Lin; Jianmian Guo; Yanyu Bao (Environmental Science and Pollution Research, 2011)

Do higher resource capture ability and utilization efficiency facilitate the successful invasion of native plants? - Xing-Yan Shen; Shao-Lin Peng; Bao-Ming Chen; Jun-Xiao Pang; Lei-Yi Chen; Hao-Ming Xu; Yu-Ping Hou (Biological Invasions, 2011)

Effects of temperature change on water discharge, and sediment and nutrient loading in the lower Pearl River basin based on SWAT modelling - Ying Li; Bao-Ming Chen; Zhong-Gen Wang; Shao-Lin Peng (Hydrological Sciences Journal, 2011)

An approach to computing topographic wetness index based on maximum downslope gradient - Cheng-Zhi Qin; A-Xing Zhu; Tao Pei; Bao-Lin Li; Thomas Scholten; Thorsten Behrens; Cheng-Hu Zhou (Precision Agriculture, 2011)

Inhibition of an invasive plant (Mikania micrantha H.B.K.) by soils of three different forests in lower subtropical China - Yu-Ping Hou; Shao-Lin Peng; Bao-Ming Chen; Guang-Yan Ni (Biological Invasions, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)

Factors Associated with Determination of Root 22Na+ Influx in the Salt Accumulation Halophyte Suaeda maritima - Jin-Lin Zhang; Anne M. Wetson; Suo-Min Wang; Ali R. Gurmani; Ai-Ke Bao; Chun-Mei Wang (Biological Trace Element Research, 2011)

Grain-size characteristics of sediment in Daniugou peatland in Changbai Mountains, Northeast China: Implications for atmospheric dust deposition - Kunshan Bao; Lin Jia; Xianguo Lu; Guoping Wang (Chinese Geographical Science, 2010)

Propranolol regulates cardiac transient outward potassium channel in rat myocardium via cAMP/PKA after short-term but not after long-term ischemia - Li Zhang; Chao-Qian Xu; Yuan Hong; Jia-Lin Zhang; Ying Liu; Mei Zhao; Yan-Xiu Cao; Yan-Jie Lu; Bao-Feng Yang; Hong-Li Shan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Characterization of dissolved organic matter derived from rice straw at different stages of decay - Hua-Lin Chen; Jiang-Min Zhou; Bao-Hua Xiao (Journal of Soils and Sediments, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Potential Challenges of Climate Change to Orchid Conservation in a Wild Orchid Hotspot in Southwestern China - Hong Liu; Chang-Lin Feng; Yi-Bo Luo; Bao-Shan Chen; Zhong-Sheng Wang; Hong-Ya Gu (The Botanical Review, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

MoFLP1, encoding a novel fungal fasciclin-like protein, is involved in conidiation and pathogenicity in Magnaporthe oryzae - Tong-bao Liu; Guo-qing Chen; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Effects of the invasive plant Mikania micrantha H.B.K. on soil nitrogen availability through allelopathy in South China - Bao-Ming Chen; Shao-Lin Peng; Guang-Yan Ni (Biological Invasions, 2009)

Role of desert annuals in nutrient flow in arid area of Northwestern China: a nutrient reservoir and provider - Bao-Ming Chen; Gen-Xuan Wang; Shao-Lin Peng (Plant Ecology, 2009)

Shear-wave splitting in the southeast of Cathaysia block, South China - Yuan Gao; Jing Wu; Jin-An Cai; Yu-Tao Shi; Shu Lin; Ting Bao; Zu-Ning Li (Journal of Seismology, 2009)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Trefoil factor-3 expression in human colon cancer liver metastasis - Mark Babyatsky; Jing Lin; Xianyang Yio; Anli Chen; Jie-yu Zhang; Yan Zheng; Christina Twyman; Xiuliang Bao; Myron Schwartz; Swan Thung; J. Lawrence Werther; Steven Itzkowitz (Clinical & Experimental Metastasis, 2009)

RNA interference against interleukin-5 attenuates airway inflammation and hyperresponsiveness in an asthma model - Shao-xing Chen; Feng-ying Huang; Guang-hong Tan; Cai-chun Wang; Yong-hao Huang; Hua Wang; Song-lin Zhou; Fan Chen; Ying-ying Lin; Jun-bao Liu (Journal of Zhejiang University-SCIENCE B, 2009)

Estimation of genetic variances in flood tolerance of poplar and selection of resistant F1 generations - Ke-Bing Du; Bao-Xian Shen; Lin Xu; Bing-Kun Tu (Agroforestry Systems, 2008)

A simple and effective method for total RNA isolation of appressoria in Magnaporthe oryzae - Tong-bao Liu; Jian-ping Lu; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Induction of nucleoside phosphorylase in Enterobacter aerogenes and enzymatic synthesis of adenine arabinoside - Xiao-kun Wei; Qing-bao Ding; Lu Zhang; Yong-li Guo; Lin Ou; Chang-lu Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Anatomically preserved lepidodendralean plants from lower permian coal balls of northern China: Achlamydocarpon intermedium sp. nov. - Yi-Long Zhou; Shi-Jun Wang; Jason Hilton; Bao-Lin Tian (Plant Systematics and Evolution, 2008)

Comparative Physicochemical Characterization of Phospholipids Complex of Puerarin Formulated by Conventional and Supercritical Methods - Ying Li; Da-Jian Yang; Shi-Lin Chen; Si-Bao Chen; Albert Sun-Chi Chan (Pharmaceutical Research, 2008)

Timing of UHP metamorphism in the Hong’an area, western Dabie Mountains, China: evidence from zircon U–Pb age, trace element and Hf isotope composition - Yuan-Bao Wu; Shan Gao; Hong-Fei Zhang; Sai-Hong Yang; Wen-Fang Jiao; Yong-Sheng Liu; Hong-Lin Yuan (Contributions to Mineralogy and Petrology, 2007)

Management Implications to Water Resources Constraint Force on Socio-economic System in Rapid Urbanization: A Case Study of the Hexi Corridor, NW China - Chuang-lin Fang; Chao Bao; Jin-chuan Huang (Water Resources Management, 2007)

Cloning, sequencing and expression analysis of the NAR promoter activated during hyphal stage of Magnaporthe grisea - Jian-ping Lu; Zhi-bing Duan; Tong-bao Liu; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Antioxidants and a new dihydroisocoumarins from Polygala hongkongensis Hemsl - Jian-Feng Wu; Si-Bao Chen; Jing-Chun Gao; Hao-Liang Song; Li-Jun Wu; Shi-lin Chen; Peng-Fei Tu (Natural Product Research, 2007)

Distribution of lead in urban soil and its potential risk in Shenyang City, China - Jin-da Wang; Hui-min Ren; Jing-shuang Liu; Jun-bao Yu; Xue-lin Zhang (Chinese Geographical Science, 2006)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

Effects of previous elemental sulfur applications on oxidation of additional applied elemental sulfur in soils - Shutian Li; Bao Lin; Wei Zhou (Biology and Fertility of Soils, 2005)

Multi-stage ponds-wetlands ecosystem for effective wastewater treatment - Jian-feng Peng; Bao-zhen Wang; Lin Wang (Journal of Zhejiang University-SCIENCE B, 2005)

Representative appressorium stage cDNA library of Magnaporthe grisea - Jian-ping Lu; Tong-bao Liu; Xiao-yun Yu; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2005)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)

Oxidation of elemental sulfur in paddy soils as influenced by flooded condition and plant growth in pot experiment - Wei Zhou; Min Wan; Ping He; Shutian Li; Bao Lin (Biology and Fertility of Soils, 2002)

Preprophase band loses its function as a cytokinetic apparatus in mitosis of neck canal mother cell - Qun He; Rui-Lin You; Sodmergen Not Available; Wen-Mei Bao (Protoplasma, 2002)

Spatial-temporal variation of heavy metal elements content in covering soil of reclamation area in fushun coal mine - Jun-bao Yu; Jing-shuang Liu; Jin-da Wang; Zhong-gen Li; Xue-lin Zhang (Chinese Geographical Science, 2002)

Biodiversity and conservation in the Tibetan Plateau - Zhang Bai-ping; Chen Xiao-dong; Li Bao-lin; Yao Yong-hui (Journal of Geographical Sciences, 2002)

Sandy desertification trend in western Northeast China Plain in the past 10 years - Li Bao-lin; Zhou Cheng-hu (Journal of Geographical Sciences, 2001)

Water resources optimization and eco-environmental protection in Qaidam Basin - Fang Chuang-lin; Bao Chao (Journal of Geographical Sciences, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)